Negative electrode material starting material for non-aqueous secondary batteries, negative electrode material for non-aqueous secondary batteries, negative electrode for non-aqueous secondary batteries, and non-aqueous secondary battery

By covering the surface of graphite particles with amorphous carbon and controlling the pore capacity and thermal characteristics, the shortcomings of existing negative electrode materials in high temperature preservation, rapid charging and discharge, and plate expansion are solved, and high capacity and excellent electrochemical performance are achieved.

CN119905591APending Publication Date: 2025-04-29MITSUBISHI CHEM CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510043607.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2019-10-04
Filing Date
2020-03-30
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing negative electrode materials for non-water lithium secondary batteries have shortcomings in high-temperature storage characteristics, fast charging and discharging characteristics and plate expansion.

Method used

By coating the surface of graphite particles with amorphous carbon and controlling the pore volume in the range of 0.01 μm to 1 μm, specific differential thermal analysis method and Raman spectral characteristics are met to improve the performance of the negative electrode material.

Benefits of technology

It achieves a balance between high capacity, excellent fast charging and discharging characteristics, low-temperature input and output characteristics and high-temperature storage characteristics, reducing plate expansion after charging and discharging cycle.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005237668240000791
    Figure BDA0005237668240000791
  • Figure BDA0005237668240000801
    Figure BDA0005237668240000801
  • Figure BDA0005237668240000851
    Figure BDA0005237668240000851
Patent Text Reader

Abstract

The invention provides a negative electrode material for a non-aqueous secondary battery, a negative electrode for a non-aqueous secondary battery containing the negative electrode material for a non-aqueous secondary battery, and a non-aqueous secondary battery. The negative electrode material for a non-aqueous secondary battery can provide a non-aqueous secondary battery having high capacity, excellent rapid charge / discharge characteristics, and excellent balance between low-temperature input / output characteristics and high-temperature storage characteristics. A negative electrode material for nonaqueous secondary batteries, which contains graphite having an amorphous carbon substance in at least a part of the surface thereof, has a cumulative pore volume of 0.100 mL / g or less in the range of micropores of 0.01-1 [mu] m (inclusive), and in a DTA curve obtained by differential thermal analysis (DTA) in an air flow, the pore volume of the negative electrode material for nonaqueous secondary batteries is less than or equal to 0.100 mL / g, and the pore volume of the negative electrode material for nonaqueous secondary batteries is less than or equal to 0.100 mL / g in the range of micropores of 0.01-1 [mu] m (inclusive). At least one of the following conditions 1) and 2) is satisfied. 1) There is no exothermic peak in a temperature range from 550 DEG C to 650 DEG C (inclusive); and (2) an exothermic peak is present in a temperature range from 550 DEG C to 650 DEG C (inclusive), and the area of the exothermic peak is more than 0 [mu] V * s / mg and 90 [mu] V * s / mg or less.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present application is a divisional application of an application with a filing date of March 30, 2020, an application number of 202080025548.5, and an invention name of “Non-aqueous secondary battery negative electrode material raw material, non-aqueous secondary battery negative electrode material, non-aqueous secondary battery negative electrode and non-aqueous secondary battery”. Technical Field

[0002] The present invention relates to a negative electrode material raw material for a non-aqueous secondary battery, a negative electrode material for a non-aqueous secondary battery, a negative electrode for a non-aqueous secondary battery including the negative electrode material for a non-aqueous secondary battery, and a non-aqueous secondary battery. Background Art

[0003] In recent years, with the miniaturization of electronic devices, the demand for high-capacity secondary batteries has continued to increase. In particular, non-aqueous secondary batteries, especially lithium-ion secondary batteries, which have higher energy density and better rapid charge and discharge characteristics than nickel-cadmium batteries and nickel-metal hydride batteries, have attracted much attention. In particular, non-aqueous lithium secondary batteries that include positive and negative electrodes that can absorb and release lithium ions and non-aqueous electrolytes dissolved with lithium salts such as LiPF6 and LiBF4 have been developed and put into practical use.

[0004] As the negative electrode material of the non-aqueous lithium secondary battery, various materials have been proposed, but for reasons such as high capacity and excellent flatness of discharge potential, natural graphite, coke, etc., graphite carbon materials such as artificial graphite, graphitized mesophase pitch, and graphitized carbon fiber obtained by graphitization have been used. In addition, for reasons such as being relatively stable for some electrolytes, amorphous carbon materials are also used. In addition, a carbon material having these two characteristics of high capacity based on graphite and small irreversible capacity and excellent stability of electrolyte based on amorphous carbon is also used, which is coated or attached to the surface of graphite particles.

[0005] Recently, in the field of electric vehicles, high capacity, excellent low-temperature input and output characteristics and other characteristics have been valued. From these viewpoints, in the negative electrode material of the above-mentioned non-aqueous lithium secondary battery, a material coated or attached with amorphous carbon on the surface of graphite particles is used. In such a material, Patent Document 1 discloses a negative electrode material in which the fast charging characteristics are improved by coating amorphous carbon under specific conditions and isotropically pressurizing graphite. In addition, in Patent Document 2, for amorphous carbon coated on graphite particles, a negative electrode material is disclosed, which uses coal tar pitch with a high quinoline content in the raw material to control the atomic concentration of sulfur and nitrogen elements present on the surface, thereby becoming high capacity and improving the charge and discharge characteristics. In addition, Patent Document 3 discloses a negative electrode material, which makes the pressurized load low and the low-temperature output characteristics improved by a carbon material with specific thermal characteristics. In addition, Patent Document 4 discloses a negative electrode material, which is coated with specific amorphous carbon and has a specific pore volume, thereby improving the low-temperature input and output characteristics and high-temperature storage characteristics.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: WO2011 / 052452

[0009] Patent Document 2: WO2012 / 157590

[0010] Patent Document 3: Japanese Patent Application Publication No. 2017-045574

[0011] Patent Document 4: Japanese Patent Application Publication No. 2018-163868

[0012] Patent Document 5: Japanese Patent Application Publication No. 2017-37711 Summary of the invention

[0013] Problem that the invention aims to solve

[0014] According to the research of the inventors, it is known that for the negative electrode material for non-aqueous secondary batteries described in Patent Document 1, the high-temperature storage characteristics are insufficient due to the component of amorphous carbon coated with graphite. In addition, it is known that for the negative electrode materials for non-aqueous secondary batteries described in Patent Documents 2 to 4, their rapid charge and discharge characteristics and high-temperature storage characteristics are insufficient. That is, the first subject of the present invention is to provide a negative electrode material for non-aqueous secondary batteries, and a negative electrode for non-aqueous secondary batteries and non-aqueous secondary batteries containing the negative electrode material for non-aqueous secondary batteries, wherein the negative electrode material for non-aqueous secondary batteries can provide a non-aqueous secondary battery with high capacity, excellent rapid charge and discharge characteristics, and excellent balance between low-temperature input and output characteristics and high-temperature storage characteristics.

[0015] In addition, according to the research of the present inventors, it is known that the non-aqueous secondary battery negative electrode materials described in Patent Documents 1 to 4 cause expansion of the electrode plate after charge and discharge cycles. That is, the second subject of the present invention is to provide a non-aqueous secondary battery negative electrode material raw material, a non-aqueous secondary battery negative electrode material, and a non-aqueous secondary battery negative electrode and a non-aqueous secondary battery containing the same, wherein the non-aqueous secondary battery negative electrode material can provide a non-aqueous secondary battery with high capacity, excellent rapid charging characteristics, and small electrode plate expansion after charge and discharge cycles.

[0016] According to the research of the inventors, it is known that for the negative electrode material for non-aqueous secondary batteries described in Patent Document 1, although it is modified by pressurization treatment in order to control the amount of micropores and adjusted by coating treatment, it is difficult to harden the particles and press them into high density when the amount of amorphous carbon material is simply increased. In addition, it is known that for the negative electrode materials for non-aqueous secondary batteries described in Patent Documents 2 to 4, although the rapid charge and discharge characteristics and high temperature storage characteristics are improved by coating amorphous carbon materials, it is due to the amorphous carbon material that the particles cannot be hardened and the electrode cannot be pressed into high density. In addition, Patent Document 5 improves the capacity and output characteristics by considering the relationship with the compressibility of the amount of amorphous carbon material, but the load and density implemented are low, which is insufficient for further high density. That is, the third subject of the present invention is to provide a negative electrode material for a non-aqueous secondary battery, a negative electrode for a non-aqueous secondary battery and a non-aqueous secondary battery comprising the negative electrode material for a non-aqueous secondary battery, wherein the negative electrode material for a non-aqueous secondary battery is coated with an amorphous carbon material in order to produce a high-capacity battery, and is pressed into a high density with a smaller compressive load, thereby achieving high capacity and small plate expansion.

[0017] Solutions to the problem

[0018] The present inventors have conducted intensive studies to solve the first problem and have found that the problem can be solved by controlling the pore volume within a specific range and providing a non-aqueous secondary battery negative electrode material having thermal properties that satisfy specific conditions.

[0019] [A1] A negative electrode material for a non-aqueous secondary battery, comprising graphite having an amorphous carbon material on at least a portion of its surface,

[0020] The cumulative pore volume of the non-aqueous secondary battery negative electrode material in the range of micropore diameters of 0.01 μm or more and 1 μm or less is 0.100 mL / g or less, and in a DTA curve obtained by differential thermal analysis (DTA) in an air flow, at least one of the following conditions 1) and 2) is satisfied,

[0021] 1) There is no exothermic peak in the temperature range of 550°C or more and 650°C or less,

[0022] 2) It has an exothermic peak in a temperature range of 550° C. to 650° C., and the area of ​​the exothermic peak exceeds 0 μV·s / mg and is 90 μV·s / mg or less.

[0023] [A2] A negative electrode material for a non-aqueous secondary battery, wherein the Raman R1 value calculated by the following formula α is 0.15 or more and 1.00 or less, and the Raman half peak width (Δν B ) is 65cm -1 Over 400cm -1 the following,

[0024] The cumulative pore volume of the non-aqueous secondary battery negative electrode material in the range of micropore diameters of 0.01 μm or more and 1 μm or less is 0.100 mL / g or less, and in a DTA curve obtained by differential thermal analysis (DTA) in an air flow, at least one of the following conditions 1) and 2) is satisfied,

[0025] 1) There is no exothermic peak in the temperature range of 550°C or more and 650°C or less,

[0026] 2) having an exothermic peak in a temperature range of 550°C to 650°C, and an area of ​​the exothermic peak exceeding 0 μV·s / mg and being 90 μV·s / mg or less,

[0027] Formula α:

[0028] [Raman R1 value] = [1360 cm in Raman spectroscopy analysis -1 Nearby peaks P B Strength I B ] / [1580cm -1 Nearby peaks P A Strength I A ].

[0029] [A3] The non-aqueous secondary battery negative electrode material described in [A1] or [A2] above, wherein the DTA curve satisfies the following condition 3):

[0030] 3) Having an exothermic starting temperature in a temperature range of 550°C to 750°C.

[0031] [A4] The non-aqueous secondary battery negative electrode material according to any one of [A1] to [A3] above, wherein the DTA curve satisfies the following condition 4):

[0032] 4) It has an exothermic peak in a temperature range exceeding 650°C and not more than 1000°C.

[0033] [A5] The non-aqueous secondary battery negative electrode material according to any one of [A1] to [A4], wherein the Raman R2 value of the non-aqueous secondary battery negative electrode material calculated by the following formula β is 0.03 or more and 0.60 or less, and the Raman R3 value calculated by the following formula γ is 0.10 or more and 1.00 or less,

[0034] Formula β:

[0035] [Raman R2 value] = [1580cm in Raman spectroscopy analysis -1 Nearby peaks P A With 1360cm -1 Nearby peaks P B The intensity of the valley (minimum) between C ] / [1580cm -1 Nearby peaks P A Strength I A ]

[0036] Formula γ:

[0037] [Raman R3 value] = [1580cm in Raman spectroscopy analysis -1 Nearby peaks P A With 1360cm -1 Nearby peaks P B The intensity of the valley (minimum) between C ] / [1360cm -1 Nearby peaks P B Strength I B ].

[0038] [A6] The non-aqueous secondary battery negative electrode material described in any one of [A1] to [A5] above, wherein the BET specific surface area (SA) is 0.5 m 2 / g or more and 10.0m 2 / g or less.

[0039] [A7] The non-aqueous secondary battery negative electrode material described in any one of [A1] to [A6] above, having a tap density of 0.60 g / cm 3 Above and 1.40g / cm 3 the following.

[0040] [A8] A negative electrode material for a non-aqueous secondary battery as described in any one of [A1] to [A7] above, wherein the interplanar spacing (d002) of the negative electrode material for a non-aqueous secondary battery determined by X-ray diffraction is less than 0.340 nm, and the crystallite size (Lc) in the c-axis direction is greater than 90 nm.

[0041] [A9] A negative electrode for a non-aqueous secondary battery, comprising:

[0042] Current collector, and

[0043] An active material layer is formed on the current collector,

[0044] The active material layer contains the negative electrode material for a non-aqueous secondary battery described in any one of [A1] to [A8].

[0045] [A10] A non-aqueous secondary battery comprising a positive electrode, a negative electrode, and an electrolyte, wherein the negative electrode is the negative electrode for a non-aqueous secondary battery described in [A9] above.

[0046] As a result of intensive research to solve the above-mentioned second problem, the inventors have found that the above-mentioned second problem can be solved by using a non-aqueous secondary battery negative electrode material using a graphite raw material in which the mercury removal amount / mercury introduction amount (B / A) measured by mercury porosimetry is controlled to a specific range. That is, the gist of the second embodiment of the present invention is as follows.

[0047] [B1] A negative electrode material for a non-aqueous secondary battery, comprising graphite, wherein the following formula (1) is 45% or more when the amount of mercury introduced by mercury porosimetry is A and the amount of mercury removed is B.

[0048] Formula (1) B / A×100(%)

[0049] [B2] The negative electrode material for a non-aqueous secondary battery according to [B1] above, wherein the mercury incorporation amount A is 0.001 mL / g or more and 0.5 mL / g or less.

[0050] [B3] The negative electrode raw material for a non-aqueous secondary battery as described in [B1] or [B2] above, wherein the mercury removal amount B is 0.0005 mL / g or more and 0.5 mL / g or less.

[0051] [B4] A non-aqueous secondary battery negative electrode material as described in any one of [B1] to [B3], having a tap density of 0.7 g / cm 3 Above and 1.4g / cm 3 the following.

[0052] [B5] A negative electrode material for a non-aqueous secondary battery, comprising the negative electrode material raw material for a non-aqueous secondary battery according to any one of [B1] to [B4] above.

[0053] [B6] The negative electrode material for a non-aqueous secondary battery as described in [B5] above, wherein the interplanar spacing (d002) of the negative electrode material for a non-aqueous secondary battery obtained by X-ray diffraction is less than 0.34 nm, and the crystallite size (Lc) in the c-axis direction is greater than 90 nm.

[0054] [B7] The non-aqueous secondary battery negative electrode material described in [B5] or [B6] above, wherein the Raman R1 value of the non-aqueous secondary battery negative electrode material calculated by the following formula α is 0.15 or more and 1.00 or less.

[0055] Formula α:

[0056] [Raman R1 value] = [1360 cm in Raman spectroscopy analysis -1 Nearby peaks P B Strength I B ] / [1580cm -1 Nearby peaks P A Strength I A ]

[0057] [B8] A non-aqueous secondary battery using the negative electrode material described in any one of [B5] to [B7] above.

[0058] The inventors of the present invention have conducted in-depth research to solve the above-mentioned third problem, and as a result, they have found that a negative electrode material for a non-aqueous secondary battery, a negative electrode for a non-aqueous secondary battery, and a non-aqueous secondary battery comprising the negative electrode material for a non-aqueous secondary battery can be obtained. The negative electrode material for a non-aqueous secondary battery can provide a non-aqueous secondary battery with good hardness and compressibility relative to the particles and small plate expansion by controlling the pore volume within the particles per unit coverage and controlling the peak of the voids within the particles, thereby completing the present invention.

[0059] [C1] A negative electrode material for a non-aqueous secondary battery, comprising graphite having at least one of an amorphous carbon material and a graphite material on at least a portion of its surface,

[0060] The micropore distribution of the negative electrode material for non-aqueous secondary batteries measured by mercury intrusion has more than two peaks. When the cumulative pore volume below the minimum value between the peak with the smallest micropore diameter and the valley of the next peak is set to y [mL / g], and the coverage of amorphous carbon material and graphite material on the graphite surface is set to x (%), the following formulas (1) and (2) are satisfied, and the micropore diameter of the peak top of the peak with the smallest micropore diameter is less than 360nm.

[0061] Formula (1): y>0.005

[0062] Formula (2): y<-0.006x+0.12.

[0063] [C2] A negative electrode material for a non-aqueous secondary battery, comprising graphite having at least one of an amorphous carbon material and a graphite material on at least a portion of its surface,

[0064] The micropore distribution of the negative electrode material for non-aqueous secondary batteries measured by mercury intrusion porosimetry has more than two peaks, and when the cumulative pore volume below the minimum value between the peak with the smallest micropore diameter and the valley of the next peak is set to y [mL / g], and the coverage of the amorphous carbon material and graphite material on the graphite surface is set to x (%), the following equations (1) and (3) are satisfied.

[0065] Formula (1): y>0.005

[0066] Formula (3): y<-0.006x+0.079

[0067] [C3] The non-aqueous secondary battery negative electrode material described in [C1] or [C2] above, wherein the graphite is natural graphite.

[0068] [C4] The non-aqueous secondary battery negative electrode material described in any one of [C1] to [C3] above, which has a true density of 2.20 g / cm 3 Above and less than 2.262g / cm 3 .

[0069] [C5] The non-aqueous secondary battery negative electrode material described in any one of [C1] to [C4] above, which has a tap density of 0.85 g / cm 3 above.

[0070] [C6] The non-aqueous secondary battery negative electrode material according to any one of [C1] to [C5] above, wherein at least a portion of the surface is covered with an amorphous carbon material.

[0071] [C7] The non-aqueous secondary battery negative electrode material described in any one of [C1] to [C6] above, comprising spherical graphite particles, wherein the spherical graphite particles are obtained by granulating flaky graphite, scale-like graphite, and blocky graphite.

[0072] [C8] The non-aqueous secondary battery negative electrode material described in [C7] above, wherein the granulation treatment is a treatment for imparting at least any of the mechanical energy of impact, compression, friction, and shearing force.

[0073] [C9] The negative electrode material for a non-aqueous secondary battery described in [C7] or [C8] above, wherein the granulation treatment is the following treatment: in a device having a rotating component that rotates at a high speed in a shell, and a rotor provided with a plurality of blades in the shell, the rotor is rotated at a high speed to impart any of impact, compression, friction, and shearing force to graphite introduced into the interior to perform granulation.

[0074] [C10] A negative electrode for a non-aqueous secondary battery, comprising: a current collector; and an active material layer formed on the current collector, wherein the active material layer contains the negative electrode material according to any one of [C1] to [C9] above.

[0075] [C11] A non-aqueous secondary battery comprising a positive electrode, a negative electrode, and an electrolyte, wherein the negative electrode is the negative electrode for a non-aqueous secondary battery described in [C10] above.

[0076] Effects of the Invention

[0077] According to the present invention, through the first method, a negative electrode material for a non-aqueous secondary battery, a negative electrode for a non-aqueous secondary battery and a non-aqueous secondary battery containing the negative electrode material for a non-aqueous secondary battery can be provided, and the negative electrode material for a non-aqueous secondary battery can provide a non-aqueous secondary battery with high capacity, excellent rapid charge and discharge characteristics, and an excellent balance between low-temperature input and output characteristics and high-temperature storage characteristics.

[0078] According to the second embodiment of the present invention, there can be provided a raw material for a negative electrode material for a non-aqueous secondary battery, a negative electrode material for a non-aqueous secondary battery, and a negative electrode for a non-aqueous secondary battery and a non-aqueous secondary battery containing the same. The raw material for a negative electrode material for a non-aqueous secondary battery and the negative electrode material for a non-aqueous secondary battery can provide a non-aqueous secondary battery with high capacity, excellent rapid charging characteristics, and small plate expansion after cycling.

[0079] According to the third embodiment of the present invention, since it is aimed at high-capacity batteries, high density can be achieved by pressing with a small load relative to the hardness of the particles, and the expansion of the electrode plates is small, it is possible to provide a negative electrode material for a non-aqueous secondary battery that can increase the capacity of the non-aqueous secondary battery, and a negative electrode for a non-aqueous secondary battery and a non-aqueous secondary battery containing the negative electrode material for a non-aqueous secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0080] Figure 1 This is a graph showing the relationship between the high-temperature storage characteristics and the low-temperature output characteristics in Examples A1 and A2, Comparative Examples A1 to A3, and Reference Example A1.

[0081] Figure 2 This is a graph showing the relationship between the high-temperature storage characteristics and the low-temperature output characteristics in Examples A3 and A4 and Comparative Examples A4 and A5.

[0082] Figure 3 It is a graph showing the relationship between the amount of mercury removal / the amount of mercury introduction (B / A) and the cycle expansion in Examples B1 to B2 and Comparative Examples B1 to B3.

[0083] Figure 4 This is a graph showing the relationship between the coverage ratio and the pore volume of the pore diameter below the minimum value of the peak of the pore distribution obtained by mercury porosimetry in Examples C1 to C3 and Comparative Examples C1 to C6.

[0084] Figure 5 The results are shown in Table 1. The results are shown in Table 1. The results are shown in Table 1. 3 Graph of required load versus Pellet-Tap.

[0085] Figure 6 It is a graph showing the mercury porosimetry measurement results of Example C1 and Comparative Example C1. DETAILED DESCRIPTION

[0086] The present invention is described in detail below, but the present invention is not limited to the following description and can be implemented after any deformation within the scope of the present invention. It should be noted that in the present invention, when "to" is used and numerical values ​​or physical property values ​​are sandwiched before and after it, the meaning used is to include the values ​​before and after it.

[0087] <A. First embodiment>

[0088] [A1. Negative electrode materials for non-aqueous secondary batteries]

[0089] A non-aqueous secondary battery negative electrode material (hereinafter sometimes referred to as "negative electrode material") involved in one embodiment of the present invention contains graphite having an amorphous carbon substance on at least a portion of its surface, and the cumulative pore volume in the range of micropore diameters of 0.01 μm or more and 1 μm or less in the non-aqueous secondary battery negative electrode material is less than 0.100 mL / g, and in a DTA curve obtained by differential thermal analysis (DTA) in an air flow, at least one of the following conditions 1) and 2) is satisfied.

[0090] 1) There is no exothermic peak in the temperature range of 550°C or more and 650°C or less;

[0091] 2) It has an exothermic peak in a temperature range of 550° C. to 650° C., and the area of ​​the exothermic peak exceeds 0 μV·s / mg and is 90 μV·s / mg or less.

[0092] The negative electrode material for a nonaqueous secondary battery of this embodiment has the following effects: high capacity, excellent rapid charge and discharge characteristics, and excellent balance between low-temperature input and output characteristics and high-temperature storage characteristics. The reason why the present invention has such effects is not certain, but it is believed to be the following.

[0093] In the negative electrode material of the present embodiment, the cumulative pore volume in the range of 0.01 μm or more and 1 μm or less becomes an index of the pore volume present inside the negative electrode material particles. By reducing it to a specific range, when the electrode is pressed to a certain density, compared with the negative electrode material with a large pore volume present inside the particles in the past, it is possible to relatively ensure that the pore volume between the particles is larger. As a result, it can be considered that Li ions can move smoothly in the electrode during charge and discharge, thereby achieving rapid charge and discharge characteristics and excellent low temperature input and output characteristics.

[0094] In addition, in general, amorphous carbon materials are easier to burn than graphite, so there is a tendency to have an exothermic peak on the low temperature side compared to graphite, especially in the case of amorphous carbon materials with insufficient development of carbon structure, this tendency is more significant. For such amorphous carbon materials with insufficient development of carbon structure, Li ions cannot move smoothly inside the amorphous carbon material, so the rapid charge and discharge characteristics and low temperature input and output characteristics are reduced, and the charged Li ions are prone to self-discharge and are prone to cause side reactions with the electrolyte on the particle surface, so there is a tendency for high temperature storage characteristics to deteriorate. In addition, due to the influence of the irreversible capacity of the amorphous carbon material and the increase of side reactions with the electrolyte, there is a tendency for the initial charge and discharge efficiency of the battery to decrease and the battery capacity to decrease.

[0095] On the other hand, in the negative electrode material of the present embodiment, by controlling the carbon structure of the amorphous carbon material to be sufficiently developed and having specific thermal properties, Li ions can move smoothly inside the amorphous carbon material, thereby showing excellent rapid charge and discharge characteristics and low temperature input and output characteristics. In addition, at the same time, the self-discharge of the charged Li ions and the side reactions with the electrolyte can also be suppressed, so it can be inferred that excellent high temperature storage characteristics will be shown. In addition, due to the influence of the irreversible capacity of the amorphous carbon material and the suppression of the side reactions with the electrolyte, there is a tendency for the initial charge and discharge efficiency of the battery to increase and the battery capacity to increase.

[0096] In addition, the negative electrode material according to another embodiment of the present invention is the following negative electrode material:

[0097] The Raman R1 value of the negative electrode material for a non-aqueous secondary battery calculated by the following formula α is 0.20 or more and 1.00 or less, and the Raman half peak width (Δν B ) is 65cm -1 Over 400cm -1 Hereinafter, the cumulative pore volume of the negative electrode material having a micropore diameter in the range of 0.01 μm or more and 1 μm or less is 0.100 mL / g or less, and in the DTA curve obtained by differential thermal analysis (DTA) in an air flow, at least one of the following conditions 1) and 2) is satisfied.

[0098] 1) There is no exothermic peak in the temperature range of 550°C or more and 650°C or less,

[0099] 2) having an exothermic peak in a temperature range of 550°C to 650°C, and an area of ​​the exothermic peak exceeding 0 μV·s / mg and being 90 μV·s / mg or less,

[0100] Formula α:

[0101] [Raman R1 value] = [1360 cm in Raman spectroscopy analysis -1 Nearby peaks P B Strength I B ] / [1580cm -1 Nearby peaks P A Strength I A ].

[0102] The negative electrode material for a nonaqueous secondary battery of this embodiment has the following effects: high capacity, excellent rapid charge and discharge characteristics, and excellent balance between low-temperature input and output characteristics and high-temperature storage characteristics. The reason why the present invention has such effects is not certain, but it is believed to be the following.

[0103] In the negative electrode material of the present embodiment, the cumulative pore volume in the range of 0.01 μm or more and 1 μm or less becomes an index of the pore volume present inside the negative electrode material particles. By reducing it to a specific range, when the electrode is pressed to a certain density, compared with the negative electrode material with a large pore volume present inside the particles in the past, it is possible to relatively ensure that the pore volume between the particles is larger. As a result, it can be considered that Li ions can move smoothly in the electrode during charge and discharge, thereby achieving rapid charge and discharge characteristics and excellent low temperature input and output characteristics.

[0104] In addition, the Raman R1 value, Raman half-peak width (Δν B ) becomes an index of graphite crystallinity on the surface of negative electrode material particles. Increasing them to a specific range means reducing the graphite crystallinity (improving amorphousness) on the surface of negative electrode material particles. It can be considered that by increasing them to a specific range, the insertion / detachment of Li ions on the surface of negative electrode material particles becomes good, and the rapid charge and discharge characteristics and low temperature input and output characteristics are excellent. The graphite crystallinity on the surface of the negative electrode material particles can be adjusted, for example, by adding a carbon material with low graphite crystallinity to at least a portion of the surface of the negative electrode material particles.

[0105] In general, carbon materials with low graphite crystallinity are easier to burn than graphite, so there is a tendency to have an exothermic peak on the low temperature side compared to graphite, especially in the case of carbon materials with insufficient development of carbon structure, this tendency is more significant. For such carbon materials with insufficient development of carbon structure, Li ions cannot move smoothly inside the carbon material, so the rapid charge and discharge characteristics and low temperature input and output characteristics are reduced, and the charged Li ions are prone to self-discharge and are prone to cause side reactions with the electrolyte on the particle surface, so there is a tendency for high temperature storage characteristics to deteriorate. In addition, due to the influence of the irreversible capacity of the carbon material with insufficient development of carbon structure and the increase of side reactions with the electrolyte, there is a tendency for the initial charge and discharge efficiency of the battery to decrease and the battery capacity to decrease.

[0106] On the other hand, in the negative electrode material of the present embodiment, by controlling the carbon structure of the carbon material with low graphite crystallinity to be sufficiently developed and having specific thermal characteristics, Li ions can move smoothly inside the carbon material with low graphite crystallinity, thus showing excellent rapid charge and discharge characteristics and low temperature input and output characteristics. In addition, at the same time, the self-discharge of the charged Li ions and the side reactions with the electrolyte can also be suppressed, so it can be inferred that excellent high temperature storage characteristics will be shown. In addition, due to the influence of the irreversible capacity of the carbon material with low graphite crystallinity and the side reactions with the electrolyte are suppressed, there is a tendency for the initial charge and discharge efficiency of the battery to increase and the battery capacity to increase.

[0107] [A1-1. Physical properties]

[0108] The negative electrode material of one embodiment of the present invention satisfies the pore volume and thermal characteristics described below. In addition, the negative electrode material of one embodiment of the present invention satisfies the Raman characteristics described below. In addition, the negative electrode material of one embodiment of the present invention preferably satisfies the following physical properties.

[0109] <A1-1-1. Cumulative pore volume>

[0110] In the negative electrode material of one embodiment of the present invention, the cumulative pore volume in the range of 0.01 μm or more and 1 μm or less is a value measured using mercury intrusion method (mercury porosimetry), and the cumulative pore volume is 0.100 mL / g or less, preferably 0.080 mL / g or less, more preferably 0.070 mL / g or less, further preferably 0.060 mL / g or less, particularly preferably 0.050 mL / g or less, and most preferably 0.030 mL / g or less, on the other hand, preferably 0.001 mL / g or more, more preferably 0.002 mL / g or more, further preferably 0.005 mL / g or more, particularly preferably 0.010 mL / g or more, and most preferably 0.020 mL / g or more. If it deviates from the above range, Li ions cannot move smoothly in the electrode during charge and discharge, so there is a tendency for rapid charge and discharge characteristics and low temperature input and output characteristics to decrease.

[0111] As an apparatus for the above-mentioned mercury porosimetry, a mercury porosimeter (Autopore9520: manufactured by Micrometritics) can be used. The sample (carbon material) is weighed to a value of about 0.2 g, sealed in a powder container, and pre-treated by degassing for 10 minutes at room temperature and vacuum (below 50μmHg). Next, the pressure is reduced to 4psia (about 28kPa), and mercury is introduced into the above-mentioned container to increase the pressure stepwise from 4psia (about 28kPa) to 40000psia (about 280MPa), and then reduced to 25psia (about 170kPa). The number of steps during the pressure increase is set to more than 80 points, and after maintaining a balance time of 10 seconds in each step, the amount of mercury intrusion is measured. The micropore distribution is calculated from the mercury intrusion curve obtained in this way using the Washburn formula. Note that the calculation was performed assuming that the surface tension (γ) of mercury was 485 dyne / cm and the contact angle (ψ) was 140°. The average micropore diameter is defined as the micropore diameter when the cumulative micropore volume (cumulative pore volume) reaches 50%.

[0112] <A1-1-2. Thermal characteristics>

[0113] For the negative electrode material of one embodiment of the present invention, in the DTA curve obtained by differential thermal analysis (DTA) in air flow, at least one of the following conditions 1) and 2) is satisfied. In addition, in the above-mentioned DTA curve, it is preferred to satisfy condition 3) and further preferably satisfy condition 4).

[0114] 1) There is no exothermic peak in the temperature range of 550°C to 650°C.

[0115] 2) It has an exothermic peak in a temperature range of 550° C. to 650° C., and the area of ​​the exothermic peak exceeds 0 μV·s / mg and is 90 μV·s / mg or less.

[0116] 3) Having an exothermic starting temperature in a temperature range of 550°C to 750°C.

[0117] 4) It has an exothermic peak in a temperature range exceeding 650°C and not more than 1000°C.

[0118] Here, the exothermic peaks in the above-mentioned temperature ranges refer to exothermic peaks with peak tops in their temperature ranges. The peaks of the above-mentioned DTA curves derived from amorphous carbon usually exist above 550°C, and satisfying at least one of conditions 1 and 2) means that the carbon structure of the amorphous carbon material is sufficiently developed and exists in a more thermally stable state. By satisfying at least one of conditions 1) and 2), Li ions can move smoothly inside the amorphous carbon material, thus showing rapid charge and discharge characteristics and low-temperature input and output characteristics. In addition, at the same time, the self-discharge of the charged Li ions and the side reactions with the electrolyte can be suppressed, thus showing excellent high-temperature storage characteristics. As a result, the balance of rapid charge and discharge characteristics, low-temperature input and output characteristics and high-temperature storage characteristics becomes good. It should be noted that the "exothermic peak" in conditions 1) and 2) refers to the peak top of the exothermic peak, and the "area of ​​the exothermic peak" in condition 2 refers to the area of ​​the entire exothermic peak, and is not limited to a temperature range of 550°C or more and 650°C or less.

[0119] The area of ​​the exothermic peak of the negative electrode material of one embodiment of the present invention in the temperature range of above 550°C and below 650°C in the DTA curve obtained by differential thermal analysis (DTA) in an air flow is preferably 90 μV·s / mg or less, more preferably 70 μV·s / mg or less, further preferably 50 μV·s / mg or less, particularly preferably 30 μV·s / mg or less, most preferably 10 μV·s / mg or less, and ideally 0 μV·s / mg.

[0120] In addition, in the negative electrode material of one embodiment of the present invention, in addition to satisfying at least one of conditions 1) and 2), condition 3) is also satisfied, which means that the carbon structure of the amorphous carbon material is more developed and exists in a more thermally stable state. By satisfying condition 3) in addition to satisfying at least one of conditions 1) and 2), Li ions can move more smoothly inside the amorphous carbon material. In addition, at the same time, the self-discharge of the charged Li ions and the side reactions with the electrolyte can be further suppressed, so the rapid charge and discharge characteristics are excellent, and the balance of low temperature input and output characteristics and high temperature storage characteristics is better, so it is preferred.

[0121] In the negative electrode material of one embodiment of the present invention, condition 3) is a condition showing a preferred range in the starting temperature of the peak present in the DTA curve due to the developed carbon structure of the amorphous carbon material. In the negative electrode material of one embodiment of the present invention, the exothermic starting temperature of the DTA curve obtained by differential thermal analysis in an air flow is preferably 550°C or more, more preferably 570°C or more, further preferably 590°C or more, particularly preferably 600°C or more, and most preferably 620°C or more. On the other hand, it is preferably 750°C or less, more preferably 720°C or less, further preferably 700°C or less, particularly preferably 680°C or less, and most preferably 670°C or less.

[0122] Further satisfying condition 4) in the negative electrode material of one embodiment of the present invention means that the carbon structure of the amorphous carbon material is controlled not to be too developed and the insertion / detachment sites of Li ions are not too reduced. By further satisfying condition 4), there are appropriate insertion / detachment sites of Li ions, and the fast charge and discharge characteristics and low temperature input and output characteristics become good, so it is preferred. It should be noted that the exothermic peak in the temperature range of more than 650°C and less than 1000°C in the above-mentioned DTA curve has an exothermic peak derived from graphite in addition to the exothermic peak derived from the amorphous carbon material, and therefore, it appears as a superposition of these exothermic peaks.

[0123] The negative electrode material of one embodiment of the present invention preferably has an exothermic peak in a specific temperature range in a DTA curve obtained by differential thermal analysis (DTA) in an air flow. As the temperature range, it is preferably more than 650°C, more preferably more than 700°C, further preferably more than 750°C, and particularly preferably more than 800°C. On the other hand, it is preferably less than 1000°C, more preferably less than 900°C, further preferably less than 850°C, and particularly preferably less than 830°C.

[0124] It should be noted that the DTA curve obtained by differential thermal analysis in air flow can be measured using a thermogravimetric-differential thermal analyzer (TG-DTA) manufactured by Hitachi High-Technologies. Specifically, 15 mg of the sample can be filled in an alumina sample container, air can be circulated at a flow rate of 200 ml / min, and the temperature can be increased from room temperature to 1000°C at a heating rate of 5°C / min for measurement.

[0125] <A1-1-3. Raman characteristics (Raman R1 value, Raman half peak width Δν B (cm -1 ), Raman R2 value, Raman R3 value)>

[0126] (Raman R1 value)

[0127] The Raman R1 value in this specification is as shown in the following formula α, and is defined as the value obtained by measuring the 1580 cm-1 Raman spectrum of the negative electrode material by Raman spectroscopy. -1 Nearby peaks P A Strength I A With 1360cm -1 Nearby peaks P B Strength I B The intensity ratio (I B / I A ). It should be noted that “1580cm -1 "Nearby" refers to 1580~1620cm -1 Range, "1360cm -1 "Nearby" refers to 1350-1370cm -1 range.

[0128] Formula α:

[0129] [Raman R1 value] = [1360 cm in Raman spectroscopy analysis -1 Nearby peaks P B Strength I B ] / [1580cm -1 Nearby peaks P A Strength I A ]

[0130] The Raman half-peak width Δν in this specification B (cm -1 ) is defined as the 1360 cm-1 Raman spectrum of the negative electrode material obtained by Raman spectroscopy. -1 Nearby peaks P B It should be noted that “1360cm -1 "Nearby" refers to 1350-1370cm -1 range.

[0131] The Raman R2 value in this specification is defined as the following formula β, which is the value of the negative electrode material measured at 1580 cm in the Raman spectrum obtained by Raman spectroscopy. -1 Nearby peaks P A Strength I A , and 1580cm -1 Nearby peaks P A and 1360cm -1 Nearby peaks P B The intensity of the valley (minimum) between C The intensity ratio (I C / I A ). It should be noted that “1580cm -1 "Nearby" refers to 1580~1620cm-1 Range, "1360cm -1 "Nearby" refers to 1350-1370cm -1 range.

[0132] Formula β:

[0133] [Raman R2 value] = [1580cm in Raman spectroscopy analysis -1 Nearby peaks P A With 1360cm -1 Nearby peaks P B The intensity of the valley (minimum) between C ] / [1580cm -1 Nearby peaks P A Strength I A ]

[0134] The Raman R3 value in this specification is defined as the following formula γ, which is the value of the negative electrode material measured at 1360 cm in the Raman spectrum obtained by Raman spectroscopy. -1 Nearby peaks P B Strength I B , and 1580cm -1 Nearby peaks P A and 1360cm -1 Nearby peaks P B The intensity of the valley (minimum) between C The intensity ratio (I C / I B ). It should be noted that “1580cm -1 "Nearby" refers to 1580~1620cm -1 Range, "1360cm -1 "Nearby" refers to 1350-1370cm -1 range.

[0135] Formula γ:

[0136] [Raman R3 value] = [1580cm in Raman spectroscopy analysis -1 Nearby peaks P A With 1360cm -1 Nearby peaks P B The intensity of the valley (minimum) between C ] / [1360cm -1 Nearby peaks P B Strength I B ]

[0137] The Raman R1 value of the negative electrode material of one embodiment of the present invention is usually 0.15 or more, preferably 0.20 or more, more preferably 0.25 or more, further preferably 0.30 or more, particularly preferably 0.32 or more, and most preferably 0.35 or more. In addition, it is usually 1.00 or less, preferably 0.80 or less, more preferably 0.70 or less, further preferably 0.65 or less, and particularly preferably 0.50 or less.

[0138] The Raman half-peak width (Δν) of the negative electrode material of one embodiment of the present invention is B ) is usually 65cm -1 Above, preferably 70cm -1 More preferably 80cm -1 More preferably, 85 cm -1 More than, particularly preferably 90cm -1 More than, most preferably 100cm -1 Above, in addition, usually 400cm -1 Below, preferably 300cm -1 Less than, more preferably 250cm -1 Below, more preferably 200cm -1 Below, particularly preferably 170cm -1 Below, most preferably 145cm -1 the following.

[0139] The Raman R2 value of the negative electrode material of one embodiment of the present invention is preferably greater than 0.03, more preferably greater than 0.05, further preferably greater than 0.07, particularly preferably greater than 0.09, and most preferably greater than 0.11. In addition, it is usually less than 0.60, preferably less than 0.40, more preferably less than 0.30, further preferably less than 0.25, and particularly preferably less than 0.22.

[0140] The Raman R3 value of the negative electrode material of the second embodiment of the present invention is preferably greater than 0.10, more preferably greater than 0.15, further preferably greater than 0.20, particularly preferably greater than 0.25, and most preferably greater than 0.30. In addition, it is usually less than 1.00, preferably less than 0.80, more preferably less than 0.70, further preferably less than 0.60, and particularly preferably less than 0.45.

[0141] These Raman characteristics become indicators of the graphite crystallinity on the surface of the negative electrode material particles. The larger their values ​​are, the lower the graphite crystallinity on the surface of the negative electrode material particles is (the higher the amorphous property is). B / I A) is not only affected by the degree of graphitization (the integrity of the graphite structure), but also by the ratio of the edge and crystal boundary of the graphite crystal surface. The larger the Raman R1 value, the more there is a tendency for the degree of graphitization to decrease and the ratio of the edge and crystal boundary to increase. Therefore, not only when part of the particle surface has amorphous carbon, but also when the edge ratio increases due to the graphite being cut and crushed, the Raman R1 value increases. On the other hand, the Raman half-peak width (Δν B ) is less affected by the ratio of the edge and crystal boundary of the graphite crystal surface, and tends to reflect the influence of the degree of graphitization (the integrity of the graphite structure) more obviously. Therefore, since part of the particle surface has amorphous carbon, there is a Raman half-peak width (Δν B ) tends to increase, but when the edge ratio is increased due to crushing, etc., there is a tendency to change less. -1 Nearby peaks P A With 1360cm -1 Nearby peaks P B The intensity of the valley (minimum) between C It is believed that it originates from the defects in the graphite crystal structure and the SP3 property in the amorphous carbon structure, and there is a Raman R2 value (I C / I A ), Raman R3 value (I C / I B ) more reflects the influence of the degree of graphitization (the integrity of the local graphite structure). Therefore, the Raman R2 value (I C / I A ), Raman R3 value (I C / I B ) tends to become larger when a part of the particle surface has amorphous carbon, but tends to change less when the edge ratio is increased based on pulverization, etc.

[0142] The above-mentioned Raman characteristic parameter values ​​above the above-mentioned lower limit value indicate that the amorphousness of the surface of the negative electrode material is in a suitable range, and Li ions become easy to insert / detach, thereby there is a tendency to improve the low-temperature input-output characteristics. On the other hand, if the above-mentioned Raman characteristic parameter values ​​are below the above-mentioned upper limit value, the increase in the influence of the irreversible capacity of the carbon with high amorphousness and the increase in the side reaction with the electrolyte are suppressed, and the reduction in the initial charge and discharge efficiency of the lithium ion secondary battery and the increase in the amount of gas generated can be prevented, and there is a tendency to improve the battery capacity.

[0143] Raman spectra can be measured using a Raman spectrometer. Specifically, the sample is filled by allowing the particles to fall naturally and fill a measuring cell, and the cell is irradiated with argon ion laser while rotating the cell in a plane perpendicular to the laser for measurement.

[0144] Wavelength of argon ion laser: 514.5nm

[0145] Laser power on sample: 25mW

[0146] Resolution: 4cm -1

[0147] Measuring range: 1100cm -1 ~1730cm -1

[0148] Peak intensity measurement, peak half-width measurement: background processing, smoothing processing (convolution 5 points based on simple average)

[0149] <A1-1-4. BET specific surface area (SA)>

[0150] The specific surface area (SA) of the negative electrode material according to one embodiment of the present invention based on the BET method is preferably 0.5 m 2 / g or more, more preferably 1.0 m 2 / g or more, more preferably 1.5m 2 / g or more, particularly preferably 2.0m 2 / g or more, on the other hand, preferably 10.0m 2 / g or less, more preferably 6.5m 2 / g or less, more preferably 5.0m 2 / g or less, particularly preferably 4.0m 2 / g or less. If SA is above the above lower limit, the position where Li ions enter and exit can be ensured, and there is a tendency for the rapid charge and discharge characteristics and low temperature input and output characteristics of the lithium ion secondary battery to become good. On the other hand, if SA is below the above upper limit, the activity of the active material to the electrolyte becomes too excessive, and the side reaction with the electrolyte is suppressed to prevent the reduction of the initial charge and discharge efficiency of the battery and the increase of the amount of gas generated, and there is a tendency for the battery capacity to increase.

[0151] It should be noted that the BET specific surface area (SA) can be measured using Macsorb manufactured by Mountech. Specifically, the measurement can be performed as follows: After the sample is pre-dried under reduced pressure at 100°C for 3 hours under nitrogen flow, it is measured by the nitrogen adsorption BET 1-point method using a gas flow method using a nitrogen-helium mixed gas cooled to liquid nitrogen temperature and with the relative pressure of nitrogen gas to atmospheric pressure accurately adjusted to 0.3.

[0152] <A1-1-5. Tap density>

[0153] The tap density (g / cm 3 ) is preferably 0.60 g / cm 3 More preferably, 0.80 g / cm 3 More preferably, 1.00 g / cm 3 More than, particularly preferably 1.10 g / cm 3 On the other hand, it is preferably 1.40 g / cm 3 Below, more preferably 1.35g / cm 3 Below, more preferably 1.30 g / cm 3 Below, particularly preferably 1.25 g / cm 3 If the tap density is above the above lower limit, the process of streaking during the production of the plate becomes good, the filling property of the negative electrode material layer is improved, and therefore, the rolling property is good, and a high-density negative electrode sheet is easily formed, and high density becomes possible. When the electrode body is made, the curvature of the Li ion migration path becomes small, and the shape of the interparticle gap is neat, so the movement of the electrolyte becomes smooth, and the rapid charge and discharge characteristics are improved, which is preferred from the above viewpoint. In addition, if it is below the above upper limit, the surface and interior of the particle have appropriate space, the particle will not become too hard, the electrode compressibility is excellent, and the low-temperature input and output characteristics and rapid charge and discharge characteristics are excellent, which is preferred from the above viewpoint.

[0154] It should be noted that the tap density was measured using a powder density measuring instrument Tapdenser KYT-3000 (manufactured by Seishin Enterprise Co., Ltd.) Specifically, the sample was dropped into a 20cc tap container, and after the container was filled, 1000 taps were performed with a stroke length of 10 mm, and the density at this time was taken as the tap density.

[0155] <A1-1-6. Interplanar spacing (d002) and crystallite size (Lc)>

[0156] Regarding the crystallinity (degree of graphitization) of the negative electrode material of one embodiment of the present invention, it is preferred that the interplanar spacing (d002) of the (002) plane obtained by the X-ray wide-angle diffraction method based on the Xuezhen method is 0.340nm or less, and further preferably the crystallite size (Lc) in the c-axis direction is 90nm or more. The d002 value is more preferably 0.338nm or less, and further preferably 0.337nm or less. In addition, Lc is more preferably 95nm or more, and further preferably 100nm or more. If d002 and Lc are within the above range, the discharge capacity increases, so it is preferred from the viewpoint of being able to increase the capacity of the battery.

[0157] <A1-1-7. Roundness>

[0158] The circularity of the negative electrode material of one embodiment of the present invention obtained by flow particle image analysis is preferably 0.88 or more, more preferably 0.90 or more, more preferably 0.91 or more, particularly preferably 0.92 or more, and most preferably 0.93 or more. If it is such a negative electrode material with high circularity, the curvature of Li ion diffusion decreases and the electrolyte movement in the interparticle gap becomes smooth, thereby improving the rapid charge and discharge characteristics, so it is preferred. On the other hand, the theoretical upper limit of the circularity is 1, so it is usually less than 1, preferably less than 0.99, more preferably less than 0.98, and more preferably less than 0.97. From the viewpoint of ensuring the contact between the obtained negative electrode materials and improving the cycle characteristics, it is preferably below the above upper limit.

[0159] It should be noted that the roundness is obtained by measuring the particle size distribution based on the equivalent circle diameter using a flow particle image analyzer (FPIA-2000 manufactured by East Asia Medical Electronics Co., Ltd.) and calculating the average roundness. The roundness is defined by the following formula, and a roundness of 1 is a theoretical true sphere.

[0160] [Circularity] = [Circumference of an equivalent circle with the same area as the particle's projected shape] / [Actual circumference of the particle's projected shape]

[0161] In the measurement of the circularity, ion exchange water was used as a dispersion medium, and polyoxyethylene (20) monolaurate was used as a surfactant. The equivalent circle diameter refers to the diameter of a circle (equivalent circle) having the same projected area as the image of the particle photographed, and the circularity refers to the ratio obtained by taking the circumference of the equivalent circle as the numerator and the circumference of the projected image of the particle photographed as the denominator. The circularity of particles with an equivalent diameter of 10 to 40 μm was averaged and used as the circularity.

[0162] <A1-1-8. Volume-based average particle size (average particle size d50)>

[0163] The volume-based average particle size (also referred to as "average particle size d50") of the negative electrode material of one embodiment of the present invention is preferably 1 μm or more, more preferably 3 μm or more, further preferably 4 μm or more, particularly preferably 5 μm or more, and preferably 50 μm or less, more preferably 40 μm or less, further preferably 30 μm or less, particularly preferably 25 μm or less, and most preferably 20 μm or less. If the value of d50 is above the lower limit, there is a tendency to easily prevent the increase of irreversible capacity and the loss of initial battery capacity. On the other hand, if the value of d50 is below the upper limit, there is a tendency to prevent the occurrence of process defects such as streaks in slurry coating, and to improve rapid charge and discharge characteristics and low-temperature input and output characteristics.

[0164] The average particle size (d50) is defined as follows: 0.01 g of composite particles are suspended in 10 mL of a 0.2% by mass aqueous solution of polyoxyethylene sorbitan monolaurate (for example, Tween 20 (registered trademark)) as a surfactant, and the suspension is introduced as a measurement sample into a commercially available laser diffraction / scattering particle size distribution measuring apparatus (for example, LA-920 manufactured by HORIBA), and the measurement sample is irradiated with 28 kHz ultrasonic waves at an output power of 60 W for 1 minute, and then the volume-based median diameter is measured in the above-mentioned measuring apparatus, which is defined as the average particle size d50.

[0165] [A1-2. Manufacturing method]

[0166] The method for producing a negative electrode material for a non-aqueous secondary battery according to one embodiment of the present invention is to produce graphite having at least a portion of its surface having amorphous carbon, or to produce a graphite having specific Raman characteristics (Raman R1 value and Raman half-peak width (Δν B )) and a method for satisfying the aforementioned pore volume and the aforementioned thermal characteristics of the negative electrode material, there is no particular limitation, for example, it can be manufactured by pressurizing spheroidal graphite subjected to spheroidization treatment, and mixing and sintering an amorphous carbon precursor (raw material of amorphous carbon). The pressure treatment can be anisotropic and isotropic pressure treatments, but from the viewpoint of controlling the aforementioned pore volume and the aforementioned thermal characteristics within a specific range, isotropic pressure treatment is preferred. In addition, as a condition for pressure treatment, there is no particular limitation, and the aforementioned pore volume and the aforementioned thermal characteristics can be controlled within a specific range by treating at more than 50MPa and less than 300MPa. For the conditions of the pressure treatment, from the viewpoint of controlling the aforementioned pore volume and the aforementioned thermal characteristics within a specific range, it is preferably 100MPa or more, more preferably 120MPa or more, further preferably 140MPa or more, particularly preferably 160MPa or more, and most preferably 180MPa or more, and preferably 280MPa or less, more preferably 260MPa or less, further preferably 240MPa or less, particularly preferably 230MPa or less, and most preferably 220MPa or less. In the above-mentioned manufacturing method, specifically, graphite having amorphous carbon on at least a portion of the surface can be adjusted to a pore volume within a specific range by pressure treatment, and an amorphous carbon precursor with lower ash content, metal impurity content, quinoline insoluble components (Qi) and the like is used for the development of the carbon structure, and is fired at a moderate firing temperature and in an inactive atmosphere, so that the pore volume and thermal characteristics of the negative electrode material can be adjusted to a specific range, so it is preferred.

[0167] <A1-2-1. Graphite>

[0168] The negative electrode material of one embodiment of the present invention includes graphite. The graphite used to manufacture the negative electrode material of one embodiment of the present invention preferably shows the following types and properties. It should be noted that the physical properties of graphite are the same as those described above for the negative electrode material unless the measurement conditions and definitions thereof are particularly described.

[0169] For the type of graphite, as long as it can occlude and release lithium ions, its type is not particularly limited, and it can be any graphite in natural graphite and artificial graphite. As natural graphite, it can be any graphite of flaky graphite, blocky graphite, soil graphite, etc., but preferably graphite with few impurities, preferably used after known purification treatment as needed. As artificial graphite, it can be listed: artificial graphite obtained by sintering and graphitizing organic substances such as coal tar pitch, coal-based heavy oil, atmospheric residue, petroleum-based heavy oil, aromatic hydrocarbons, nitrogen-containing cyclic compounds, sulfur-containing cyclic compounds, polyphenylene, polyvinyl chloride, polyvinyl alcohol, polyacrylonitrile, polyvinyl butyral, natural polymer, polyphenylene sulfide, polyphenylene ether, furfuryl alcohol resin, phenol phenolic resin, imide resin at a temperature of usually more than 2500°C and usually less than 3200°C. At this time, silicon-containing compounds, boron-containing compounds, etc. can also be used as graphitization catalysts.

[0170] Regarding the crystallinity (degree of graphitization) of graphite, the interplanar spacing (d002) of the (002) plane based on the wide-angle X-ray diffraction method is usually 0.335 nm or more and less than 0.340 nm. In addition, the d002 value is preferably 0.338 nm or less, more preferably 0.337 nm or less, and further preferably 0.336 nm or less.

[0171] As for the shape of graphite, from the viewpoint of rapid charge and discharge characteristics, spheroidal graphite (spheroidized graphite) is particularly preferred. As a method for spheroidizing graphite particles, spheroidized graphite particles can be manufactured by implementing spheroidization treatment using known techniques. For example, a device that repeatedly imparts mechanical effects such as compression, friction, and shear force, which are mainly composed of impact force and also include interactions between particles, can be cited. Specifically, the following device is preferably used: a rotor having a plurality of blades is provided inside the housing, and the carbon material introduced inside is imparted with mechanical effects such as impact, compression, friction, and shear force by high-speed rotation of the rotor, thereby performing a surface treatment device. In addition, a device having a mechanism for repeatedly imparting mechanical effects by circulating graphite particles is preferably used. As specific devices, for example: Hybridization System (manufactured by Nara Machinery Co., Ltd.), Kryptron (manufactured by Earthtechnica), CF mill (manufactured by Ube Industries, Ltd.), mechanical melting system (manufactured by Hosokawa micron), Theta Composer (manufactured by Tokuju Industries, Ltd.), etc. Among these, the hybrid system manufactured by Nara Machinery Co., Ltd. is preferred. For example, when the aforementioned device is used for treatment, the circumferential speed of the rotating rotor is not particularly limited, and is preferably set to 30m / sec to 100m / sec, more preferably set to 40m / sec to 100m / sec, and further preferably set to 50m / sec to 100m / sec. In addition, although the treatment can be carried out by passing only the carbon material, it is preferably circulated or retained in the device for more than 30 seconds for treatment, and it is more preferably circulated or retained in the device for more than 1 minute for treatment. Alternatively, spherical graphite obtained by granulating a plurality of flake-shaped or scale-shaped graphite, graphite such as ground graphite powder, and a granulating agent according to the method described in Patent Document 4 may be used.

[0172] (A1-2-1-1. Roundness)

[0173] The roundness of the graphite used in the raw material of the negative electrode material of one embodiment of the present invention obtained by flow particle image analysis is preferably 0.88 or more, more preferably 0.90 or more, more preferably 0.91 or more, particularly preferably 0.92 or more, and most preferably 0.93 or more. If it is such a graphite with high roundness, the curvature of the Li ion diffusion of the negative electrode material manufactured using the graphite decreases and the electrolyte movement in the interparticle gap becomes smooth, so that the rapid charge and discharge characteristics can be improved, so it is preferred. On the other hand, the theoretical upper limit of the roundness is 1, so it is usually less than 1, preferably less than 0.99, more preferably less than 0.98, and more preferably less than 0.97. From the viewpoint of ensuring the contact between the obtained negative electrode materials and improving the cycle characteristics, it is preferably below the above upper limit.

[0174] The circularity is obtained by measuring the particle size distribution based on the equivalent circle diameter using a flow particle image analyzer (FPIA-2000 manufactured by Toa Medical Electronics Co., Ltd.) and calculating the average circularity. The circularity is defined by the following formula, and a circularity of 1 is a theoretical true sphere.

[0175] [Circularity] = [Circumference of an equivalent circle with the same area as the particle's projected shape] / [Actual circumference of the particle's projected shape]

[0176] In the measurement of the circularity, ion exchange water was used as a dispersion medium, and polyoxyethylene (20) monolaurate was used as a surfactant. The equivalent circle diameter refers to the diameter of a circle (equivalent circle) having the same projected area as the image of the particle photographed, and the circularity refers to the ratio obtained by taking the circumference of the equivalent circle as the numerator and the circumference of the projected image of the particle photographed as the denominator. The circularity of particles with an equivalent diameter of 10 to 40 μm was averaged and used as the circularity.

[0177] (A1-2-1-2. Tap density)

[0178] The tap density of graphite is preferably 0.60 g / cm 3 More preferably, 0.70 g / cm 3 More preferably, 0.80 g / cm 3 More than, particularly preferably 0.855 / cm 3 More than, most preferably 0.90g / cm 3 On the other hand, it is usually 1.40 g / cm 3 Below, preferably 1.30 g / cm 3 Below, more preferably 1.20 g / cm 3 the following.

[0179] (A1-2-1-3. Volume-based average particle size)

[0180] The volume-based average particle size (D50) of graphite is not particularly limited, but is usually 1 μm or more, preferably 3 μm or more, more preferably 5 μm or more, and is usually 50 μm or less, preferably 40 μm or less, more preferably 30 μm or less.

[0181] (A1-2-1-4. BET specific surface area)

[0182] The BET specific surface area of ​​graphite is not particularly limited, but is usually 1.0 m 2 / g or more, preferably 1.5m 2 / g or more, more preferably 2.0m 2 / g or more, more preferably 3.0m 2 / g or more, particularly preferably 4.5m 2 / g or more, and most preferably 5.0m 2 / g or more, usually 30.0m 2 / g or less, preferably 20.0m 2 / g or less, more preferably 10.0 m 2 / g or less.

[0183] (A1-2-1-5. Raman R1 value)

[0184] The Raman R1 value of graphite represented by the following formula α is not particularly limited, but is preferably 0.10 or more and 1.00 or less. In addition, the Raman R value is more preferably 0.15 or more, further preferably 0.20 or more, and particularly preferably 0.25 or more, and on the other hand, is more preferably 0.80 or less, and further preferably 0.60 or less.

[0185] Formula α:

[0186] Raman R1 value = (1360cm in Raman spectroscopy analysis -1 Nearby peaks P B Strength I B ) / (1580cm -1 Nearby peaks P A Strength I A )

[0187] <A1-2-2. Pressurization treatment of graphite>

[0188] The manufacture of the negative electrode material of one embodiment of the present invention preferably includes a step of pressurizing graphite. As a method for pressurizing graphite, there is no particular limitation as long as it is a method that can be pressurized, and examples thereof include: adding the raw graphite to a container such as a rubber type, hydrostatic isotropic pressurization with water as a pressurizing medium, and isotropic pressurization based on air pressure with a gas such as air as a pressurizing medium. In addition, the raw graphite can also be filled into a mold to be pressurized in a constant direction by unidirectional pressurization.

[0189] The pressure of the pressurized medium for the pressure treatment of graphite is preferably in the range of 5 to 400 MPa, more preferably in the range of 30 to 350 MPa, and further preferably in the range of 50 to 300 MPa. If it is above the above lower limit, the pore volume can be made into a smaller range. In addition, if the pressure is below the above upper limit, there is a tendency to easily suppress the increase in the specific surface area of ​​the obtained negative electrode material.

[0190] <A1-2-3. Amorphous carbon composite of graphite>

[0191] The negative electrode material of one embodiment of the present invention comprises graphite having amorphous carbon on at least a portion of the surface. The amorphous carbon composite treatment can be performed by mixing and sintering graphite with an amorphous carbon precursor (raw material of amorphous carbon). By performing amorphous carbon composite of graphite under suitable conditions, the aforementioned thermal characteristics can be satisfied, and the pore volume can also be easily controlled to the aforementioned range.

[0192] As amorphous carbon precursor, there is no particular limitation, and examples thereof include organic substances such as tar and pitch, aromatic hydrocarbons such as naphthalene, anthracene and derivatives thereof, phenolic resins, thermoplastic polymers such as polyvinyl alcohol, etc. These organic precursors can be used alone or in combination of two or more. Among these, tar, pitch, and aromatic hydrocarbons are preferred from the viewpoint that the carbon structure is easily developed.

[0193] The ash content contained in the amorphous carbon precursor is preferably 1% by weight or less, more preferably 0.5% by weight or less, and further preferably 0.1% by weight or less relative to the total weight of the amorphous carbon precursor. In addition, the lower limit of the ash content is usually 0.1 ppm by weight or more. If the ash content contained in the amorphous carbon precursor is within the above range, it is easy to satisfy the above-mentioned thermal characteristics.

[0194] In this specification, the amount of metal impurities contained in the amorphous carbon precursor is defined as the value obtained by dividing the total content of Fe, Al, Si, and Ca relative to the total weight of the amorphous carbon precursor by the residual carbon rate. It is preferably 1000 wtppm or less, more preferably 400 wtppm or less, further preferably 100 wtppm or less, particularly preferably 50 wtppm or less, and usually 0.1 wtppm or more relative to the total weight of the amorphous carbon precursor. If the amount of metal impurities contained in the amorphous carbon precursor is within the above range, it is easy to satisfy the above-mentioned thermal characteristics.

[0195] The quinoline insoluble component (Qi) contained in the amorphous carbon precursor is preferably 5% by weight or less, more preferably 2% by weight or less, further preferably 1% by weight or less, particularly preferably 0.5% by weight or less, and most preferably 0.1% by weight or less relative to the total weight of the amorphous carbon precursor. If the quinoline insoluble component (Qi) contained in the amorphous carbon precursor is within the above range, it is easy to satisfy the above-mentioned thermal characteristics.

[0196] After mixing graphite with an amorphous carbon precursor, calcination is performed. The temperature during calcination is preferably 950°C or more, more preferably 1000°C or more, further preferably 1050°C or more, particularly preferably 1100°C or more, and most preferably 1150°C or more. On the other hand, it is preferably 2000°C or less, more preferably 1800°C or less, further preferably 1600°C or less, and particularly preferably 1500°C or less. In addition, the calcination time is preferably 0.5 hours or more, more preferably 1 hour or more. On the other hand, it is preferably 1000 hours or less, more preferably 500 hours or less, and further preferably 100 hours or less. If the temperature and time during calcination are within the above range, it is easy to satisfy the aforementioned thermal characteristics.

[0197] The atmosphere during sintering is preferably an inert atmosphere. Specifically, there can be cited: a method of reducing the oxygen concentration by circulating an inert gas such as nitrogen or argon, a method of discharging oxygen outside the system by decompression treatment and restoring the pressure with nitrogen or argon, and a method of reducing the oxygen contained in the atmosphere in the furnace by filling sacrificial materials such as coke powder around the product. The oxygen concentration in the system can be controlled by the flow rate of the inert gas, the flow time, the degree of decompression treatment, the filling conditions of the sacrificial material, etc. The oxygen concentration (volume concentration) is preferably less than 3%, more preferably less than 1%, further preferably less than 1000ppm, particularly preferably less than 500ppm, and most preferably less than 100ppm. If the above range is exceeded, the development of the carbon structure of the amorphous carbon material is hindered, and there is a tendency to be difficult to meet the aforementioned thermal properties.

[0198] The mixing ratio of the amorphous carbon precursor when mixing the amorphous carbon precursor in graphite should be appropriately selected based on the composition of the target composite particles. For the amount of the amorphous carbon precursor relative to the graphite, the weight ratio ([weight of amorphous carbon] / [weight of graphite]]×100) as its carbon residue (amorphous carbon) is usually 0.01% or more, preferably 0.1% or more, more preferably 0.5% or more, further preferably 1% or more, particularly preferably 2% or more, and most preferably 3% or more. On the other hand, it is preferably 30% or less, more preferably 20% or less, further preferably 15% or less, and particularly preferably 10% or less. If the weight ratio is within the above range, it is high capacity and Li ions are easily inserted / detached, so low temperature input and output characteristics, rapid charge and discharge characteristics, and cycle characteristics are excellent, which is preferred from this point of view.

[0199] <A1-2-4. Other treatments>

[0200] In order to produce the negative electrode material according to one embodiment of the present invention, the composite particles obtained by the above-mentioned production method may be subjected to a separate pulverization treatment.

[0201] As the coarse pulverizer used for the pulverization treatment, jaw crusher, impact crusher, cone crusher, etc. can be listed, as the intermediate pulverizer, roll crusher, hammer mill, etc. can be listed, as the fine pulverizer, ball mill, vibration mill, pin mill, stirring mill, jet mill, etc. can be listed. Among these, ball mill and vibration mill are preferred from the viewpoint of short pulverization time and processing speed.

[0202] The pulverizing speed is suitably set according to the type and size of the device. For example, in the case of ball milling, it is usually 50 rpm or more, preferably 100 rpm or more, more preferably 150 rpm or more, and further preferably 200 rpm or more. In addition, it is usually 2500 rpm or less, preferably 2300 rpm or less, and more preferably 2000 rpm or less. If the speed is too fast, there is a tendency that the particle size control becomes difficult, and if the speed is too slow, there is a tendency that the processing speed slows down.

[0203] The pulverization time is usually more than 30 seconds, preferably more than 1 minute, more preferably more than 1 minute and 30 seconds, and further preferably more than 2 minutes, and is usually less than 3 hours, preferably less than 2.5 hours, and more preferably less than 2 hours. If the pulverization time is too short, there is a tendency that particle size control becomes difficult, and if the pulverization time is too long, there is a tendency that productivity decreases.

[0204] In the case of a vibration mill, the pulverizing speed is usually 50 rpm or more, preferably 100 rpm or more, more preferably 150 rpm or more, and further preferably 200 rpm or more, and is usually 2500 rpm or less, preferably 2300 rpm or less, and more preferably 2000 rpm or less. If the speed is too fast, there is a tendency that the control of the particle size becomes difficult, and if the speed is too slow, there is a tendency that the processing speed slows down.

[0205] The pulverization time is usually more than 30 seconds, preferably more than 1 minute, more preferably more than 1 minute and 30 seconds, and further preferably more than 2 minutes, and is usually less than 3 hours, preferably less than 2.5 hours, and more preferably less than 2 hours. If the pulverization time is too short, there is a tendency that particle size control becomes difficult, and if the pulverization time is too long, there is a tendency that productivity decreases.

[0206] In order to produce the negative electrode material of one embodiment of the present invention, the composite particles obtained by the above-mentioned production method can be subjected to particle size classification. As the classification conditions, the classification can be carried out using an apparatus with an opening of usually 53 μm or less, preferably 45 μm or less, and more preferably 38 μm or less.

[0207] There are no particular restrictions on the device used for the classification process. For example, in the case of dry screening, a rotary screen, a shaking screen, a rotating screen, a vibrating screen, etc. can be used; in the case of dry airflow classification, a gravity classifier, an inertial force classifier, a centrifugal force classifier (granulator, cyclone separator), etc. can be used; in the case of wet screening, a mechanical wet classifier, a hydraulic classifier, a sedimentation classifier, a centrifugal wet classifier, etc. can be used.

[0208] [A2. Negative electrode for non-aqueous secondary battery]

[0209] A negative electrode for a nonaqueous secondary battery according to an embodiment of the present invention (hereinafter sometimes referred to as “the negative electrode of the present invention”) comprises a current collector and an active material layer formed on the current collector, the active material layer containing the negative electrode material according to an embodiment of the present invention described above.

[0210] When the negative electrode is prepared using the negative electrode material, a binder resin is mixed with the negative electrode material in an aqueous or organic medium to prepare a slurry, and a thickener is added thereto as necessary, and then the slurry is applied to a current collector and dried.

[0211] As the binder resin, it is preferred to use a resin that is stable to the non-aqueous electrolyte and non-water-soluble. For example, rubber-like polymers such as styrene-butadiene rubber, isoprene rubber, and ethylene-propylene rubber; synthetic resins such as polyethylene, polypropylene, polyethylene terephthalate, polyimide, polyacrylic acid, and aromatic polyamide; thermoplastic elastomers such as styrene-butadiene-styrene block copolymers or their hydrogenated products, styrene-ethylene-butadiene, styrene copolymers, styrene-isoprene and styrene block copolymers and their hydrogenates; soft resin-like polymers such as syndiotactic-1,2-polybutadiene, ethylene-vinyl acetate copolymers, and copolymers of ethylene and α-olefins with 3 to 12 carbon atoms; fluorinated polymers such as tetrafluoroethylene-ethylene copolymers, polyvinylidene fluoride, polypentafluoropropylene, and polyhexafluoropropylene. As organic media, for example, N-methylpyrrolidone and dimethylformamide can be used.

[0212] Relative to 100 parts by weight of the negative electrode material, 0.1 parts by weight or more, preferably 0.2 parts by weight or more of the binding resin is generally used. By making the amount of the binding resin used 0.1 parts by weight or more relative to 100 parts by weight of the negative electrode material, the binding force between the negative electrode materials and the binding force between the negative electrode materials and the collector become sufficient, and the reduction in battery capacity and the deterioration of cycle characteristics caused by the stripping of the negative electrode material from the negative electrode can be prevented.

[0213] In addition, the amount of the binder resin used is preferably 10 parts by weight or less, more preferably 7 parts by weight or less relative to 100 parts by weight of the negative electrode material. By making the amount of the binder resin used less than 10 parts by weight relative to 100 parts by weight of the negative electrode material, it is possible to prevent the reduction of the negative electrode capacity and to prevent the entry and exit of alkali metal ions such as lithium ions relative to the negative electrode material from being hindered.

[0214] As the thickener added to the slurry, for example, water-soluble celluloses such as carboxymethyl cellulose, methyl cellulose, hydroxyethyl cellulose and hydroxypropyl cellulose, polyvinyl alcohol and polyethylene glycol, etc. are listed. Among these, carboxymethyl cellulose is preferred. The thickener is preferably used in an amount of usually 0.1 to 10 parts by weight, particularly 0.2 to 7 parts by weight, relative to 100 parts by weight of the negative electrode material.

[0215] As the negative electrode current collector, copper, copper alloy, stainless steel, nickel, titanium, carbon, etc., which are currently known to be applicable to this purpose, can be used. The current collector is usually in the form of a sheet, but a material having irregularities on the surface, a mesh, a punched metal, etc. are also preferably used.

[0216] After applying the slurry of the negative electrode material and the binder resin on the collector and drying it, it is preferably pressed to increase the density of the active material layer formed on the collector, thereby increasing the battery capacity per unit volume of the negative electrode active material layer. The density of the active material layer is preferably 1.2 to 1.8 g / cm3 The range is more preferably 1.3 to 1.6 g / cm 3 By making the density of the active material layer above the above lower limit, it is possible to prevent the battery capacity from decreasing due to an increase in the electrode thickness. In addition, by making the density of the active material layer below the above upper limit, the amount of electrolyte retained in the voids decreases due to a decrease in the voids between particles in the electrode, and it is possible to prevent the mobility of alkali metal ions such as lithium ions from decreasing, thereby preventing the rapid charge and discharge characteristics from decreasing.

[0217] [A3. Non-aqueous secondary battery]

[0218] The non-aqueous secondary battery of one embodiment of the present invention is a non-aqueous secondary battery having a positive electrode, a negative electrode, and an electrolyte, wherein the negative electrode used is the negative electrode of one embodiment of the present invention. In particular, the positive electrode and the negative electrode used in the non-aqueous secondary battery of one embodiment of the present invention are usually preferably positive electrodes and negative electrodes capable of absorbing and releasing Li ions, and the non-aqueous secondary battery of one embodiment of the present invention is preferably a lithium ion secondary battery.

[0219] The non-aqueous secondary battery of one embodiment of the present invention can be manufactured according to a conventional method except that the negative electrode of one embodiment of the present invention is used. In particular, the non-aqueous secondary battery of one embodiment of the present invention is preferably designed to have a value of [capacity of the negative electrode] / [capacity of the positive electrode] of 1.01 to 1.5, and more preferably 1.2 to 1.4.

[0220] [A3-1. Positive electrode]

[0221] As a positive electrode material of a non-aqueous secondary battery as an embodiment of the present invention, for example, lithium transition metal composite oxides such as lithium cobalt composite oxide represented by LiCoO2, lithium nickel composite oxide represented by LiNiO2, lithium manganese composite oxide represented by LiMnO2 and LiMn2O4, transition metal oxides such as manganese dioxide, and mixtures of these composite oxides can be used. Furthermore, TiS2, FeS2, Nb3S4, Mo3S4, CoS2, V2O5, CrO3, V3O3, FeO2, GeO2 and LiNi can be used. 0.33 Mn 0.33 Co 0.33 O2, LiFePO4, etc.

[0222] The positive electrode can be made by slurrying the material with the binding resin in the above-mentioned positive electrode material with an appropriate solvent and applying it on the collector and drying it. It should be noted that in the slurry, it is preferred to contain conductive materials such as acetylene black and Ketjen black. In addition, a thickener may also be contained as needed. It should be noted that as a binding material and a thickener, those known for their use can be used, for example, those exemplified as for the manufacture of the negative electrode can be used.

[0223] The amount of the conductive material is preferably 0.5 to 20 parts by weight, more preferably 1 to 15 parts by weight, relative to 100 parts by weight of the positive electrode material. In addition, the amount of the thickener is preferably 0.2 to 10 parts by weight, more preferably 0.5 to 7 parts by weight, relative to 100 parts by weight of the positive electrode material. In addition, with respect to the amount of the binder resin relative to 100 parts by weight of the positive electrode material, when the binder resin is slurried with water, it is preferably 0.2 to 10 parts by weight, more preferably 0.5 to 7 parts by weight. On the other hand, when the binder resin is slurried with an organic solvent such as N-methylpyrrolidone that dissolves the binder resin, it is preferably 0.5 to 20 parts by weight, more preferably 1 to 15 parts by weight.

[0224] Examples of the positive electrode current collector include aluminum, titanium, zirconium, hafnium, niobium, tantalum, and alloys thereof. Among these, aluminum, titanium, tantalum, and alloys thereof are preferred, and aluminum and alloys thereof are most preferred.

[0225] [A3-2. Electrolyte]

[0226] As the electrolyte solution, a solution prepared by dissolving various lithium salts in a conventionally known non-aqueous solvent can be used.

[0227] As nonaqueous solvent, for example, cyclic carbonates such as ethylene carbonate, fluoroethylene carbonate, propylene carbonate, butylene carbonate and vinylene carbonate, chain carbonates such as dimethyl carbonate, methyl ethyl carbonate and diethyl carbonate, cyclic esters such as gamma-butyrolactone, crown ethers, 2-methyltetrahydrofuran, tetrahydrofuran, 1,2-dimethyltetrahydrofuran and 1, the chain ethers such as cyclic ethers such as 3-dioxolane, 1,2-dimethoxyethane, etc. can be used. Usually more than two kinds in these solvents can be used in combination. Among these, preferably use cyclic carbonate and chain carbonate, or further mix therein after other solvents and use.

[0228] Compounds such as vinylene carbonate, vinylethylene carbonate, succinic anhydride, maleic anhydride, propane sultone and diethyl sulfone, difluorophosphates such as lithium difluorophosphate, etc. may be added to the electrolyte. Furthermore, overcharge inhibitors such as diphenyl ether and cyclohexylbenzene may be added.

[0229] Examples of electrolytes dissolved in non-aqueous solvents include LiClO4, LiPF6, LiBF4, LiCF3SO3, LiN(CF3SO2)2, LiN(CF3CF2SO2)2, LiN(CF3SO2)(C4F9SO2), and LiC(CF3SO2)3. The concentration of the electrolyte in the electrolyte solution is usually 0.5 mol / L to 2 mol / L, preferably 0.6 mol / L to 1.5 mol / L.

[0230] [A3-3. Partition]

[0231] In the non-aqueous secondary battery of one embodiment of the present invention, a separator is preferably used, and the separator is interposed between the positive electrode and the negative electrode. As such a separator, a porous sheet or nonwoven fabric of polyolefin such as polyethylene or polypropylene is preferably used.

[0232] <B. Second embodiment>

[0233] The present invention is described in detail below, but the present invention is not limited to the following description and can be implemented after any deformation within the scope of the present invention. It should be noted that in the present invention, when "to" is used and numerical values ​​or physical property values ​​are sandwiched before and after it, the meaning used is to include the values ​​before and after it.

[0234] [B1. Raw materials for negative electrode materials for non-aqueous secondary batteries]

[0235] A non-aqueous secondary battery negative electrode material raw material according to one embodiment of the present invention (hereinafter sometimes referred to as “the negative electrode material raw material of the present invention”) contains graphite, and when the mercury injection amount (mL / g) measured by mercury intrusion porosimetry is defined as A and the mercury removal amount (mL / g) is defined as B, the mercury removal amount / mercury injection amount (B / A)×100 is 45% or more.

[0236] The mercury removal amount / mercury injection amount (B / A) is an indicator of the complexity of the internal structure of the raw material particles of the negative electrode material. The complexity of the internal structure of the particles is related to the magnitude of the residual stress in the particles, and the large residual stress in the particles may be related to the ease of particle expansion accompanying the charge and discharge cycle of the negative electrode material using the raw material. Therefore, the mercury removal amount / mercury injection amount (B / A)×100 is usually 45% or more, more preferably 50% or more, further preferably 55% or more, particularly preferably 60% or more, and most preferably 63% or more. There is no particular upper limit on the ratio of the mercury removal amount / mercury injection amount (B / A)×100. The less complex the structure within the particle is (that is, the simpler the structure within the particle is), the more the sphericity of the particle tends to decrease. If the sphericity of the particle decreases, the lithium ion diffusivity in the negative electrode using the negative electrode material using the raw material decreases, and the adverse effect on load characteristics such as rapid charging performance may become significant. Therefore, the mercury removal amount / mercury injection amount (B / A)×100 is preferably 95% or less, more preferably 90% or less, further preferably 85% or less, and most preferably 80% or less.

[0237] As the amount of mercury inlet (mL / g) A, there is no particular limitation. A is small, which means that the amount of micropores in the particle is small. If the amount of micropores in the particle is small, it may be related to the reduction of load characteristics such as the input-output characteristics of the negative electrode material using the raw material. Therefore, the amount of mercury inlet (mL / g) A is preferably 0.001mL / g or more, more preferably 0.003mL / g or more, further preferably 0.005mL / g or more, particularly preferably 0.01mL / g or more, and most preferably 0.03mL / g or more. A is large, which means that the amount of micropores in the particle is large, and the amount of micropores in the particle is large, which may be related to the reduction of the bulk density of the negative electrode material using the raw material and the reduction of the slurry production efficiency and the electrode drying efficiency. Therefore, as the upper limit of the amount of mercury inlet (mL / g) A, it is preferably 1.0mL / g or less, more preferably 0.8mL / g or less, further preferably 0.6mL / g or less, particularly preferably 0.4mL / g or less, and most preferably 0.3mL / g or less.

[0238] The mercury removal amount (mL / g) B is not particularly limited. A small B reflects a small amount of micropores in the particle or a complex structure in the particle. The former may lead to a decrease in load characteristics such as input-output characteristics of the negative electrode material using the raw material, and the latter reflects a large residual stress in the particle. The large residual stress in the particle may lead to concerns about the generation of particle expansion accompanying the charge-discharge cycle of the negative electrode material using the raw material. Therefore, the mercury removal amount (mL / g) B is preferably 0.001 mL / g or more, more preferably 0.005 mL / g or more, further preferably 0.010 mL / g or more, particularly preferably 0.040 mL / g or more, and most preferably 0.065 mL / g or more. A large B means that the amount of mercury introduced (mL / g) A immediately before the measurement of B is large, and too large A may cause the above-mentioned concern. Therefore, the upper limit of the amount of mercury removed (mL / g) B is preferably 1.0 mL / g or less, more preferably 0.6 mL / g or less, further preferably 0.4 mL / g or less, particularly preferably 0.2 mL / g or less, and most preferably 0.1 mL / g or less.

[0239] When such a negative electrode material raw material is contained in the negative electrode material, it is preferable because it can suppress the expansion of the electrode plate after the charge and discharge cycle of the secondary battery (cycle expansion).

[0240] The non-aqueous secondary battery negative electrode material raw material and the non-aqueous secondary battery negative electrode material of this embodiment can provide a non-aqueous secondary battery with high capacity, excellent cycle expansion suppression, and excellent rapid charging performance. Although the reason why the present invention exerts such an effect is not yet clear, it is believed to be the following reason.

[0241] In the negative electrode material raw material of this embodiment, the amount of mercury withdrawal / mercury injection (B / A) becomes an index of the complexity of the structure within the particle. The smaller the B / A value, the more complex the structure within the particle. It can be considered that the complexity of the structure within the particle is related to the magnitude of the residual stress within the particle, and the large residual stress within the particle may be related to the ease of particle expansion accompanying the charge and discharge cycle of the negative electrode material using the negative electrode material raw material. By making the value of B / A×100 greater than 45%, it is considered that the complexity of the structure within the particle can be suppressed to a certain extent, thereby suppressing the residual stress within the particle, thereby suppressing the particle expansion accompanying the charge and discharge cycle of the negative electrode material using the negative electrode material raw material, and the suppression of the cycle expansion of the negative electrode is excellent.

[0242] In addition, by maintaining the value of B / A×100 at 63% or more, the negative electrode cycle expansion is excellently suppressed, and the fast charging performance can also be improved. This is believed to be because the diffusion of lithium ions in the negative electrode is promoted, the lithium ion concentration gradient in the negative electrode is slowed down, and the concentration overvoltage is suppressed under the use conditions such as fast charging where the material diffusion is rate-determined.

[0243] [B1-1. Physical properties]

[0244] The negative electrode material raw material according to one embodiment of the present invention satisfies (B / A)×100 described below.

[0245] <B1-1-1. Mercury intake and mercury removal>

[0246] For the negative electrode material of the present invention, when the mercury injection amount (mL / g) measured by mercury intrusion porosimetry is A and the mercury removal amount (mL / g) is B, mercury removal amount / mercury injection amount (B / A)×100 is 45% or more.

[0247] As an apparatus for the above-mentioned mercury porosimetry method, a mercury porosimeter (Autopore 9520: manufactured by Micrometritics) can be used. The sample (negative electrode material raw material) is weighed to a value of about 0.2 g, sealed in a powder container, and pre-treated by degassing for 10 minutes at room temperature and vacuum (below 50μmHg). Next, the pressure is reduced to 4psia (about 28kPa), and mercury is introduced into the above-mentioned container to increase the pressure stepwise from 4psia (about 28kPa) to 40000psia (about 280MPa), and then reduce the pressure to 25psia (about 170kPa). The number of steps during the pressure increase is set to 42 points or more, and the number of steps during the pressure reduction is set to 39 points or more. After maintaining a balance time of 10 seconds in each step, the amount of mercury intrusion is measured. The micropore distribution is calculated from the mercury intrusion curve obtained in this way using the Washburn formula. It should be noted that the calculation was performed with the surface tension (γ) of mercury being 485 dyne / cm and the contact angle (ψ) being 140°. The average micropore diameter is defined as the micropore diameter when the cumulative micropore volume reaches 50%. From the mercury intrusion behavior and mercury withdrawal behavior obtained in this way, the mercury intrusion amount (A) and mercury withdrawal amount (B) were calculated as follows.

[0248] Mercury injection amount (A) = cumulative pore volume of 0.01 μm or more and 0.6 μm or less on the injection side (mL / g)

[0249] Mercury removal amount (B) = mercury removal amount until 25 psia (about 170 kPa) on the exit side (mL / g)

[0250] In addition, the negative electrode material raw material according to one embodiment of the present invention preferably satisfies the following physical properties.

[0251] <B1-1-2. Roundness>

[0252] The roundness of the negative electrode material raw material obtained by flow particle image analysis of one embodiment of the present invention is preferably 0.88 or more, more preferably 0.90 or more, more preferably 0.91 or more, particularly preferably 0.92 or more, and most preferably 0.93 or more. If it is such a stone mill with high roundness, the curvature of the Li ion diffusion of the negative electrode material manufactured using it decreases and the electrolyte movement in the interparticle gap becomes smooth, thereby improving the rapid charge and discharge characteristics, so it is preferred. On the other hand, the theoretical upper limit of the roundness is 1, so it is usually less than 1, preferably less than 0.99, more preferably less than 0.98, and more preferably less than 0.97. From the viewpoint of ensuring the contact between the obtained negative electrode materials and improving the cycle characteristics, it is preferably below the above upper limit.

[0253] It should be noted that the roundness is obtained by measuring the particle size distribution based on the equivalent circle diameter using a flow particle image analyzer (FPIA-2000 manufactured by East Asia Medical Electronics Co., Ltd.) and calculating the average roundness. The roundness is defined by the following formula, and a roundness of 1 is a theoretical true sphere.

[0254] [Circularity] = [Circumference of an equivalent circle with the same area as the particle's projected shape] / [Actual circumference of the particle's projected shape]

[0255] In the measurement of the circularity, ion exchange water was used as a dispersion medium, and polyoxyethylene (20) monolaurate was used as a surfactant. The equivalent circle diameter refers to the diameter of a circle (equivalent circle) having the same projected area as the image of the particle photographed, and the circularity refers to the ratio obtained by taking the circumference of the equivalent circle as the numerator and the circumference of the projected image of the particle photographed as the denominator. The circularity of particles with an equivalent diameter of 10 to 40 μm was averaged and used as the circularity.

[0256] <B1-1-3. Tap density>

[0257] The tap density of the negative electrode material is preferably 0.60 g / cm 3 More preferably, 0.70 g / cm 3 More preferably, 0.80 g / cm 3 More than, particularly preferably 0.855 / cm 3 More than, most preferably 0.90g / cm 3 On the other hand, it is usually 1.40 g / cm 3 Below, preferably 1.30 g / cm 3 Below, more preferably 1.20 g / cm 3 the following.

[0258] It should be noted that the tap density was measured using a powder density measuring instrument Tapdenser KYT-3000 (manufactured by Seishin Enterprise Co., Ltd.) Specifically, the sample was dropped into a 20cc tap container, and after the container was filled, 1000 taps were performed with a stroke length of 10 mm, and the density at this time was taken as the tap density.

[0259] <B1-1-4. Volume-based average particle size>

[0260] The volume-based average particle size (D50) of the negative electrode material raw material is not particularly limited, and is usually 1 μm or more, preferably 3 μm or more, more preferably 5 μm or more, further preferably 8 μm or more, and particularly preferably 10 μm or more, and is usually 50 μm or less, preferably 40 μm or less, more preferably 30 μm or less, further preferably 20 μm or less, particularly preferably 16 μm or less, and most preferably 14 μm or less.

[0261] The average particle size (d50) is defined as follows: 0.01 g of composite particles are suspended in 10 mL of a 0.2% by mass aqueous solution of polyoxyethylene sorbitan monolaurate (for example, Tween 20 (registered trademark)) as a surfactant, and the suspension is introduced as a measurement sample into a commercially available laser diffraction / scattering particle size distribution measuring apparatus (for example, LA-920 manufactured by HORIBA), and the measurement sample is irradiated with 28 kHz ultrasonic waves at an output power of 60 W for 1 minute, and then the volume-based median diameter is measured in the above-mentioned measuring apparatus, which is defined as the average particle size d50.

[0262] <B1-1-5. BET specific surface area>

[0263] The BET specific surface area of ​​the negative electrode material is not particularly limited, but is usually 1.0 m 2 / g or more, preferably 1.5m 2 / g or more, more preferably 2.0m 2 / g or more, more preferably 3.0m 2 / g or more, particularly preferably 4.5m 2 / g or more, and most preferably 5.0m 2 / g or more, usually 30.0m 2 / g or less, preferably 25.0m 2 / g or less, more preferably 20.0m 2 / g or less, more preferably 16.0m 2 / g or less, more preferably 13.0m 2 / g or less, and more preferably 12.0m 2 / g or less.

[0264] It should be noted that the BET specific surface area (SA) can be measured using Macsorb manufactured by Mountech. Specifically, the measurement can be performed as follows: After the sample is pre-dried under reduced pressure at 100°C for 3 hours under nitrogen flow, it is measured by the nitrogen adsorption BET 1-point method using a gas flow method using a nitrogen-helium mixed gas cooled to liquid nitrogen temperature and with the relative pressure of nitrogen gas to atmospheric pressure accurately adjusted to 0.3.

[0265] [B2. Negative electrode materials for non-aqueous secondary batteries]

[0266] The negative electrode material for a non-aqueous secondary battery of the present invention includes the negative electrode material raw material for a non-aqueous secondary battery of the present invention described above.

[0267] [B2-1. Physical properties]

[0268] The negative electrode material according to one embodiment of the present invention preferably satisfies the following physical properties.

[0269] (Raman R1 value)

[0270] The Raman R1 value in this specification is as shown in the following formula α, and is defined as the value obtained by measuring the 1580 cm-1 Raman spectrum of the negative electrode material by Raman spectroscopy. -1 Nearby peaks P A Strength I A With 1360cm -1 Nearby peaks P B Strength I B The intensity ratio (I B / I A ). It should be noted that “1580cm -1 "Nearby" refers to 1580~1620cm -1 Range, "1360cm -1 "Nearby" refers to 1350-1370cm -1 range.

[0271] The Raman R1 value represented by the following formula α of the negative electrode material raw material is not particularly limited, but is preferably 0.10 or more and 1.00 or less. In addition, the Raman R1 value is more preferably 0.15 or more, further preferably 0.20 or more, and particularly preferably 0.25 or more, and on the other hand, is more preferably 0.80 or less, and further preferably 0.60 or less.

[0272] Formula α:

[0273] Raman R1 value = (1360cm in Raman spectroscopy analysis -1 Nearby peaks P B Strength I B) / (1580cm -1 Nearby peaks P A Strength I A )

[0274] <B2-1-1. Raman properties of negative electrode materials (Raman R1 value, Raman half peak width Δν B (cm -1 ), Raman R2 value, Raman R3 value)>

[0275] (Raman R1 value)

[0276] As described above, the Raman R1 value in this specification is defined as the value at 1580 cm-1 measured in the Raman spectrum obtained by Raman spectroscopy for the negative electrode material as shown in the following formula α. -1 Nearby peaks P A Strength I A With 1360cm -1 Nearby peaks P B Strength I B The intensity ratio (I B / I A ). It should be noted that “1580cm -1 "Nearby" refers to 1580~1620cm -1 Range, "1360cm -1 "Nearby" refers to 1350-1370cm -1 range.

[0277] Formula α:

[0278] [Raman R1 value] = [1360 cm in Raman spectroscopy analysis -1 Nearby peaks P B Strength I B ] / [1580cm -1 Nearby peaks P A Strength I A ]

[0279] The Raman half-peak width Δν in this specification B (cm -1 ) is defined as the 1360 cm-1 Raman spectrum of the negative electrode material obtained by Raman spectroscopy. -1 Nearby peaks P B It should be noted that “1360cm -1 "Nearby" refers to 1350-1370cm -1 range.

[0280] The Raman R2 value in this specification is defined as the following formula β, which is the value of the negative electrode material measured at 1580 cm in the Raman spectrum obtained by Raman spectroscopy. -1Nearby peaks P A Strength I A , and 1580cm -1 Nearby peaks P A and 1360cm -1 Nearby peaks P B The intensity of the valley (minimum) between C The intensity ratio (I C / I A ). It should be noted that “1580cm -1 "Nearby" refers to 1580~1620cm -1 Range, "1360cm -1 "Nearby" refers to 1350-1370cm -1 range.

[0281] Formula β:

[0282] [Raman R2 value] = [1580cm in Raman spectroscopy analysis -1 Nearby peaks P A With 1360cm -1 Nearby peaks P B The intensity of the valley (minimum) between C ] / [1580cm -1 Nearby peaks P A Strength I A ]

[0283] The Raman R3 value in this specification is defined as the following formula γ, which is the value of the negative electrode material measured at 1360 cm in the Raman spectrum obtained by Raman spectroscopy. -1 Nearby peaks P B Strength I B , and 1580cm -1 Nearby peaks P A and 1360cm -1 Nearby peaks P B The intensity of the valley (minimum) between C The intensity ratio (I C / I B ). It should be noted that “1580cm -1 "Nearby" refers to 1580~1620cm -1 Range, "1360cm -1 "Nearby" refers to 1350-1370cm -1 range.

[0284] Formula γ:

[0285] [Raman R3 value] = [1580cm in Raman spectroscopy analysis -1 Nearby peaks PA With 1360cm -1 Nearby peaks P B The intensity of the valley (minimum) between C ] / [1360cm -1 Nearby peaks P B Strength I B ]

[0286] The Raman R1 value of the negative electrode material of one embodiment of the present invention is usually 0.15 or more, preferably 0.20 or more, more preferably 0.25 or more, further preferably 0.30 or more, particularly preferably 0.32 or more, and most preferably 0.35 or more. In addition, it is usually 1.00 or less, preferably 0.80 or less, more preferably 0.70 or less, further preferably 0.65 or less, and particularly preferably 0.50 or less.

[0287] The Raman half-peak width (Δν) of the negative electrode material of one embodiment of the present invention is B ) is usually 65cm -1 Above, preferably 70cm -1 More preferably 80cm -1 More preferably, 85 cm -1 More than, particularly preferably 90cm -1 More than, most preferably 100cm -1 Above, in addition, usually 400cm -1 Below, preferably 300cm -1 Less than, more preferably 250cm -1 Below, more preferably 200cm -1 Below, particularly preferably 170cm -1 Below, most preferably 145cm -1 the following.

[0288] The Raman R2 value of the negative electrode material of one embodiment of the present invention is preferably greater than 0.03, more preferably greater than 0.05, further preferably greater than 0.07, particularly preferably greater than 0.09, and most preferably greater than 0.11. In addition, it is usually less than 0.60, preferably less than 0.40, more preferably less than 0.30, further preferably less than 0.25, and particularly preferably less than 0.22.

[0289] These Raman characteristics become indicators of the crystallinity of graphite on the surface of the negative electrode material. The larger their values ​​are, the lower the crystallinity of graphite on the surface of the negative electrode material is (the higher the amorphous property is). B / I A) is not only affected by the degree of graphitization (the integrity of the graphite structure), but also by the ratio of the edge and crystal boundary of the graphite crystal surface. The larger the Raman R1 value, the more there is a tendency for the degree of graphitization to decrease and the ratio of the edge and crystal boundary to increase. Therefore, not only when a part of the surface of the negative electrode material has amorphous carbon, but also when the edge ratio increases due to the graphite being cut and crushed, the Raman R1 value increases. On the other hand, the Raman half-peak width (Δν B ) is less affected by the ratio of the edge and crystal boundary of the graphite crystal surface, and tends to reflect the influence of the degree of graphitization (the integrity of the graphite structure) more obviously. Therefore, since part of the surface of the negative electrode material has amorphous carbon, there is a Raman half-peak width (Δν B ) tends to increase, but when the edge ratio is increased due to crushing, etc., there is a tendency to change less. -1 Nearby peaks P A With 1360cm -1 Nearby peaks P B The intensity of the valley (minimum) between C It is believed that it originates from the defects in the graphite crystal structure and the SP3 property in the amorphous carbon structure, and there is a Raman R2 value (I C / I A ), Raman R3 value (I C / I B ) more reflects the influence of the degree of graphitization (the integrity of the local graphite structure). Therefore, the Raman R2 value (I C / I A ), Raman R3 value (I C / I B ) tends to become larger when a part of the surface of the negative electrode material has amorphous carbon, but tends to change less when the edge ratio is increased based on pulverization, etc.

[0290] The above-mentioned Raman characteristic parameter values ​​above the above-mentioned lower limit value indicate that the amorphousness of the surface of the negative electrode material is in a suitable range, and Li ions become easy to insert / detach, thereby there is a tendency to improve the low-temperature input-output characteristics. On the other hand, if the above-mentioned Raman characteristic parameter values ​​are below the above-mentioned upper limit value, the increase in the influence of the irreversible capacity of the carbon with high amorphousness and the increase in the side reaction with the electrolyte are suppressed, and the reduction in the initial charge and discharge efficiency of the lithium ion secondary battery and the increase in the amount of gas generated can be prevented, and there is a tendency to improve the battery capacity.

[0291] Raman spectra can be measured using a Raman spectrometer. Specifically, the sample is filled by allowing the particles to fall naturally and fill a measuring cell, and the cell is irradiated with argon ion laser while rotating the cell in a plane perpendicular to the laser for measurement.

[0292] Wavelength of argon ion laser: 514.5nm

[0293] Laser power on sample: 25mW

[0294] Resolution: 4cm -1

[0295] Measuring range: 1100cm -1 ~1730cm -1

[0296] Peak intensity measurement, peak half-width measurement: background processing, smoothing processing (convolution 5 points based on simple average)

[0297] <B2-1-2. BET specific surface area (SA)>

[0298] The specific surface area (SA) of the negative electrode material according to one embodiment of the present invention based on the BET method is preferably 0.5 m 2 / g or more, more preferably 1.0 m 2 / g or more, more preferably 1.2m 2 / g or more, particularly preferably 1.5m 2 / g or more, and most preferably 1.8m 2 / g or more, on the other hand, preferably 10.0m 2 / g or less, more preferably 6.5m 2 / g or less, more preferably 5.0m 2 / g or less, particularly preferably 4.0m 2 / g or less, and most preferably 3.0m 2 / g or less. If SA is above the above lower limit, the position where Li ions enter and exit can be ensured, and there is a tendency for the rapid charge and discharge characteristics of the lithium ion secondary battery to become good. On the other hand, if SA is below the above upper limit, the activity of the active material for the electrolyte becomes too excessive, and the side reaction with the electrolyte is suppressed to prevent the reduction of the initial charge and discharge efficiency of the battery and the increase in the amount of gas generated, and there is a tendency for the battery capacity to increase. The BET specific surface area (SA) is measured by the same method as that described in the negative electrode material raw material.

[0299] <B2-1-3. Tap density>

[0300] The tap density (g / cm 3 ) is preferably 0.60 g / cm 3 More preferably, 0.80 g / cm 3 More preferably, 1.00 g / cm 3 More than, particularly preferably 1.10 g / cm 3 On the other hand, it is preferably 1.40 g / cm 3 Below, more preferably 1.35g / cm 3 Below, more preferably 1.30 g / cm 3 Below, particularly preferably 1.24 g / cm 3 Below. If the tap density is above the above lower limit, the process of streaking during the production of the pole plate becomes good, and the filling property of the negative electrode material layer is improved. Therefore, the rolling property is good, and it is easy to form a high-density negative electrode sheet, and high density becomes possible. When the electrode body is made, the curvature of the Li ion migration path becomes smaller, and the shape of the interparticle gap is neat, so the movement of the electrolyte becomes smooth, and the rapid charge and discharge characteristics are improved. From the above viewpoint, it is preferred. In addition, if it is below the above upper limit, the surface and interior of the particle have appropriate space, the particle will not become too hard, the electrode compressibility is excellent, and the rapid charge and discharge characteristics are excellent, which is preferred from the above viewpoint. The tap density is measured by the same method as the method described in the negative electrode material raw material.

[0301] <B2-1-4. Interplanar spacing (d002) and crystallite size (Lc)>

[0302] Regarding the crystallinity (degree of graphitization) of the negative electrode material of one embodiment of the present invention, it is preferred that the interplanar spacing (d002) of the (002) plane obtained by the X-ray wide-angle diffraction method based on the Xuezhen method is 0.340nm or less, and further preferably the crystallite size (Lc) in the c-axis direction is 90nm or more. The d002 value is more preferably 0.338nm or less, and further preferably 0.337nm or less. In addition, Lc is more preferably 95nm or more, and further preferably 100nm or more. If d002 and Lc are within the above range, the discharge capacity increases, so it is preferred from the viewpoint of being able to increase the capacity of the battery.

[0303] <B2-1-5. Roundness>

[0304] The circularity of the negative electrode material of one embodiment of the present invention obtained by flow particle image analysis is preferably 0.88 or more, more preferably 0.90 or more, further preferably 0.91 or more, particularly preferably 0.92 or more, and most preferably 0.93 or more. If it is such a negative electrode material with high circularity, the curvature of the Li ion diffusion decreases and the electrolyte movement in the interparticle gap becomes smooth, thereby improving the rapid charge and discharge characteristics, so it is preferred. On the other hand, the theoretical upper limit of the circularity is 1, so it is usually less than 1, preferably less than 0.99, more preferably less than 0.98, and more preferably less than 0.97. From the viewpoint of ensuring the contact between the obtained negative electrode materials and improving the cycle characteristics, it is preferably below the above upper limit. The circularity is obtained by the same method as the method described in the negative electrode material raw material.

[0305] <B2-1-6. Volume-based average particle size (average particle size d50)>

[0306] The volume-based average particle size (also referred to as "average particle size d50") of the negative electrode material of one embodiment of the present invention is preferably 1 μm or more, more preferably 3 μm or more, further preferably 4 μm or more, particularly preferably 5 μm or more, and most preferably 8 μm or more. In addition, it is preferably 50 μm or less, more preferably 40 μm or less, further preferably 30 μm or less, particularly preferably 20 μm or less, and most preferably 14 μm or less. If the value of d50 is above the lower limit, there is a tendency to easily prevent the increase of irreversible capacity and the loss of initial battery capacity. On the other hand, if the value of d50 is below the upper limit, there is a tendency to prevent the occurrence of process defects such as streaks in slurry coating, and to improve rapid charge and discharge characteristics and low-temperature input and output characteristics. The volume-based average particle size is obtained by the same method as the method described in the negative electrode material raw material.

[0307] [B3. Manufacturing method]

[0308] The method for producing a raw material of a negative electrode material for a non-aqueous secondary battery according to one embodiment of the present invention is not particularly limited as long as it is a method that can produce a raw material of a negative electrode material containing graphite and satisfying a ratio of mercury removal amount / mercury introduction amount (B / A)×100 of 45% or more when the amount of mercury introduced (mL / g) measured by mercury intrusion is A and the amount of mercury removal (mL / g) is B. For example, it can be produced by pressurizing spherical graphite subjected to a spheroidization treatment. The pressurization treatment may include anisotropic and isotropic pressurization treatments, but isotropic pressurization treatments are preferred from the viewpoint of controlling the amount of mercury removal / mercury introduction (B / A) within a specific range. In addition, the conditions for the pressurization treatment are not particularly limited, and the amount of mercury removal / mercury introduction (B / A) can be controlled within a specific range by treating at 50 MPa or more and 300 MPa or less. The conditions for the pressure treatment are preferably 100 MPa or more, more preferably 120 MPa or more, further preferably 140 MPa or more, particularly preferably 160 MPa or more, and most preferably 180 MPa or more, from the viewpoint of controlling the mercury removal amount / mercury injection amount (B / A) within a specific range, and preferably 280 MPa or less, more preferably 260 MPa or less, further preferably 240 MPa or less, particularly preferably 230 MPa or less, and most preferably 220 MPa or less. The above-mentioned production method is specifically, for example, as follows: natural graphite is pulverized, a granulating agent is mixed with the pulverized natural graphite to perform a spheroidization treatment, and the granulating agent is further removed by heat treatment to obtain spheroidized graphite, the obtained spheroidized graphite is pressure treated, and the obtained molded product is crushed and classified to produce a non-aqueous secondary battery negative electrode material raw material in which the mercury removal amount / mercury injection amount (B / A) is controlled within a specific range.

[0309] In addition, the manufacturing method of the negative electrode material for a non-aqueous secondary battery of one embodiment of the present invention is not particularly limited, and can be manufactured by mixing the negative electrode material raw material for a non-aqueous secondary battery of one embodiment of the present invention with an amorphous carbon precursor (amorphous carbon raw material) and calcining. Specifically, it is preferred to use an amorphous carbon precursor with low ash content, metal impurity content, quinoline insoluble components (Qi), etc., and calcine at a moderate calcination temperature and inactive atmosphere, so that the spherical stone mill can adjust the pore volume by pressure treatment, thereby achieving a specific range of mercury removal / mercury entry, and is suitable for the development of carbon structure.

[0310] <B3-1. Graphite>

[0311] The negative electrode material raw material of one embodiment of the present invention includes graphite. The graphite used to manufacture the negative electrode material raw material of one embodiment of the present invention preferably shows the following types and properties. It should be noted that the physical properties of graphite are the same as those described above for the negative electrode material raw material unless the measurement conditions and definitions thereof are particularly described.

[0312] For the type of graphite, as long as it can occlude and release lithium ions, its type is not particularly limited, and it can be any graphite in natural graphite and artificial graphite. As natural graphite, it can be any graphite of flaky graphite, blocky graphite, soil graphite, etc., but preferably graphite with few impurities, preferably used after known purification treatment as needed. As artificial graphite, it can be listed: artificial graphite obtained by sintering and graphitizing organic substances such as coal tar pitch, coal-based heavy oil, atmospheric residue, petroleum-based heavy oil, aromatic hydrocarbons, nitrogen-containing cyclic compounds, sulfur-containing cyclic compounds, polyphenylene, polyvinyl chloride, polyvinyl alcohol, polyacrylonitrile, polyvinyl butyral, natural polymer, polyphenylene sulfide, polyphenylene ether, furfuryl alcohol resin, phenol phenolic resin, imide resin at a temperature of usually more than 2500°C and usually less than 3200°C. At this time, silicon-containing compounds, boron-containing compounds, etc. can also be used as graphitization catalysts.

[0313] Regarding the crystallinity (degree of graphitization) of graphite, the interplanar spacing (d002) of the (002) plane based on the wide-angle X-ray diffraction method is usually 0.335 nm or more and less than 0.340 nm. In addition, the d002 value is preferably 0.338 nm or less, more preferably 0.337 nm or less, and further preferably 0.336 nm or less.

[0314] As for the shape of graphite, from the viewpoint of rapid charge and discharge characteristics, spheroidal graphite (spheroidized graphite) is particularly preferred. As a method for spheroidizing graphite particles, spheroidized graphite particles can be manufactured by implementing a spheroidization process using a known technique. As a spheroidization process, for example, a device can be cited that repeatedly imparts mechanical effects such as compression, friction, and shear force to particles, which are mainly composed of impact force and also include interactions between particles. As a device for spheroidization, specifically, the following device is preferably used: a rotor having a plurality of blades disposed inside a housing, and a device for surface treatment by which the carbon material introduced inside is imparted with mechanical effects such as impact, compression, friction, and shear force by high-speed rotation of the rotor. In addition, a device having a mechanism for repeatedly imparting mechanical effects by circulating graphite particles is preferably used. As specific devices, for example: Hybridization System (manufactured by Nara Machinery Co., Ltd.), Kryptron (manufactured by Earthtechnica), CF mill (manufactured by Ube Industries, Ltd.), mechanical melting system (manufactured by Hosokawa micron), Theta Composer (manufactured by Tokuju Industries, Ltd.), etc. Among these, the hybrid system manufactured by Nara Machinery Co., Ltd. is preferred. For example, when the aforementioned device is used for treatment, the circumferential speed of the rotating rotor is not particularly limited, and is preferably set to 30m / sec to 100m / sec, more preferably set to 40m / sec to 100m / sec, and further preferably set to 50m / sec to 100m / sec. In addition, although the treatment can be carried out by passing only the carbon material, it is preferably circulated or retained in the device for more than 30 seconds for treatment, and it is more preferably circulated or retained in the device for more than 1 minute for treatment. Alternatively, spherical graphite obtained by granulating a plurality of flake-shaped or scale-shaped graphite, graphite such as ground graphite powder, and a granulating agent according to the method described in Patent Document 4 may be used.

[0315] (Roundness)

[0316] The roundness of the graphite used as the negative electrode material raw material of one embodiment of the present invention obtained by flow particle image analysis is preferably 0.88 or more, more preferably 0.90 or more, more preferably 0.91 or more, particularly preferably 0.92 or more, and most preferably 0.93 or more. If it is such a graphite with high roundness, the curvature of the Li ion diffusion of the negative electrode material manufactured using the graphite decreases and the electrolyte movement in the interparticle gap becomes smooth, so that the rapid charge and discharge characteristics can be improved, so it is preferred. On the other hand, the theoretical upper limit of the roundness is 1, so it is usually less than 1, preferably less than 0.99, more preferably less than 0.98, and more preferably less than 0.97. From the viewpoint of ensuring the contact between the obtained negative electrode materials and improving the cycle characteristics, it is preferably below the above upper limit.

[0317] (Tap density)

[0318] The tap density of graphite is preferably 0.60 g / cm 3 More preferably, 0.70 g / cm 3 More preferably, 0.80 g / cm 3 More than, particularly preferably 0.855 / cm 3 More than, most preferably 0.90g / cm 3 On the other hand, it is usually 1.40 g / cm 3 Below, preferably 1.30 g / cm 3 Below, more preferably 1.20 g / cm 3 the following.

[0319] (Volume-based average particle size)

[0320] The volume-based average particle size (D50) of graphite is not particularly limited, but is usually 1 μm or more, preferably 3 μm or more, more preferably 5 μm or more, and is usually 50 μm or less, preferably 40 μm or less, more preferably 30 μm or less.

[0321] (BET specific surface area)

[0322] The BET specific surface area of ​​graphite is not particularly limited, but is usually 1.0 m 2 / g or more, preferably 1.5m 2 / g or more, more preferably 2.0m 2 / g or more, more preferably 3.0m 2 / g or more, particularly preferably 4.5m 2 / g or more, and most preferably 5.0m 2 / g or more, usually 30.0m 2 / g or less, preferably 25.0m 2 / g or less, more preferably 20.0m 2 / g or less.

[0323] (Raman R1 value)

[0324] The Raman R1 value of graphite represented by the following formula α is not particularly limited, but is preferably 0.10 or more and 1.00 or less. In addition, the Raman R value is more preferably 0.15 or more, further preferably 0.20 or more, and particularly preferably 0.25 or more, and on the other hand, is more preferably 0.80 or less, and further preferably 0.60 or less.

[0325] Formula α:

[0326] Raman R1 value = (1360cm in Raman spectroscopy analysis -1 Nearby peaks P B Strength I B ) / (1580cm -1 Nearby peaks P A Strength I A )

[0327] <B3-2. Pressurization treatment of graphite>

[0328] The manufacture of the negative electrode material raw material of one embodiment of the present invention preferably includes a step of pressurizing graphite. As a method for pressurizing graphite, there is no particular limitation as long as it is a method that can be pressurized, and examples thereof include: adding the raw graphite to a container such as a rubber type, hydrostatic isotropic pressurization with water as a pressurizing medium, and isotropic pressurization based on air pressure with a gas such as air as a pressurizing medium. In addition, the raw graphite can also be filled into a mold to be pressurized in a constant direction by unidirectional pressurization.

[0329] The pressure of the pressurized medium for the pressure treatment of graphite is preferably in the range of 5 to 400 MPa, more preferably in the range of 30 to 350 MPa, and further preferably in the range of 50 to 300 MPa. If it is above the above lower limit, the pore volume can be made into a smaller range. In addition, if the pressure is below the above upper limit, there is a tendency to easily suppress the increase in the specific surface area of ​​the obtained negative electrode material.

[0330] <B3-3. Amorphous carbon composite of negative electrode material>

[0331] The negative electrode material of one embodiment of the present invention preferably includes graphite having amorphous carbon on at least a portion of the surface. The amorphous carbon composite treatment is performed by mixing the negative electrode material raw material containing the above-mentioned graphite with an amorphous carbon precursor (amorphous carbon raw material) and sintering. By performing amorphous carbon composite of the negative electrode material raw material containing graphite under appropriate conditions, it is easy to control the cumulative pore volume within the aforementioned range.

[0332] As amorphous carbon precursor, there is no particular limitation, and examples thereof include organic substances such as tar and pitch, aromatic hydrocarbons such as naphthalene, anthracene and derivatives thereof, phenolic resins, thermoplastic polymers such as polyvinyl alcohol, etc. These organic precursors can be used alone or in combination of two or more. Among these, tar, pitch, and aromatic hydrocarbons are preferred from the viewpoint that the carbon structure is easily developed.

[0333] The ash content contained in the amorphous carbon precursor is preferably 1% by weight or less, more preferably 0.5% by weight or less, and further preferably 0.1% by weight or less relative to the total weight of the amorphous carbon precursor. In addition, the lower limit of the ash content is usually 0.1 ppm by weight or more. If the ash content contained in the amorphous carbon precursor is within the above range, the thermal properties become good.

[0334] The amount of metal impurities contained in the amorphous carbon precursor in the present invention is defined as the value obtained by dividing the total content of Fe, Al, Si, and Ca relative to the total weight of the amorphous carbon precursor by the residual carbon rate. It is preferably 1000 wtppm or less, more preferably 400 wtppm or less, further preferably 100 wtppm or less, particularly preferably 50 wtppm or less, and usually 0.1 wtppm or more relative to the total weight of the amorphous carbon precursor. If the amount of metal impurities contained in the amorphous carbon precursor is within the above range, the thermal properties become good.

[0335] The quinoline insoluble component (Qi) contained in the amorphous carbon precursor is preferably 5 wt% or less, more preferably 2 wt% or less, further preferably 1 wt% or less, particularly preferably 0.5 wt% or less, and most preferably 0.1 wt% or less relative to the total weight of the amorphous carbon precursor. If the quinoline insoluble component (Qi) contained in the amorphous carbon precursor is within the above range, the thermal properties become good.

[0336] After mixing graphite with an amorphous carbon precursor, calcination is performed. The temperature during calcination is preferably above 950°C, more preferably above 1000°C, further preferably above 1050°C, particularly preferably above 1100°C, and most preferably above 1150°C. On the other hand, it is preferably below 2000°C, more preferably below 1800°C, further preferably below 1600°C, and particularly preferably below 1500°C. In addition, the calcination time is preferably above 0.5 hours, more preferably above 1 hour, on the other hand, it is preferably below 1000 hours, more preferably below 500 hours, and further preferably below 100 hours. If the temperature and time during calcination are within the above range, the thermal properties become good.

[0337] The atmosphere during sintering is preferably an inert atmosphere. Specifically, there can be cited: a method of reducing the oxygen concentration by circulating an inert gas such as nitrogen or argon, a method of discharging oxygen outside the system by decompression treatment and restoring the pressure with nitrogen or argon, and a method of reducing the oxygen contained in the atmosphere in the furnace by filling sacrificial materials such as coke powder around the product. The oxygen concentration in the system can be controlled by the flow rate of the inert gas, the flow time, the degree of decompression treatment, the filling conditions of the sacrificial material, etc. The oxygen concentration (volume concentration) is preferably less than 3%, more preferably less than 1%, further preferably less than 1000ppm, particularly preferably less than 500ppm, and most preferably less than 100ppm. If the above range is exceeded, the development of the carbon structure of the amorphous carbon material is hindered, and there is a tendency that it is difficult to obtain ideal thermal properties.

[0338] The mixing ratio of the amorphous carbon precursor when mixing the amorphous carbon precursor in graphite should be appropriately selected based on the composition of the target composite particles. For the amount of the amorphous carbon precursor relative to the graphite, the weight ratio ([weight of amorphous carbon] / [weight of graphite]]×100) as its carbon residue (amorphous carbon) is usually 0.01% or more, preferably 0.1% or more, more preferably 0.5% or more, further preferably 1% or more, particularly preferably 2% or more, and most preferably 3% or more. On the other hand, it is preferably 30% or less, more preferably 20% or less, further preferably 15% or less, and particularly preferably 10% or less. If the weight ratio is within the above range, it is high capacity and Li ions are easily inserted / detached, so low temperature input and output characteristics, rapid charge and discharge characteristics, and cycle characteristics are excellent, which is preferred from this point of view.

[0339] <B3-4. Other treatments>

[0340] In order to produce the negative electrode material according to one embodiment of the present invention, the composite particles obtained by the above-mentioned production method may be subjected to a separate pulverization treatment.

[0341] As the coarse pulverizer used for the pulverization treatment, jaw crusher, impact crusher, cone crusher, etc. can be listed, as the intermediate pulverizer, roll crusher, hammer mill, etc. can be listed, as the fine pulverizer, ball mill, vibration mill, pin mill, stirring mill, jet mill, etc. can be listed. Among these, ball mill and vibration mill are preferred from the viewpoint of short pulverization time and processing speed.

[0342] The pulverizing speed is suitably set according to the type and size of the device. For example, in the case of ball milling, it is usually 50 rpm or more, preferably 100 rpm or more, more preferably 150 rpm or more, and further preferably 200 rpm or more. In addition, it is usually 2500 rpm or less, preferably 2300 rpm or less, and more preferably 2000 rpm or less. If the speed is too fast, there is a tendency that the particle size control becomes difficult, and if the speed is too slow, there is a tendency that the processing speed slows down.

[0343] The pulverization time is usually more than 30 seconds, preferably more than 1 minute, more preferably more than 1 minute and 30 seconds, and further preferably more than 2 minutes, and is usually less than 3 hours, preferably less than 2.5 hours, and more preferably less than 2 hours. If the pulverization time is too short, there is a tendency that particle size control becomes difficult, and if the pulverization time is too long, there is a tendency that productivity decreases.

[0344] In the case of a vibration mill, the pulverizing speed is usually 50 rpm or more, preferably 100 rpm or more, more preferably 150 rpm or more, and further preferably 200 rpm or more, and is usually 2500 rpm or less, preferably 2300 rpm or less, and more preferably 2000 rpm or less. If the speed is too fast, there is a tendency that the control of the particle size becomes difficult, and if the speed is too slow, there is a tendency that the processing speed slows down.

[0345] The pulverization time is usually more than 30 seconds, preferably more than 1 minute, more preferably more than 1 minute and 30 seconds, and further preferably more than 2 minutes, and is usually less than 3 hours, preferably less than 2.5 hours, and more preferably less than 2 hours. If the pulverization time is too short, there is a tendency that particle size control becomes difficult, and if the pulverization time is too long, there is a tendency that productivity decreases.

[0346] In order to produce the negative electrode material of one embodiment of the present invention, the composite particles obtained by the above-mentioned production method can be subjected to particle size classification. As the classification conditions, the classification can be carried out using an apparatus with an opening of usually 53 μm or less, preferably 45 μm or less, and more preferably 38 μm or less.

[0347] There are no particular restrictions on the device used for the classification process. For example, in the case of dry screening, a rotary screen, a shaking screen, a rotating screen, a vibrating screen, etc. can be used; in the case of dry airflow classification, a gravity classifier, an inertial force classifier, a centrifugal force classifier (granulator, cyclone separator), etc. can be used; in the case of wet screening, a mechanical wet classifier, a hydraulic classifier, a sedimentation classifier, a centrifugal wet classifier, etc. can be used.

[0348] [B4. Negative electrode for non-aqueous secondary battery]

[0349] A negative electrode for a non-aqueous secondary battery according to an embodiment of the present invention (hereinafter sometimes referred to as "the negative electrode of the present invention") comprises: a current collector and an active material layer formed on the current collector, wherein the active material layer contains the negative electrode material according to an embodiment of the present invention described above. The negative electrode for a non-aqueous secondary battery according to this embodiment may be the same as the first embodiment except for the active material layer.

[0350] When the negative electrode is prepared using the negative electrode material, a binder resin is mixed with the negative electrode material in an aqueous or organic medium to prepare a slurry, and a thickener is added thereto as necessary, and then the slurry is applied to a current collector and dried.

[0351] As the binder resin, it is preferred to use a resin that is stable to the non-aqueous electrolyte and non-water-soluble. For example, rubber-like polymers such as styrene-butadiene rubber, isoprene rubber, and ethylene-propylene rubber; synthetic resins such as polyethylene, polypropylene, polyethylene terephthalate, polyimide, polyacrylic acid, and aromatic polyamide; thermoplastic elastomers such as styrene-butadiene-styrene block copolymers or their hydrogenated products, styrene-ethylene-butadiene, styrene copolymers, styrene-isoprene and styrene block copolymers and their hydrogenates; soft resin-like polymers such as syndiotactic-1,2-polybutadiene, ethylene-vinyl acetate copolymers, and copolymers of ethylene and α-olefins with 3 to 12 carbon atoms; fluorinated polymers such as tetrafluoroethylene-ethylene copolymers, polyvinylidene fluoride, polypentafluoropropylene, and polyhexafluoropropylene. As organic media, for example, N-methylpyrrolidone and dimethylformamide can be used.

[0352] Relative to 100 parts by weight of the negative electrode material, 0.1 parts by weight or more, preferably 0.2 parts by weight or more of the binding resin is generally used. By making the amount of the binding resin used 0.1 parts by weight or more relative to 100 parts by weight of the negative electrode material, the binding force between the negative electrode materials and the binding force between the negative electrode materials and the collector become sufficient, and the reduction in battery capacity and the deterioration of cycle characteristics caused by the stripping of the negative electrode material from the negative electrode can be prevented.

[0353] In addition, the amount of the binder resin used is preferably 10 parts by weight or less, more preferably 7 parts by weight or less relative to 100 parts by weight of the negative electrode material. By making the amount of the binder resin used less than 10 parts by weight relative to 100 parts by weight of the negative electrode material, it is possible to prevent the reduction of the negative electrode capacity and to prevent the entry and exit of alkali metal ions such as lithium ions relative to the negative electrode material from being hindered.

[0354] As the thickener added to the slurry, for example, water-soluble celluloses such as carboxymethyl cellulose, methyl cellulose, hydroxyethyl cellulose and hydroxypropyl cellulose, polyvinyl alcohol and polyethylene glycol, etc. are listed. Among these, carboxymethyl cellulose is preferred. The thickener is preferably used in an amount of usually 0.1 to 10 parts by weight, particularly 0.2 to 7 parts by weight, relative to 100 parts by weight of the negative electrode material.

[0355] As the negative electrode current collector, copper, copper alloy, stainless steel, nickel, titanium, carbon, etc., which are currently known to be applicable to this purpose, can be used. The current collector is usually in the form of a sheet, but a material having irregularities on the surface, a mesh, a punched metal, etc. are also preferably used.

[0356] After applying the slurry of the negative electrode material and the binder resin on the collector and drying it, it is preferably pressed to increase the density of the active material layer formed on the collector, thereby increasing the battery capacity per unit volume of the negative electrode active material layer. The density of the active material layer is preferably 1.2 to 1.8 g / cm 3 The range is more preferably 1.3 to 1.6 g / cm 3 By making the density of the active material layer above the above lower limit, it is possible to prevent the battery capacity from decreasing due to an increase in the electrode thickness. In addition, by making the density of the active material layer below the above upper limit, the amount of electrolyte retained in the voids decreases due to a decrease in the voids between particles in the electrode, and it is possible to prevent the mobility of alkali metal ions such as lithium ions from decreasing, thereby preventing the rapid charge and discharge characteristics from decreasing.

[0357] [B5. Non-aqueous secondary battery]

[0358] The non-aqueous secondary battery of one embodiment of the present invention is a non-aqueous secondary battery having a positive electrode, a negative electrode, and an electrolyte, wherein the negative electrode used is the negative electrode of one embodiment of the present invention. In particular, the positive electrode and the negative electrode used in the non-aqueous secondary battery of one embodiment of the present invention are usually preferably positive electrodes and negative electrodes capable of absorbing and releasing Li ions, and the non-aqueous secondary battery of one embodiment of the present invention is preferably a lithium ion secondary battery.

[0359] The non-aqueous secondary battery of one embodiment of the present invention can be manufactured according to a conventional method except that the negative electrode of one embodiment of the present invention is used. In particular, the non-aqueous secondary battery of one embodiment of the present invention is preferably designed to have a value of [capacity of the negative electrode] / [capacity of the positive electrode] of 1.01 to 1.5, and more preferably 1.2 to 1.4.

[0360] [B5-1. Positive electrode]

[0361] As a positive electrode material of a non-aqueous secondary battery as an embodiment of the present invention, for example, lithium transition metal composite oxides such as lithium cobalt composite oxide represented by LiCoO2, lithium nickel composite oxide represented by LiNiO2, lithium manganese composite oxide represented by LiMnO2 and LiMn2O4, transition metal oxides such as manganese dioxide, and mixtures of these composite oxides can be used. Furthermore, TiS2, FeS2, Nb3S4, Mo3S4, CoS2, V2O5, CrO3, V3O3, FeO2, GeO2 and LiNi can be used. 0.33 Mn 0.33 Co 0.33 O2, LiFePO4, etc.

[0362] The positive electrode can be made by slurrying the material with the binding resin in the above-mentioned positive electrode material with an appropriate solvent and coating it on the collector and drying it. It should be noted that in the slurry, it is preferred to contain conductive materials such as acetylene black and Ketjen black. In addition, a thickener may also be contained as needed. It should be noted that as a binding material and a thickener, those known for their use can be used, for example, those exemplified as for the manufacture of the negative electrode can be used.

[0363] The amount of the conductive material is preferably 0.5 to 20 parts by weight, more preferably 1 to 15 parts by weight, relative to 100 parts by weight of the positive electrode material. In addition, the amount of the thickener is preferably 0.2 to 10 parts by weight, more preferably 0.5 to 7 parts by weight, relative to 100 parts by weight of the positive electrode material. In addition, with respect to the amount of the binder resin relative to 100 parts by weight of the positive electrode material, when the binder resin is slurried with water, it is preferably 0.2 to 10 parts by weight, more preferably 0.5 to 7 parts by weight. On the other hand, when the binder resin is slurried with an organic solvent such as N-methylpyrrolidone that dissolves the binder resin, it is preferably 0.5 to 20 parts by weight, more preferably 1 to 15 parts by weight.

[0364] Examples of the positive electrode current collector include aluminum, titanium, zirconium, hafnium, niobium, tantalum, and alloys thereof. Among these, aluminum, titanium, tantalum, and alloys thereof are preferred, and aluminum and alloys thereof are most preferred.

[0365] [B6-2. Electrolyte]

[0366] As the electrolyte solution, a solution prepared by dissolving various lithium salts in a conventionally known non-aqueous solvent can be used.

[0367] As the non-aqueous solvent, cyclic carbonates such as ethylene carbonate, fluoroethylene carbonate, propylene carbonate, butylene carbonate and vinylene carbonate can be used; chain carbonates such as dimethyl carbonate, ethyl methyl carbonate and diethyl carbonate; cyclic esters such as γ-butyrolactone; cyclic ethers such as crown ethers, 2-methyltetrahydrofuran, tetrahydrofuran, 1,2-dimethyltetrahydrofuran and 1,3-dioxolane; chain ethers such as 1,2-dimethoxyethane, etc. can be used. Usually, two or more of these solvents can be mixed and used. Among these, cyclic carbonates and chain carbonates are preferably used, or other solvents are further mixed therein and used.

[0368] Compounds such as vinylene carbonate, vinylethylene carbonate, succinic anhydride, maleic anhydride, propane sultone and diethyl sulfone, difluorophosphates such as lithium difluorophosphate, etc. may be added to the electrolyte. Furthermore, overcharge inhibitors such as diphenyl ether and cyclohexylbenzene may be added.

[0369] Examples of electrolytes dissolved in non-aqueous solvents include LiClO4, LiPF6, LiBF4, LiCF3SO3, LiN(CF3SO2)2, LiN(CF3CF2SO2)2, LiN(CF3SO2)(C4F9SO2), and LiC(CF3SO2)3. The concentration of the electrolyte in the electrolyte solution is usually 0.5 mol / L to 2 mol / L, preferably 0.6 mol / L to 1.5 mol / L.

[0370] [B6-3. Partition]

[0371] In the non-aqueous secondary battery of one embodiment of the present invention, a separator is preferably used, and the separator is interposed between the positive electrode and the negative electrode. As such a separator, a porous sheet or nonwoven fabric of polyolefin such as polyethylene or polypropylene is preferably used.

[0372] <C. Third embodiment>

[0373] The present invention is described in detail below, but the present invention is not limited to the following description and can be implemented after any deformation within the scope of the present invention. It should be noted that in the present invention, when "to" is used and numerical values ​​or physical property values ​​are sandwiched before and after it, the meaning used is to include the values ​​before and after it.

[0374] [C1. Negative electrode materials for non-aqueous secondary batteries]

[0375] A negative electrode material for a non-aqueous secondary battery (hereinafter sometimes referred to as "negative electrode material") according to one embodiment of the present invention is a graphite having at least one of an amorphous carbon material or a graphite material on at least a portion of its surface, wherein the non-aqueous secondary battery negative electrode material has a micropore distribution measured by mercury intrusion porosimetry having two or more peaks, and when the cumulative pore volume below the minimum value between the peak with the smallest micropore diameter and the valley of the next peak is set to y [mL / g], and the coverage of the amorphous carbon material and the graphite material on the graphite surface is set to x (%), the following equations (1) and (2) are satisfied, and the micropore diameter of the peak top of the peak with the smallest micropore diameter is less than 360 nm.

[0376] Formula (1): y>0.005

[0377] Formula (2): y<-0.006x+0.12

[0378] In addition, the negative electrode material for a non-aqueous secondary battery in another embodiment of the present invention preferably contains graphite having at least one of an amorphous carbon material or a graphite material on at least a portion of the surface, and the micropore distribution of the negative electrode material for a non-aqueous secondary battery measured by mercury intrusion has two or more peaks, and when the cumulative pore volume below the minimum value between the valleys of the peaks is set to y [mL / g] and the coverage is set to x (%), the following equations (1) and (3) are satisfied.

[0379] Formula (1): y>0.005

[0380] Formula (3): y<-0.006x+0.079

[0381] The nonaqueous secondary battery negative electrode material of this embodiment can provide a nonaqueous secondary battery for high-capacity batteries that can be pressed to a high density with a small pressing load and has small electrode plate expansion. Although the reason why the present invention exerts such an effect is not yet clear, it is believed to be due to the following reasons.

[0382] In the negative electrode material of the present embodiment, the cumulative pore volume in the range of micropore diameters below the minimum value in the pore volume obtained by mercury intrusion becomes an indicator of the pore volume present inside the negative electrode material particles. By reducing it to a specific range relative to the coverage, when the electrode is pressed to a certain density, compared with the previous negative electrode material with a large pore volume present inside the particle, it can be pressed in a state where the particle is less deformed, and compared with the negative electrode material with no micropores in the particle, it can be deformed appropriately when pressed. As a result, it can be pressed to a higher density.

[0383] In addition, the smallest peak in the mercury intrusion method is an indicator of the size of the micropores in the particle. The small peak of the micropores in the particle indicates that micropores with small pore diameters exist in the particle, and the scales in the particle are more densely bonded to each other. It is believed that the expansion of the plate after the cycle is reduced by dense bonding.

[0384] [C1-1. Physical properties]

[0385] The negative electrode material of one embodiment of the present invention satisfies the relationship between the cumulative pore volume and the coverage described below. In addition, the negative electrode material of the present invention preferably satisfies the following physical properties.

[0386] <C1-1-1. Pore volume>

[0387] In the negative electrode material of the present invention, the micropore distribution measured by the mercury intrusion method (mercury porosimetry) has more than two peaks, and when the cumulative pore volume below the minimum value between the peak with the smallest micropore diameter and the valley of the next peak is set to y (mL / g) and the coverage is set to x (%), the following formulas (1) and (2) are satisfied.

[0388] Formula (1): y>0.005

[0389] Formula (2): y<-0.006x+0.12

[0390] The number of peaks is 2 or more, more preferably 2.

[0391] The peak of the pore distribution indicates the spaces between particles and the spaces within particles. When there is only one peak, it means that only the spaces between particles exist, and deformation during pressing becomes insufficient.

[0392] Since the intraparticle voids are required to exist in the formula (1), y>0.005 is satisfied, y>0.01 is more preferred, and y>0.015 is even more preferred.

[0393] As formula (2), when y<αx+β is assumed, the horizontal axis is the coverage x, and the cumulative pore volume y is the y axis, which is expressed as: Figure 1The slope of formula (2) in , β represents the y intercept of formula (2). From the perspective of the coverage of amorphous carbon materials and graphite materials and the efficiency of filling the voids in the particles, α is preferably less than -0.0055, and preferably more than -0.007, more preferably more than -0.0065, and most preferably more than -0.006. From the perspective of the value of the voids in the particles before covering with at least one of the amorphous carbon material or the graphite material, β is preferably less than 0.11, more preferably less than 0.10, further preferably less than 0.09, particularly preferably less than 0.079, and most preferably less than 0.07. It is indicated outside the scope of the above formula that the micropores are not well covered by at least one of the amorphous carbon material or the graphite material, so that good compressibility cannot be obtained, and as a result, the fast charging and input and output storage characteristics are adversely affected.

[0394] The peak on the side with a small pore size indicates that the size of the micropores in the particle is small. The fine micropores in the particle indicate that there are micropores with small pore sizes in the example, and the scales in the particle are further densified. From this aspect, the micropore size of the peak with the smallest micropore size in the pore volume measured by mercury intrusion is preferably 350nm or less, more preferably 280nm or less, further preferably 220nm or less, further preferably 160nm or less, particularly preferably 100nm or less, and most preferably 85nm or less. It should be noted that when there is only one peak, it means that there is no void in the particle. The peak on the small side is outside the above range, indicating that there are large voids in the particle with a higher frequency, showing that the adhesion between the scales forming the particle is small. As a result, when charging and discharging are repeated, the particles expand, and the plate may expand further as a result.

[0395] <C1-1-2. Cumulative pore volume>

[0396] In the negative electrode material of the present invention, the cumulative pore volume in the range below the minimum value between the valleys of the two peaks on the side with a small micropore size of the micropore distribution is a value measured using mercury intrusion method (mercury porosimetry), which is usually 0.12mL / g or less, preferably 0.080mL / g or less, more preferably 0.070mL / g or less, further preferably 0.060mL / g or less, particularly preferably 0.050mL / g or less, most preferably 0.040mL / g or less, on the other hand, preferably 0.001mL / g or more, more preferably 0.002mL / g or more, further preferably 0.005mL / g or more, particularly preferably 0.010mL / g or more, most preferably 0.020mL / g or more. If it is within the above range, charging and discharging enables Li ions to move smoothly in the electrode, and fast charge and discharge characteristics and low temperature input and output characteristics are good, so it is preferred.

[0397] As an apparatus for the above-mentioned mercury porosimetry, a mercury porosimeter (Autopore9520: manufactured by Micrometritics) can be used. The sample (negative electrode material) is weighed to a value of about 0.2 g, sealed in a powder container, and pre-treated by degassing for 10 minutes at room temperature and vacuum (below 50μmHg). Next, the pressure is reduced to 4psia (about 28kPa), and mercury is introduced into the above-mentioned container to increase the pressure stepwise from 4psia (about 28kPa) to 40000psia (about 280MPa), and then reduced to 25psia (about 170kPa). The number of steps during the pressure increase is set to more than 80 points, and after maintaining a balance time of 10 seconds in each step, the amount of mercury intrusion is measured. The micropore distribution is calculated from the mercury intrusion curve obtained in this way using the Washburn formula. It should be noted that the calculation was performed on the assumption that the surface tension (γ) of mercury was 485 dyne / cm and the contact angle (ψ) was 140°.

[0398] Then, based on the obtained results, a graph is plotted with the pore diameter on the horizontal axis and the pore volume on the vertical axis, and the minimum value between the peak with the smallest pore diameter and the valley of the next peak in the graph is obtained, and the minimum value is defined as the cumulative pore volume y.

[0399] <C1-1-3. Coverage rate>

[0400] In this specification, the coverage x (%) can be obtained as follows: That is, it can be calculated based on the mixing ratio of graphite and the amorphous precursor and the firing yield after firing.

[0401] Formula (4):

[0402] Coverage x (%) = ([weight of sample after sintering - weight of graphite] / [weight of sample after sintering] × 100)

[0403] In the case of a sample whose mixing ratio and firing yield are unknown, they can be estimated using the difference in true density between amorphous and graphite.

[0404] First, the crystallinity of the base material graphite is confirmed by the d002 value of XRD. The theoretical d002 value of graphite is Natural graphite with high crystallinity shows a value close to the theoretical value. On the other hand, for artificial graphite, the value of d002 varies greatly depending on the type of raw coke and the graphitization temperature. The d002 value is preferably The following, more preferably The following is more preferably If the d002 value is outside the above range, the crystallinity of the graphite is low and the charge-discharge capacity is insufficient, which is not preferred. For the following high crystallinity, the coverage can be estimated using the following estimation formula (5).

[0405] Formula (5):

[0406] Coverage (%) = 596.72 - 264.02 × true density

[0407] The true density of the negative electrode material according to one embodiment of the present invention is preferably 2.200 g / cm 3 More preferably, 2.210 g / cm 3 More preferably, 2.200 g / cm 3 Above, the theoretical true density of graphite is 2.262g / cm 3 .

[0408] The above coverage is usually 20% or less, preferably 15% or less, more preferably 10% or less, further preferably 9% or less, particularly preferably 8% or less, and most preferably 7% or less. On the other hand, it is preferably 0.1% or more, more preferably 1% or more, further preferably 2% or more, and particularly preferably 3% or more. If it is below the above upper limit, the proportion of graphite in the negative electrode material is appropriate, and it is easy to increase the capacity. On the other hand, if it is above the lower limit, the amorphous material is appropriate, and lithium ions can be smoothly moved from the graphite surface, so the rapid charge and discharge characteristics and low temperature input and output characteristics are good.

[0409] The true density is defined as a value measured by a liquid substitution method (pycnometer method) using butanol. In order to reduce the measurement error during the measurement as much as possible, it is preferred that the measurement be performed at least 3 times, preferably 5 times, more preferably 7 times, and particularly preferably 10 times and the average value is used.

[0410] The d002 value of the carbon material of the present invention can be determined by X-ray diffraction based on the Gakatsuki method. The X-ray diffraction measurement conditions here are as follows.

[0411] X-ray: Cu Kα ray

[0412] Measuring range and step angle: 20 degrees ≤ 2θ ≤ 30 degrees, 0.013 degrees

[0413] Sample adjustment: Powdered sample is filled in the concave part of the sample plate with a depth of 0.2 mm to make a flat sample surface. The values ​​measured by the Gakushin method can be used as the interplanar spacing d002 and crystallite size Lc002 measured by the above X-ray diffraction. It should be noted that in the Gakushin method, for 100 nm The above values ​​are not differentiated and are all recorded as

[0414] <C1-1-4. BET specific surface area (SA)>

[0415] The specific surface area (SA) of the negative electrode material according to one embodiment of the present invention based on the BET method is preferably 0.5 m 2 / g or more, more preferably 0.8m 2 / g or more, more preferably 1.0 m 2 / g or more, on the other hand, preferably 10.0m 2 / g or less, more preferably 6.5m 2 / g or less, more preferably 5.0m 2 / g or less, particularly preferably 4.0m 2 / g or less. If SA is above the above lower limit, the position where Li ions enter and exit can be ensured, and there is a tendency for the rapid charge and discharge characteristics and low temperature input and output characteristics of the lithium ion secondary battery to become good. On the other hand, if SA is below the above upper limit, the activity of the active material to the electrolyte becomes too excessive, and the side reaction with the electrolyte is suppressed to prevent the reduction of the initial charge and discharge efficiency of the battery and the increase of the amount of gas generated, and there is a tendency for the battery capacity to increase.

[0416] It should be noted that the BET specific surface area (SA) can be measured using Macsorb manufactured by Mountech. Specifically, the measurement can be performed as follows: After the sample is pre-dried under reduced pressure at 100°C for 3 hours under nitrogen flow, it is measured by the nitrogen adsorption BET 1-point method using a gas flow method using a nitrogen-helium mixed gas cooled to liquid nitrogen temperature and with the relative pressure of nitrogen gas to atmospheric pressure accurately adjusted to 0.3.

[0417] <C1-1-5. Tap density>

[0418] The tap density (g / cm 3 ) is preferably 1.15 g / cm 3 More preferably, 1.16 g / cm 3 More preferably, 1.17 g / cm 3 More than, particularly preferably 1.18 g / cm 3 On the other hand, it is preferably 1.40 g / cm 3 Below, more preferably 1.35g / cm 3 Below, more preferably 1.30 g / cm 3If the tap density is above the above lower limit, the process of streaking during the production of the plate becomes good, the filling property of the negative electrode material layer is improved, and therefore, the rolling property is good, and a high-density negative electrode sheet is easily formed, and high density becomes possible. When the electrode body is made, the curvature of the Li ion migration path becomes small, and the shape of the interparticle gap is neat, so the movement of the electrolyte becomes smooth, and the rapid charge and discharge characteristics are improved, which is preferred from the above viewpoint. In addition, if it is below the above upper limit, the surface and interior of the particle have appropriate space, the particle will not become too hard, the electrode compressibility is excellent, and the low-temperature input and output characteristics and rapid charge and discharge characteristics are excellent, which is preferred from the above viewpoint.

[0419] It should be noted that the tap density was measured using a powder density measuring instrument Tapdenser KYT-3000 (manufactured by Seishin Enterprise Co., Ltd.) Specifically, the sample was dropped into a 20cc tap container, and after the container was filled, 1000 taps were performed with a stroke length of 10 mm, and the density at this time was taken as the tap density.

[0420] <C1-1-6. Tablet density @2.4t / cm 3 >

[0421] Insert two tools, a φ10, 35mm long shaft as an extrusion tool, and a φ10, 6mm long shaft as a support tool, into a die with an inner diameter of φ10. Then install it in a device that can measure the load and height (thickness) when clamped (for example, powder resistance measurement system manufactured by Mitsubishi Chemical Analytech Co Ltd.), apply a load of 15kgf with a hydraulic pump, and measure the tool height. Next, take out only the extrusion tool, add 0.6g of composite particles, and insert the extrusion tool again. Install the die on a hydraulic jack (for example, high-pressure jack J-1 manufactured by AS ONE), close the pressure valve, and slowly pressurize to 0.9t / cm 2 , and then quickly pressurize to 2.4t / cm 2 After that, hold for 3 seconds, remove your hand from the hydraulic jack, wait for 60 seconds, and release the pressure valve to reduce the pressure. Then, install it again on a device that can measure the load and height when clamped, apply a load of 15kgf with a hydraulic pump, and measure the height of the tool after pressurization. At the same time, measure the weight of the composite particles after pressurization, and define the density calculated by the difference in the tool height and the weight as the tableting density. The load per unit area can be calculated from the scale of the hydraulic jack, the diameter of the cylinder, and the inner diameter of the mold. For example, in the embodiment described later, a cylinder diameter of φ22mm is used, and pressure is applied until the scale of the shaft reaches 500kgf, and 2.4t / cm 2 of load.

[0422] <C1-1-7. Tablet density - tap density>

[0423] Subtract the tap density (g / cm2) from the tablet density 3 ) represents the ease of compaction when a load is applied and can be used as an indicator of the hardness of the particles.

[0424] The tablet density - tap density is preferably 0.1 g / cm 3 More preferably, 0.15 g / cm 3 More preferably, 0.2 g / cm 3 More than, particularly preferably 0.26 g / cm 3 On the other hand, it is preferably 0.8 g / cm 3 Below, more preferably 0.6 g / cm 3 Below, more preferably 0.4 g / cm 3 If the tablet density-tap density is below the upper limit, the particles have a moderate hardness, and the particles on the electrode surface will not be too damaged when pressed to a high density, and the movement of the electrolyte becomes smooth, so it is preferred. In addition, if it is above the lower limit, the particles will not be too hard and can be pressed to a high density, so it is preferred.

[0425] <C1-1-8. Volume-based average particle size (average particle size d50)>

[0426] The volume-based average particle size (also referred to as "average particle size d50") of the negative electrode material of one embodiment of the present invention is preferably 1 μm or more, more preferably 3 μm or more, further preferably 4 μm or more, particularly preferably 5 μm or more, and preferably 50 μm or less, more preferably 40 μm or less, further preferably 30 μm or less, particularly preferably 25 μm or less, and most preferably 20 μm or less. If the value of d50 is above the lower limit, there is a tendency to prevent the increase of irreversible capacity and the loss of initial battery capacity. On the other hand, if the value of d50 is below the upper limit, the occurrence of process defects such as streaks in slurry coating can be prevented, and there is a tendency to improve rapid charge and discharge characteristics and low-temperature input and output characteristics.

[0427] The average particle size (d50) is defined as follows: 0.01 g of composite particles are suspended in 10 mL of a 0.2% by mass aqueous solution of polyoxyethylene sorbitan monolaurate (for example, Tween 20 (registered trademark)) as a surfactant, and the suspension is introduced as a measurement sample into a commercially available laser diffraction / scattering particle size distribution measuring apparatus (for example, LA-920 manufactured by HORIBA), and the measurement sample is irradiated with 28 kHz ultrasonic waves at an output power of 60 W for 1 minute, and then the volume-based median diameter is measured in the above-mentioned measuring apparatus, which is defined as the average particle size d50.

[0428] [C2. Manufacturing method]

[0429] The manufacturing method of the negative electrode material for non-aqueous secondary batteries of one embodiment of the present invention is not particularly limited as long as it is capable of manufacturing a method for manufacturing a negative electrode material having at least one of an amorphous carbon material or a graphite material in at least a portion of the surface, satisfying a specific relationship between the intra-particle voids relative to the coverage, and the peak of the peak below the minimum value in the pore volume measured by the mercury intrusion method satisfies a specific size. For example, spherical graphite can be pressurized and mixed with an amorphous carbon precursor (raw material of amorphous carbon material) and fired to manufacture, wherein the spherical graphite is obtained by finely crushing the flakes and implementing spheroidization in the presence of a granulating material. Pressure treatment can cite anisotropic and isotropic pressure treatments, but from the viewpoint of controlling the relationship between the above-mentioned cumulative pore volume y and the above-mentioned coverage x within a specific range, isotropic pressure treatment is preferred. In addition, as a condition for pressure treatment, it is not particularly limited, and by treating at 50MPa or more and 300MPa or less, the relationship between the above-mentioned cumulative pore volume y and the above-mentioned coverage x can be controlled within a specific range. As for the conditions of the pressure treatment, from the viewpoint of controlling the relationship between the cumulative pore volume y and the coverage x within a specific range, it is preferably 100 MPa or more, more preferably 120 MPa or more, further preferably 140 MPa or more, particularly preferably 160 MPa or more, and most preferably 180 MPa or more, and preferably 280 MPa or less, more preferably 260 MPa or less, further preferably 240 MPa or less, particularly preferably 230 MPa or less, and most preferably 220 MPa or less. Specifically, the above-mentioned manufacturing method is preferred because it can control the pore volume per unit coverage by controlling the crushing conditions, spheroidization conditions, molding pressure, and coverage of the flakes, and can control the size of the peak top of the small peak.

[0430] <C2-1. Graphite>

[0431] The negative electrode material of one embodiment of the present invention includes graphite. The graphite used to manufacture the negative electrode material of one embodiment of the present invention preferably shows the following types and properties. It should be noted that the physical properties of graphite are the same as those described above for the negative electrode material unless the measurement conditions and definitions thereof are particularly described.

[0432] For the type of graphite, as long as it can occlude and release lithium ions, its type is not particularly limited, and it can be any graphite in natural graphite and artificial graphite. As natural graphite, it can be any graphite of flaky graphite, blocky graphite, soil graphite, etc., but preferably graphite with few impurities, preferably used after known purification treatment as needed. As artificial graphite, it can be listed: artificial graphite obtained by sintering and graphitizing organic substances such as coal tar pitch, coal-based heavy oil, atmospheric residue, petroleum-based heavy oil, aromatic hydrocarbons, nitrogen-containing cyclic compounds, sulfur-containing cyclic compounds, polyphenylene, polyvinyl chloride, polyvinyl alcohol, polyacrylonitrile, polyvinyl butyral, natural polymer, polyphenylene sulfide, polyphenylene ether, furfuryl alcohol resin, phenol phenolic resin, imide resin at a temperature of usually more than 2500°C and usually less than 3200°C. At this time, silicon-containing compounds, boron-containing compounds, etc. can also be used as graphitization catalysts.

[0433] Regarding the crystallinity (degree of graphitization) of graphite, the interplanar spacing (d002) of the (002) plane determined by the X-ray wide-angle diffraction method is generally preferably The following, more preferably The following is more preferably When d002 is within the above range, the crystallinity of graphite is appropriate and sufficient charge and discharge capacity is obtained, which is preferable.

[0434] As for the shape of graphite, spherical graphite (spheroidized graphite) is particularly preferred from the viewpoint of rapid charge and discharge characteristics. As a method for spheroidizing graphite particles, it is particularly preferred to have a granulation step, which is a step of imparting at least any mechanical energy of impact, compression, friction and shear force to the granulated raw carbon material, and the granulation step is carried out in the presence of a granulating agent that satisfies the following conditions 1) and 2).

[0435] 1) In the step of granulating the raw carbon material, the granulated material is liquid.

[0436] 2) The granulated material contains an organic compound that becomes amorphous carbon.

[0437] 3) The granulating agent does not contain an organic solvent, or, if it contains an organic solvent, at least one of the organic solvents does not have a flash point, or, if it has a flash point, the flash point is 5° C. or higher.

[0438] As long as the above-mentioned granulation step is provided, other steps may be further provided as required. Other steps may be implemented individually or in multiple steps simultaneously. As an embodiment, a method including the following steps 1 to 5 may be listed. These steps are described below.

[0439] (Step 1) Step of adjusting the particle size of the raw carbon material

[0440] (Second step) Step of mixing raw carbon material and granulating agent

[0441] (Step 3) Step of granulating the raw carbon material

[0442] (Step 4) Step of removing granulating agent

[0443] (Step 5) A step of adding an amorphous carbon material having a lower crystallinity than the raw carbon material to the granulated carbon material.

[0444] (Step 1) Step of adjusting the particle size of the raw carbon material

[0445] The above-mentioned graphite is used as the raw carbon material for producing the negative electrode material for a non-aqueous secondary battery of the present invention.

[0446] The raw coke material is preferably adjusted to the following particle size in the first step. That is, the average particle size (d50) of the obtained raw coke material is preferably 1 μm or more, more preferably 2 μm or more, and further preferably 3 μm or more. On the other hand, it is preferably 30 μm or less, more preferably 20 μm or less, further preferably 15 μm or less, particularly preferably 12 μm or less, and most preferably 9 μm or less.

[0447] By adjusting the particle size of the raw carbon material so that d50 is within the above range, it becomes an ideal particle size for a negative electrode material after spheroidization, and the distance between scales becomes short, resulting in strong particles, which is preferred.

[0448] Examples of a method for adjusting the d50 of the raw carbon material to the above range include at least one of pulverizing and classifying (natural) graphite particles.

[0449] The device used for pulverizing is not particularly limited. For example, as a coarse pulverizer, a shearing mill, a jaw crusher, an impact crusher, a cone crusher, etc. can be listed. As an intermediate pulverizer, a roller crusher, a hammer mill, etc. can be listed. As a fine pulverizer, a mechanical pulverizer, an air flow pulverizer, a cyclone pulverizer, etc. can be listed. Specifically, a ball mill, a vibration mill, a pin pulverizer, a stirring mill, a jet mill, a cyclone mill, a turbine mill, etc. can be listed. In particular, in the case of obtaining graphite particles with a d50 of less than 10 μm, it is preferred to use an air flow pulverizer or a cyclone pulverizer.

[0450] There are no particular restrictions on the device used for the classification process. For example, in the case of dry screening, a rotary screen, a shaking screen, a rotating screen, a vibrating screen, etc. can be used. In the case of dry airflow classification, a gravity classifier, an inertial force classifier, a centrifugal force classifier (granulator, cyclone separator), etc. can be used. In addition, in the case of wet screening, a mechanical wet classifier, a hydraulic classifier, a sedimentation classifier, a centrifugal wet classifier, etc. can be used.

[0451] In addition, the raw carbon material obtained in the first step preferably satisfies the following physical properties.

[0452] For the interplanar spacing (d002) and crystallite size (Lc) of the 002 plane measured by wide-angle X-ray diffraction of the raw carbon material, d002 is usually Below, Lc is Above, preferably d002 is Below, Lc is Above. d002 and Lc are values ​​representing the crystallinity of the bulk of the carbon material. The smaller the value of d002 and the larger the Lc, the more crystalline the carbon material is. Since the amount of lithium entering the graphite interlayer is close to the theoretical value, the capacity increases. If the crystallinity is low, there is a tendency that the high capacity and the low irreversible capacity of the excellent battery characteristics when the high crystalline graphite is used for the electrode cannot be shown. The combination of d002 and Lc in the above range is particularly preferred.

[0453] X-ray diffraction is measured by the following method. First, about 15% by mass of X-ray standard high-purity silicon powder is added to the carbon powder and mixed. The mixed mixture is used as the material, and CuKα rays monochromated by a graphite monochromator are used as the ray source. The wide-angle X-ray diffraction curve is measured by a reflection X-ray diffractometer method. Then, the interplanar spacing (d002) and the crystallite size (Lc) are obtained using the Xuezhen method.

[0454] The filling structure of the raw carbon material is affected by the size, shape, degree of interaction between particles, etc., but in the present invention, the tap density can also be used as one of the indicators for quantitatively discussing the filling structure. The research of the inventors and others has confirmed that for graphite particles with essentially equal true density and average particle size, the more spherical the shape and the smoother the particle surface, the higher the tap density. That is, in order to increase the tap density, it is important to make the shape of the particles close to spherical and maintain the smoothness of the particle surface. When the particle shape is close to spherical and the particle surface is smooth, the filling property of the powder is also significantly improved. The tap density of the raw carbon material is preferably 0.1g / cm 3 More preferably, 0.15 g / cm3 More preferably, 0.2 g / cm 3 More than, particularly preferably 0.3 g / cm 3 The tap density is measured by the method described later in Examples.

[0455] The argon ion laser Raman spectrum of the raw carbon material is used as an indicator to characterize the surface properties of the particles. The Raman R value of the raw carbon material is preferably 0.05 or more and 0.9 or less, more preferably 0.05 or more and 0.7 or less, and further preferably 0.05 or more and 0.5 or less, wherein the Raman R value is the value of the argon ion laser Raman spectrum at 1360 cm -1 The peak intensity near 1580 cm -1 The R value is the ratio of the peak intensity near the surface of the carbon particle (the distance from the particle surface The R value is an index of crystallinity (within ), and the smaller the R value, the higher the crystallinity, or the crystal state is not disordered. Raman spectrum is measured by the method shown below. Specifically, the sample is filled by allowing the particles of the measured object to fall naturally into the Raman spectrometer measuring cell, irradiating the measuring cell with argon ion laser, and rotating the measuring cell in a plane perpendicular to the laser for measurement. It should be noted that the wavelength of the argon ion laser is 514.5nm.

[0456] The BET specific surface area (SA) of the raw material flaky graphite is preferably 5 m 2 / g or more, more preferably 10m 2 / g or more, and preferably 25 m 2 / g or less, more preferably 20m 2 When it is within the above range, the spheroidization can be efficiently performed in the next step of spheroidization, which is preferred.

[0457] The BET specific surface area (SA) of the raw material flaky graphite can be measured using Macsorb manufactured by Mountech Co., Ltd. Specifically, the measurement can be performed as follows: After the sample is pre-dried under reduced pressure at 100°C for 3 hours under nitrogen flow, it is measured by the nitrogen adsorption BET 1-point method using the gas flow method using a nitrogen-helium mixed gas cooled to liquid nitrogen temperature and the relative pressure value of nitrogen to atmospheric pressure accurately adjusted to 0.3.

[0458] (Second step) Step of mixing raw carbon material and granulating agent

[0459] The granulating agent used in one embodiment of the present invention satisfies the following conditions: 1) it is liquid during the above-mentioned step of granulating the raw carbon material; 2) the granulating material contains an organic compound that becomes amorphous carbon; and 3) the granulating agent does not contain an organic solvent, or when it contains an organic solvent, at least one of the organic solvents does not have a flash point, or when it has a flash point, the flash point is above 5°C.

[0460] By having a granulating agent that meets the above requirements, when the raw carbon material is granulated in the subsequent third step, liquid bridging is performed between the raw carbon materials through the granulating agent, and the attractive force generated by the capillary negative pressure in the liquid bridge between the raw carbon materials and the liquid surface tension plays a role of liquid bridging adhesion force between the particles. The liquid bridging adhesion force between the raw carbon materials is increased, so that the raw carbon material is more firmly attached to the particle surface, and the distance between the scales can be more effectively shortened, so it is preferred.

[0461] In the present invention, the strength of the liquid bridging adhesion between the raw carbon materials generated by the granulating agent performing liquid bridging between the raw carbon materials is proportional to the γcosθ value (wherein γ: surface tension of the liquid, θ: contact angle between the liquid and the particles). That is, when the raw carbon material is granulated, the granulating agent is preferably one with high wettability with the raw carbon material. Specifically, it is preferred to select a granulating agent with cosθ>0 so that the γcosθ value>0, and the contact angle θ of the granulating agent with graphite measured by the following measurement method is preferably less than 90°.

[0462] (Method for measuring contact angle θ with graphite)

[0463] 1.2 μL of granulating agent is dropped on the surface of HOPG, and the contact angle is measured by a contact angle measuring device (e.g., automatic contact angle measuring instrument DM-501 manufactured by Kyowa Interface Co., Ltd.) when the wetting extension converges and the change rate of the contact angle θ per second reaches 3% or less (also referred to as a steady state). In the case of using a granulating agent having a viscosity of 500 cP or less at 25°C, the value at 25°C is used as the measured value of the contact angle θ, and in the case of using a granulating agent having a viscosity of more than 500 cP at 25°C, the value at a temperature heated to a viscosity of 500 cP or less is used as the measured value of the contact angle θ.

[0464] In addition, the closer the contact angle θ between the raw carbon material and the granulating agent is to 0°, the larger the γcosθ value becomes, so the liquid bridging adhesion between the graphite particles increases, and the graphite particles can be more firmly attached to each other. Therefore, the contact angle θ between the above-mentioned granulating agent and the graphite is more preferably 85° or less, further preferably 80° or less, further preferably 50° or less, particularly preferably 30° or less, and most preferably 20° or less.

[0465] By using a granulating agent having a large surface tension (γ), the γcosθ value also becomes large, and the adhesion of the graphite particles is improved. Therefore, γ is preferably 0 or more, more preferably 15 or more, and further preferably 30 or more. The surface tension (γ) of the granulating agent can be measured using a surface tension meter (e.g., DCA-700 manufactured by Kyowa Interface Science Co., Ltd.) according to the Wilhelmy method.

[0466] In addition, as an impedance component to the extension of the liquid bridge generated by the movement of the particles, the viscous force acts, and its magnitude is proportional to the viscosity. Therefore, if the raw carbon material is liquid during the granulation process, the viscosity of the granulating agent is not particularly limited, but is preferably 1 cP or more during the granulation process.

[0467] The viscosity of the granulating agent at 25° C. is preferably 1 cP to 100,000 cP, more preferably 5 cP to 10,000 cP, further preferably 10 cP to 8,000 cP, and particularly preferably 50 cP to 6,000 cP. If the viscosity is within the above range, when the raw carbon material is granulated, the detachment of the attached particles due to the impact force of collision with the rotor, the housing, etc. can be prevented.

[0468] The viscosity of the granulating agent used in the present invention is measured using a rheometer (e.g., ARES manufactured by Rheometric Scientific Co., Ltd.), by adding an appropriate amount of the object to be measured (here, the granulating agent) into a cup and adjusting the temperature to a given value. -1 When the shear stress is 0.1 Pa or more, the shear rate is 100 s -1 The value measured at the following conditions is defined as the viscosity in this specification, at a shear rate of 100 s -1 When the shear stress is less than 0.1Pa, the -1 The value measured at the following conditions is defined as the viscosity in this specification, at a shear rate of 1000s -1 When the shear stress under the condition of less than 0.1 Pa, the value measured at the shear rate at which the shear stress reaches 0.1 Pa or more is defined as the viscosity in this specification. It should be noted that the shear stress can also be made 0.1 Pa or more by setting the shaft used to a shape suitable for low-viscosity fluids.

[0469] In addition, the viscosity of the granulating agent when the raw carbon material and the granulating agent are mixed is preferably 1 cP or more and 1000 cP or less, more preferably 5 cP or more and 800 cP or less, further preferably 10 cP or more and 600 cP or less, and particularly preferably 20 cP or more and 500 cP or less. If the viscosity is within the above range, the granulating material is uniformly attached to the raw carbon material, and when the raw carbon material is granulated, the detachment of the attached particles caused by the impact force of the collision with the rotor and the housing can be prevented. In addition, the granulating material enters the micropores of 1 nm to 4 nm and becomes amorphous carbon in the subsequent process. Thus, the micropores can be reduced, so that the negative electrode material with excellent low-temperature input-output characteristics and high-temperature storage characteristics can be manufactured, so it is preferred. The viscosity in the above-mentioned process of granulating the raw carbon material can be adjusted by adding an organic solvent described later and controlling the mixing temperature.

[0470] In addition, the granulating agent used in the embodiment of the present invention includes an organic compound that becomes amorphous carbon. Thus, by the granulating material entering the micropores of 1nm to 4nm to form amorphous carbon, the micropores can be reduced, so that the negative electrode material with excellent low-temperature input-output characteristics and high-temperature storage characteristics can be manufactured. For example, resins such as heavy oil, tar and asphalt of petroleum and coal systems, polyvinyl alcohol, polyacrylonitrile, phenolic resin, cellulose, etc. can be listed. As needed, water-based solvents can be used, or organic solvents without flash points can be used, or organic solvents with flash points of 5°C or more can be used for dilution. Among these, it is preferred to include heavy oil, tar, asphalt, etc. of petroleum and coal systems as soft carbon, because they are not easy to generate micropores when they are amorphous carbon, and can more effectively reduce micropores of 1nm to 4nm.

[0471] In addition, the granulating agent used in the embodiment of the present invention does not contain an organic solvent, or when containing an organic solvent, at least one of the organic solvents does not have a flash point, or when having a flash point, the flash point is 5° C. or more. As a result, when the raw carbon material is granulated in the subsequent third step, the risk of ignition, fire, and explosion of the granulating agent caused by impact and heat generation can be prevented, so that stable and efficient production can be performed.

[0472] Examples of organic solvents having a flash point of 5° C. or higher include: paraffin oils such as liquid paraffin, olefin oils, cycloparaffin oils, aromatic oils and other synthetic oils, plant oils, animal aliphatics, esters, higher alcohols and other natural oils; alkylbenzenes such as xylene, cumene, ethylbenzene, and propylbenzene; alkylnaphthalenes such as methylnaphthalene, ethylnaphthalene, and propylnaphthalene; aromatic hydrocarbons such as allylbenzene and allylnaphthalene such as styrene; aliphatic hydrocarbons such as octane, nonane, and decane; ketones such as methyl isobutyl ketone, diisobutyl ketone, and cyclohexanone; esters such as propyl acetate, butyl acetate, isobutyl acetate, and amyl acetate; alcohols such as methanol, ethanol, propanol, butanol, isopropyl alcohol, isobutyl alcohol, ethylene glycol, propylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, and glycerol; ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl Ether, diethylene glycol monobutyl ether, triethylene glycol monobutyl ether, tetraethylene glycol monobutyl ether, methoxypropanol, methoxypropyl-2-acetate, methoxymethyl butanol, methoxybutyl acetate, diethylene glycol dimethyl ether, dipropylene glycol dimethyl ether, diethylene glycol ethyl methyl ether, triethylene glycol dimethyl ether, tripropylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, ethylene glycol monophenyl ether and other glycol derivatives; ethers such as 1,4-dioxane; nitrogen-containing compounds such as dimethylformamide, pyridine, 2-pyrrolidone, N-methyl-2-pyrrolidone; sulfur-containing organic compounds such as dimethyl sulfoxide; halogen-containing organic compounds such as dichloromethane, chloroform, carbon tetrachloride, dichloroethane, trichloroethane, chlorobenzene; and mixtures thereof, etc., do not contain substances with low flash points such as toluene. These organic solvents can also be used alone as granulating agents. It should be noted that in this specification, the flash point can be measured by a known method.

[0473] As a method for mixing the raw carbon material and the granulating agent, for example, the method of mixing the raw carbon material and the granulating agent using a mixer or a kneading machine, the method of mixing the granulating agent obtained by dissolving an organic compound in a low-viscosity diluent solvent (organic solvent) with the raw carbon material, and then removing the diluent solvent (organic solvent), etc. Among these methods, the method of mixing the raw carbon material and the granulating agent using a mixer or a kneading machine is preferred, because in this method, the more components that become carbon substances in the organic compound, the more effectively the micropores of 1nm to 4nm can be reduced. In addition, it is also possible to cite a method of mixing the raw carbon material and the granulating agent by simultaneously putting the granulating agent and the raw carbon material into a granulating device when the raw carbon material is granulated in the next third step, and a method of performing a granulation step.

[0474] The amount of the granulating agent added is preferably 0.1 parts by weight or more, more preferably 1 part by weight or more, further preferably 3 parts by weight or more, further preferably 6 parts by weight or more, further preferably 10 parts by weight or more, particularly preferably 12 parts by weight or more, and most preferably 15 parts by weight or more, and preferably 1000 parts by weight or less, more preferably 100 parts by weight or less, further preferably 80 parts by weight or less, particularly preferably 50 parts by weight or less, and most preferably 30 parts by weight or less. If it is within the above range, it is not easy to produce problems such as a decrease in the degree of sphericity caused by a decrease in the adhesion between particles and a decrease in productivity caused by the adhesion of the raw carbon material to the device.

[0475] (Step 3) Step of granulating the raw carbon material (step of spheroidizing the raw carbon material)

[0476] The carbon material is preferably a carbon material obtained by subjecting the raw carbon material to a spheroidization treatment (hereinafter also referred to as granulation) by applying mechanical effects such as impact compression, friction, and shearing force. In addition, the spheroidized graphite is preferably formed of a plurality of flaky or scale-like graphites and ground graphite powders, and is particularly preferably formed of a plurality of flaky graphites.

[0477] The present invention preferably has a granulation step for granulating the raw carbon material by applying at least any mechanical energy of impact, compression, friction and shearing force. As an apparatus used in this step, for example, an apparatus can be used that repeatedly applies mechanical action such as compression, friction, shearing force, etc., mainly including impact force and also including interaction of the raw carbon material.

[0478] Specifically, the following device is preferred: a device having a rotor with a plurality of blades disposed inside a housing, and applying mechanical effects such as impact, compression, friction, shearing force, etc. to the raw carbon material introduced inside by high-speed rotation of the rotor, thereby performing surface treatment. In addition, a device having a mechanism for repeatedly applying mechanical effects by circulating the raw carbon material is preferred.

[0479] As such an apparatus, for example, a hybridization system (manufactured by Nara Machinery Co., Ltd.), Kryptron, Kryptron Orb (manufactured by Earthtechnica Co., Ltd.), CF mill (manufactured by Ube Industries, Ltd.), mechanical melting system, Nobilta, Faculty (manufactured by Hosokawa Micron Co., Ltd.), Theta Composer (manufactured by Tokuju Kosho Co., Ltd.), COMPOSI (manufactured by Nippon Coke Industries), etc. Among these, a hybridization system manufactured by Nara Machinery Co., Ltd. is preferred.

[0480] When the above-mentioned device is used for treatment, for example, the circumferential speed of the rotating rotor is preferably 30 m / s or more, more preferably 50 m / s or more, further preferably 60 m / s or more, particularly preferably 70 m / s or more, most preferably 80 m / s or more, and preferably 100 m / s or less. Within the above range, spheroidization can be more effectively performed, and the adhesion of the fine powder to the base material and the inclusion of the fine powder in the base material can be performed simultaneously.

[0481] In addition, although the treatment of imparting mechanical action to the raw carbon material can be carried out by simply allowing the raw carbon material to pass through, it is preferred to allow the raw carbon material to circulate or retain in the device for more than 30 seconds, more preferably allow the raw carbon material to circulate or retain in the device for more than 1 minute, further preferably allow the raw carbon material to circulate or retain in the device for more than 3 minutes, and particularly preferably allow the raw carbon material to circulate or retain in the device for more than 5 minutes.

[0482] In addition, the viscosity of the granulating agent when the raw carbon material and the granulating agent are mixed is preferably 1 cP or more, more preferably 5 cP or more, further preferably 10 cP or more, and particularly preferably 20 cP or more. On the other hand, it is preferably 1000 cP or less, more preferably 800 cP or less, further preferably 600 cP or less, and particularly preferably 500 cP or less. If the viscosity is within the above range, when the raw carbon material is granulated in the presence of the granulating material, the detachment of the attached particles caused by the impact force of the collision with the rotor and the housing can be prevented. In addition, the granulating material enters the micropores of 1 nm to 4 nm and becomes amorphous carbon in the subsequent process. Thus, the micropores can be reduced, thereby being able to manufacture a negative electrode material with excellent low-temperature input-output characteristics and high-temperature storage characteristics, so it is preferred. The viscosity in the above-mentioned process of granulating the raw carbon material can be adjusted by adding an organic solvent described later and controlling the mixing temperature.

[0483] In addition, in the process of granulating the raw carbon material, the raw carbon material can also be granulated in the presence of other substances, such as metals or their oxides that can be alloyed with lithium, flaky graphite, flaky graphite, ground graphite powder, amorphous carbon and unbaked coke, etc. By simultaneously using substances other than the raw carbon material for granulation, non-aqueous secondary battery carbon materials of various types of particle structures can be manufactured.

[0484] In addition, the raw carbon material, granulating agent and the above-mentioned other substances can be put into the above-mentioned device in full at one time, or they can be put in separately in sequence, or they can be put in continuously. In addition, the raw carbon material, granulating agent and the above-mentioned other substances can be put into the above-mentioned device at the same time, or they can be put in after mixing, or they can be put in separately. The raw carbon material, granulating agent and the above-mentioned other substances can be mixed at the same time, or the above-mentioned other substances can be added to the mixture obtained by mixing the raw carbon material and the granulating agent, and the raw carbon material can be added to the mixture obtained by mixing other substances and the granulating agent. According to the particle design, it can be added and mixed separately at an appropriate time.

[0485] During the spheroidization of carbon materials, it is more preferred to carry out spheroidization while making the fine powder generated in the spheroidization effectively attached to the particle surface. By making the fine powder generated in the spheroidization attached to the particle surface while carrying out spheroidization, small scales are densely bonded to the gaps between large scales, and the scales can be firmly bonded. Therefore, when coated with amorphous materials or graphitized materials thereafter, the intra-particle voids can be more effectively reduced. In addition, the amount of the edge that can be used as the insertion / detachment site of Li ions increases, and the electrolyte can be effectively and efficiently distributed throughout the intra-particle voids, thereby effectively utilizing the insertion and detachment sites of Li ions in the particles, so that there is a tendency to show good low-temperature output characteristics and cycle characteristics. In addition, the fine powder attached to the base material is not limited to the fine powder generated in the spheroidization, and can be adjusted to include fine powders at the same time when adjusting the flaky graphite particle size, or can be added and mixed separately at an appropriate period.

[0486] In order to make the fine powder effectively adhere to the particle surface of the matrix material, it is preferred to enhance the adhesion between flaky graphite particles and flaky graphite particles, between flaky graphite particles and fine powder particles, and between fine powder particles and fine powder particles. Specific examples of the adhesion between particles include: van der Waals force and electrostatic attraction without interparticle inclusions, physical or chemical crosslinking force with interparticle inclusions, etc.

[0487] The smaller the van der Waals force is, the more [self-weight] < [adhesion] it is. Therefore, the smaller the average particle size (d50) of flaky graphite (raw carbon material) as a raw material for spheroidized graphite is, the greater the adhesion between particles is, and the easier it is for the fine powder to be attached to the base material and for the fine powder to be enclosed in the spheroidized particles, so it is preferred. The average particle size (d50) of flaky graphite is preferably 1 μm or more, more preferably 2 μm or more, and further preferably 3 μm or more, and preferably 80 μm or less, more preferably 50 μm or less, further preferably 35 μm or less, particularly preferably 20 μm or less, especially preferably 10 μm or less, and most preferably 8 μm or less.

[0488] Examples of the physical or chemical crosslinking force between particles with inclusions between them include the physical or chemical crosslinking force between liquid inclusions and solid inclusions. Examples of the chemical crosslinking force include the crosslinking force when covalent bonds, ionic bonds, hydrogen bonds, etc. are formed between particles and inclusions between them through chemical reactions, sintering, mechanical and chemical effects, etc.

[0489] (Fourth step) Step of removing part of the granulating agent and the organic solvent

[0490] In the present invention, it is preferred to include the aforementioned step of removing a portion of the granulating agent and the organic solvent. Examples of methods for removing a portion of the granulating agent and the organic solvent include a method of washing with a solvent, and a method of volatilizing and decomposing a portion of the granulating agent and the organic solvent by applying heat under normal pressure or reduced pressure.

[0491] The heat treatment temperature at this time is preferably 60°C or higher, more preferably 100°C or higher, further preferably 200°C or higher, particularly preferably 300°C or higher, and preferably 1500°C or lower, more preferably 1000°C or lower, further preferably 800°C or lower, and most preferably near the boiling point of the granulated material. When the heat treatment temperature is within the above range, the granulating agent can be fully volatilized, decomposed and removed, thereby reducing production costs, and the molding state during molding treatment also becomes good, so it is preferred.

[0492] The heat treatment time is preferably 0.5 to 48 hours, more preferably 1 to 40 hours, further preferably 2 to 30 hours, and particularly preferably 3 to 24 hours. When the heat treatment time is within the above range, the granulating agent can be fully volatilized and decomposed to be removed, thereby improving productivity.

[0493] The atmosphere for heat treatment may be an active atmosphere such as air atmosphere, or an inactive atmosphere such as nitrogen atmosphere or argon atmosphere. There is no particular limitation when heat treatment is performed at 200°C to 300°C, but when heat treatment is performed at above 300°C, from the viewpoint of preventing oxidation of the graphite surface, an inactive atmosphere such as nitrogen atmosphere or argon atmosphere is preferred.

[0494] (Fifth step) A step of adding a carbon material having a lower crystallinity than the raw carbon material to the granulated carbon material

[0495] In the present invention, there may be a step of further adding a carbon material having lower crystallinity than the raw carbon material to the granulated carbon material. According to this step, graphite having amorphous carbon material on at least a portion of the surface can be obtained, so that the negative electrode for a non-aqueous secondary battery using the graphite has less side reactions with the electrolyte, and a negative electrode material for a non-aqueous secondary battery with high capacity, low-temperature input-output characteristics, and excellent high-temperature storage characteristics can be obtained.

[0496] The treatment of adding an attached (compounded) amorphous carbon material to the granulated carbon material is a treatment of mixing an organic compound as an amorphous carbon material with the granulated carbon material, and heating the mixture under a non-oxidizing atmosphere, preferably under the flow of nitrogen, argon, carbon dioxide, etc., so as to carbonize the organic compound into an amorphous state. As specific organic compounds that become amorphous carbon materials, petroleum-based and coal-based heavy oils, tars, and asphalts can be used. Specifically, various carbon-based heavy oils such as soft or hard coal tar pitches, coal liquefied oils, petroleum-based heavy oils such as atmospheric or vacuum distillation residues of crude oil, and cracking-based heavy oils produced by cracking naphtha as a by-product of ethylene production can be used.

[0497] In addition, examples include heat-treated asphalts such as ethylene tar pitch obtained by heat-treating cracking heavy oil, FCC decant oil, and Ashland pitch. In addition, examples include vinyl polymers such as polyvinyl chloride, polyvinyl acetate, polyvinyl butyral, and polyvinyl alcohol, substituted phenolic resins such as 3-methylphenolic resin and 3,5-dimethylphenolic resin, aromatic hydrocarbons such as acenaphthene, decacyclic ene, and anthracene, nitrogen ring compounds such as phenazine and acridine, and sulfur ring compounds such as thiophene. In addition, examples of organic compounds that are carbonized in a solid phase include natural polymers such as cellulose, chain vinyl resins such as polyvinylidene chloride and polyacrylonitrile, and aromatic polymers such as polyphenylene; thermosetting resins such as furfuryl alcohol resin, phenolic resin, and polyimide resin; and thermosetting resin raw materials such as furfuryl alcohol. Among these, petroleum-based and coal-based heavy oils, tars, and asphalts that are soft carbons with less Qi and Ti and completely soften when the temperature is raised during sintering are preferred. This is because they are less likely to generate micropores when they are amorphous carbons and can more effectively reduce micropores of 1nm to 4nm.

[0498] As a method for mixing a granulated carbon material with an organic compound that becomes an amorphous carbon substance, for example, there can be cited: a method of mixing a raw carbon material and a granulating agent using a mixer or a kneader, a method of mixing a granulating agent obtained by dissolving an organic compound in a low-viscosity diluent solvent (organic solvent) with a raw carbon material, and then removing the diluent solvent (organic solvent), etc. Among these methods, a method of mixing a raw carbon material and a granulating agent using a mixer or a kneader is preferred, because in this method, the more components that become carbon substances in the organic compound, the more effectively pores of 1 nm to 4 nm can be reduced.

[0499] In addition, when the granulated carbon material is mixed with an organic compound as a carbon substance, the viscosity of the organic compound as the carbon substance is preferably 1 cP or more and 1000 cP or less, more preferably 5 cP or more and 800 cP or less, further preferably 10 cP or more and 600 cP or less, and particularly preferably 20 cP or more and 500 cP or less. When the viscosity is within the above range, the organic compound as a carbon substance enters into the micropores of 1 nm to 4 nm of the granulated carbon material and is formed into amorphous carbon by sintering, thereby reducing the micropores, thereby being able to manufacture a negative electrode material with excellent low-temperature input-output characteristics and high-temperature storage characteristics, and therefore is preferred.

[0500] The mixing temperature when mixing the granulated carbon material with the organic compound as the carbon substance is usually above the softening point of the organic compound as the carbon substance, preferably a temperature higher than the softening point by 10°C, more preferably a temperature higher than the softening point by 20°C, further preferably a temperature higher than 30°C, and particularly preferably a temperature higher than 50°C, and is usually carried out at 450°C or less, preferably 250°C or less. When the heating temperature is too low, the viscosity of the organic compound as the carbon substance precursor increases, mixing becomes difficult, and there is a concern that the coating morphology becomes uneven. When the heating temperature is too high, the viscosity of the mixed system becomes high due to the volatilization and polycondensation of the organic compound as the carbon substance precursor, mixing becomes difficult, and there is a concern that the coating morphology becomes uneven.

[0501] The heating temperature (calcination temperature) varies depending on the organic compound used to prepare the mixture, and is usually heated to 500°C or more, preferably heated to 600°C or more, and more preferably heated to 700°C or more to add and adhere amorphous carbon to at least a portion of the graphite surface. The upper limit of the heating temperature is the temperature at which the carbonized product of the organic compound does not reach a crystalline structure equivalent to the crystalline structure of the flaky graphite in the mixture, and the upper limit of the heating temperature is usually 2000°C, preferably 1800°C, more preferably 1700°C, and further preferably 1600°C.

[0502] After the above treatment, the carbon material composite carbon material can be prepared by appropriately combining crushing, pulverizing and classification. In addition, the shape is arbitrary, but the average particle size is usually 2 to 50 μm, preferably 5 to 35 μm, and particularly preferably 8 to 30 μm.

[0503] In addition, if known techniques are used, known techniques that can be controlled within the required range can be used. That is, spheroidized graphite particles can be manufactured by spheroidizing using known techniques. For example, a device that repeatedly imparts mechanical effects such as compression, friction, and shearing force to particles, which are mainly composed of impact force and also include the interaction of particles, can be cited. Specifically, the following device is preferably used: a rotor having a plurality of blades is provided inside the housing, and the carbon material introduced into the interior is imparted with mechanical effects such as impact, compression, friction, and shearing force by rotating the rotor at high speed, thereby performing a surface treatment device. In addition, it is preferred to have a device that repeatedly imparts mechanical effects by circulating graphite particles. As a specific device, for example: a hybrid system (Hybridization System) (manufactured by Nara Machinery Manufacturing Co., Ltd.), Kryptron (manufactured by Earthtechnica), CF mill (manufactured by Ube Industries, Ltd.), mechanical melting system (manufactured by Hosokawa micron), Theta Composer (manufactured by Tokushou Works Co., Ltd.), etc. Among these, the mixing system manufactured by Nara Machinery Manufacturing Co., Ltd. is preferred. For example, when the aforementioned device is used for treatment, the circumferential speed of the rotating rotor is not particularly limited, and is preferably set to 30m / sec to 100m / sec, more preferably 40m / sec to 100m / sec, and further preferably 50m / sec to 100m / sec. In addition, although the treatment can be carried out by passing only the carbon material, it is preferably circulated or retained in the device for more than 30 seconds for treatment, and more preferably circulated or retained in the device for more than 1 minute for treatment.

[0504] <C2-2. Pressurization treatment of graphite>

[0505] The manufacture of the negative electrode material of one embodiment of the present invention preferably includes a step of pressurizing graphite. There are no particular restrictions on the method of pressurizing graphite as long as it is a method that can be pressurized, and examples thereof include: adding the raw graphite to a container such as a rubber type, isotropic hydrostatic pressurization using water as a pressurizing medium, and isotropic pressurization based on air pressure using a gas such as air as a pressurizing medium. In addition, the raw graphite can also be filled into a mold and pressurized in a constant direction by unidirectional pressurization.

[0506] The pressurization may be performed in any of steps 1 to 5 of producing the spheroidized graphite, but is preferably performed between steps 4 and 5 because the pressurization is performed in a state where the excess granulated material is removed, and the pressure can be applied more efficiently.

[0507] The pressure of the pressurized medium used in the pressurization treatment of graphite is usually preferably 100 MPa or more, more preferably 150 MPa or more, and further preferably 200 MPa or more, and its upper limit is usually 400 MPa or less, preferably 300 MPa or less. When it is below the above lower limit, the control of the micropores based on the molding becomes insufficient, and the particle internal pore volume per unit coverage is difficult to reach the preferred range. When it is above the above upper limit, the device becomes too large, and the mass production is excessively damaged. From such a point of view, it is not preferred.

[0508] The sample after the molding treatment is preferably subjected to a pulverization, crushing, and pulverization treatment to the same or less than the particle size before the treatment. Wherein, as a method of pulverization, a known device can be used. In the case of a large molded body, it is preferably implemented through a process such as a coarse pulverization process, an intermediate pulverization process, and a pulverization process. As a device for a coarse pulverization process, for example: a jaw crusher, an impact crusher, a cone crusher, a rotary compound machine, etc. can be cited, as an intermediate pulverizer, a roller crusher, a directional mill, a hammer mill, etc. can be cited, and as a fine pulverization device, a turbine mill, a Cryptron, a pin crusher, a ball mill, a vibration mill, a pulverizer, etc. can be cited. After the above-mentioned pulverization, a classification treatment is implemented, and the pulverization is pulverized to the same or less than the raw material. In the case of a larger particle size than before the treatment, the particles show adhesion and aggregation by the molding treatment, and cannot be well coated in this part when the amorphous coating is applied, so it is not preferred. On the other hand, in the case of a particle size significantly smaller than that before the treatment, the spherical graphite is pulverized to cause SA to increase, so it is not preferred.

[0509] (Cumulative pore volume)

[0510] The graphite used in the raw material of the negative electrode material of one embodiment of the present invention preferably has more than 2 peaks in the micropore distribution measured using mercury intrusion method (mercury porosimetry), and for the cumulative pore volume in the range below the minimum value, the value measured using mercury intrusion method (mercury porosimetry) is usually 0.15mL / g or less, preferably 0.08mL / g or less, more preferably 0.070mL / g or less, further preferably 0.060mL / g or less, and particularly preferably 0.050mL / g or less. In the case where the cumulative pore volume is greater than the above range, it means that the intra-particle void is large, and it is difficult to effectively reduce the pore volume when coated with amorphous, so it is not preferred.

[0511] (The smaller side of the peak)

[0512] The graphite used in the raw material of the negative electrode material of one embodiment of the present invention preferably has two or more peaks in the micropore distribution measured using mercury intrusion method (mercury porosimetry), and the peak top of the peak on the side with a smaller micropore diameter is measured using mercury intrusion method (mercury porosimetry), usually 500nm or less, preferably 400nm or less, more preferably 300nm or less, further preferably 200nm or less, and particularly preferably 100nm or less. When the intra-particle void is greater than the above range, at the moment of spheroidization, the flaky graphite as the raw material is far from each other, and there is a large void, so it cannot be effectively bonded when coated with amorphous, so it is not preferred.

[0513] (Roundness)

[0514] The graphite used in the negative electrode material raw material of one embodiment of the present invention has a circularity obtained by flow particle image analysis of preferably 0.88 or more, more preferably 0.90 or more, more preferably 0.91 or more, particularly preferably 0.92 or more, and most preferably 0.93 or more. If it is such a stone mill with high circularity, the curvature of the Li ion diffusion of the negative electrode material manufactured using it decreases and the electrolyte movement in the interparticle gap becomes smooth, thereby improving the rapid charge and discharge characteristics, so it is preferred. On the other hand, the theoretical upper limit of the circularity is 1, so it is usually less than 1, preferably less than 0.99, more preferably less than 0.98, and more preferably less than 0.97. From the viewpoint of ensuring the contact between the obtained negative electrode materials and improving the cycle characteristics, it is preferably below the above upper limit.

[0515] The circularity is obtained by measuring the particle size distribution based on the equivalent circle diameter using a flow particle image analyzer (FPIA-2000 manufactured by Toa Medical Electronics Co., Ltd.) and calculating the average circularity. The circularity is defined by the following formula, and a circularity of 1 is a theoretical true sphere.

[0516] [Circularity] = [Circumference of an equivalent circle with the same area as the particle's projected shape] / [Actual circumference of the particle's projected shape]

[0517] In the measurement of the circularity, ion exchange water was used as a dispersion medium, and polyoxyethylene (20) monolaurate was used as a surfactant. The equivalent circle diameter refers to the diameter of a circle (equivalent circle) having the same projected area as the image of the particle photographed, and the circularity refers to the ratio obtained by taking the circumference of the equivalent circle as the numerator and the circumference of the projected image of the particle photographed as the denominator. The circularity of particles with an equivalent diameter of 10 to 40 μm was averaged and used as the circularity.

[0518] (Tap density)

[0519] The tap density of graphite is preferably 0.60 g / cm 3 More preferably, 0.70 g / cm 3 More preferably, 0.80 g / cm 3 More than, particularly preferably 0.855 / cm 3 More than, most preferably 0.90g / cm 3 On the other hand, it is usually 1.40 g / cm 3 Below, preferably 1.30 g / cm 3 Below, more preferably 1.20 g / cm 3 the following.

[0520] (Volume-based average particle size)

[0521] The volume-based average particle size (D50) of graphite is not particularly limited, but is usually 1 μm or more, preferably 3 μm or more, more preferably 5 μm or more, and is usually 50 μm or less, preferably 40 μm or less, more preferably 30 μm or less.

[0522] (BET specific surface area)

[0523] The BET specific surface area of ​​graphite is not particularly limited, but is usually 1.0 m 2 / g or more, preferably 1.5m 2 / g or more, more preferably 2.0m 2 / g or more, more preferably 3.0m 2 / g or more, particularly preferably 4.5m 2 / g or more, and most preferably 5.0m 2 / g or more, usually 30.0m 2 / g or less, preferably 20.0m 2 / g or less, more preferably 10.0 m 2 / g or less.

[0524] (Raman R1 value)

[0525] The Raman R1 value of graphite represented by the following formula α is not particularly limited, but is preferably 0.10 or more and 1.00 or less. In addition, the Raman R value is more preferably 0.15 or more, further preferably 0.20 or more, and particularly preferably 0.25 or more, and on the other hand, is more preferably 0.80 or less, and further preferably 0.60 or less.

[0526] Formula α:

[0527] Raman R1 value = (1360cm in Raman spectroscopy analysis -1 Nearby peaks P B Strength I B ) / (1580cm-1 Nearby peaks P A Strength I A )

[0528] <C2-3. Amorphous carbon composite of graphite>

[0529] The negative electrode material of one embodiment of the present invention includes graphite having at least one of an amorphous carbon material or a graphite material on at least a portion of the surface. Here, the amorphous carbon material refers to carbon whose interplanar spacing (d002) of the (002) plane based on the X-ray wide-angle diffraction method is generally 0.340nm or more, and the amorphous carbon material has the same meaning as the carbon material. On the other hand, the graphite material refers to graphite with (d002) less than 0.340nm. The amorphous carbon composite treatment is carried out by mixing graphite with an amorphous carbon precursor (raw material of the amorphous carbon material) and sintering. By performing amorphous carbon composite of graphite under suitable conditions, while achieving the aforementioned thermal characteristics, the pore volume is also easily controlled within the aforementioned range.

[0530] As amorphous carbon precursor, there is no particular limitation, and examples thereof include organic substances such as tar and pitch, aromatic hydrocarbons such as naphthalene, anthracene and its derivatives, phenolic resin, thermoplastic polymers such as polyvinyl alcohol, etc. These organic precursors can be used alone or in combination of two or more. Among these, from the viewpoint that the carbon structure is easily developed and can be coated with a small amount, tar, pitch, and aromatic hydrocarbons are preferred. In order to satisfy the aforementioned relationship between coverage and micropore amount, the residual carbon is preferably 50% or more, more preferably 60%, and particularly preferably 65% ​​or more. The higher the residual carbon rate, the more the foaming and volume reduction during the calcination treatment are suppressed, so that the micropores in the particles of the above-mentioned graphite can be efficiently buried, so it is preferred.

[0531] The amount of metal impurities contained in the amorphous carbon precursor of the present invention is defined as: the value obtained by dividing the total content of Fe, Al, Si, and Ca relative to the total weight of the amorphous carbon precursor by the residual carbon rate. It is preferably less than 1000 ppm by weight, more preferably less than 400 ppm by weight, further preferably less than 100 ppm by weight, particularly preferably less than 50 ppm by weight, and usually more than 0.1 ppm by weight. If the amount of metal impurities contained in the amorphous carbon precursor is within the above range, it is easy to satisfy the relationship between the aforementioned coverage and the amount of micropores, so it is preferred.

[0532] The quinoline insoluble component (Qi) contained in the amorphous carbon precursor is preferably 5% by weight or less, more preferably 2% by weight or less, further preferably 1% by weight or less, particularly preferably 0.5% by weight or less, and most preferably 0.1% by weight or less relative to the total weight of the amorphous carbon precursor. If the quinoline insoluble component (Qi) contained in the amorphous carbon precursor is within the above range, it is easy to satisfy the relationship between the aforementioned coverage and the amount of micropores, and therefore it is preferred.

[0533] After mixing graphite with an amorphous carbon precursor, calcination is performed. The temperature during calcination is preferably above 950°C, more preferably above 1000°C, further preferably above 1050°C, particularly preferably above 1100°C, and most preferably above 1150°C. On the other hand, it is preferably below 2000°C, more preferably below 1800°C, further preferably below 1600°C, and particularly preferably below 1500°C. In addition, the calcination time is preferably above 0.5 hours, more preferably above 1 hour, on the other hand, it is preferably below 1000 hours, more preferably below 500 hours, and further preferably below 100 hours. If the temperature and time during calcination are within the above range, it is easy to satisfy the relationship between the aforementioned coverage and the amount of micropores, so it is preferred.

[0534] The atmosphere during sintering is preferably an inert atmosphere. Specifically, there can be cited: a method of reducing the oxygen concentration by circulating an inert gas such as nitrogen or argon, a method of discharging oxygen outside the system by decompression treatment and restoring the pressure with nitrogen or argon, and a method of reducing the oxygen contained in the atmosphere in the furnace by filling sacrificial materials such as coke powder around the product. The oxygen concentration in the system can be controlled by the flow rate of the inert gas, the flow time, the degree of decompression treatment, the filling conditions of the sacrificial material, etc. The oxygen concentration (volume concentration) is preferably less than 3%, more preferably less than 1%, further preferably less than 1000ppm, particularly preferably less than 500ppm, and most preferably less than 100ppm. If the above range is exceeded, the development of the carbon structure of the amorphous carbon material is hindered, and there is a tendency for the amorphous itself to produce micropores and it is difficult to satisfy the aforementioned relationship between the coverage and the amount of micropores.

[0535] The mixing ratio of the amorphous carbon precursor when mixing the amorphous carbon precursor in the graphite should be appropriately selected based on the composition of the target composite particles. For the amount of the amorphous carbon precursor relative to the graphite, the weight ratio ([weight of amorphous carbon] / [weight of graphite]]×100) as its carbon residue (amorphous carbon) is usually 0.01% or more, preferably 0.1% or more, more preferably 0.5% or more, further preferably 1% or more, particularly preferably 2% or more, and most preferably 3% or more. On the other hand, it is preferably 30% or less, more preferably 20% or less, further preferably 15% or less, and particularly preferably 10% or less. If the weight ratio is within the above range, the battery has a high capacity and Li ions are easily inserted / detached, so the low temperature input and output characteristics, rapid charge and discharge characteristics, and cycle characteristics are excellent, which is preferred from this point of view.

[0536] <Graphite-based composite materials>

[0537] The negative electrode material of one embodiment of the present invention includes graphite having at least one of an amorphous carbon material and a graphite material on at least a portion of the surface. The graphitization treatment is performed by mixing graphite with an organic compound (raw material of the graphite material) and calcining the mixture.

[0538] The method for manufacturing the negative electrode material of graphite having a graphite substance on at least a portion of the surface is not particularly limited, and the negative electrode material of graphite having a graphite substance on at least a portion of the surface can be preferably manufactured by the following process, wherein the above-mentioned graphite (also referred to as "raw graphite") is crushed after being subjected to pressure treatment, and then mixed with an organic compound for obtaining a graphite substance-coated portion, and the obtained mixture is graphitized and pulverized; or, the raw carbon material is mixed with an organic compound for obtaining a graphite substance-coated portion and subjected to pressure treatment, and then the obtained mixture is graphitized and pulverized. The latter with fewer pulverization steps is more preferred.

[0539] Specific examples of organic compounds include: easily graphitized organic compounds exemplified by coal-based heavy oils such as impregnated asphalt, coal tar pitch, coal liquefied oil, straight-run heavy oils such as asphaltene, and petroleum-based heavy oils such as decomposition heavy oils such as ethylene heavy tail tar, aromatic hydrocarbons, nitrogen-containing cyclic compounds, sulfur-containing cyclic compounds, polyphenylene, polyvinyl chloride, polyvinyl alcohol, polyacrylonitrile, polyvinyl butyral, natural furfuryl alcohol polymer, polyphenylene sulfide, polyphenylene ether, resin, phenolic resin, imide resin, etc. Among them, preferably, an easily graphitized organic compound that can be graphitized or carbonized by sintering.

[0540] The step of mixing the raw material graphite with the organic compound / the step of performing a pressure treatment can be performed in the same manner as in the amorphous carbon composite of graphite.

[0541] · Process of calcining the mixture

[0542] Specifically, the process comprises heating the mixture in a non-oxidizing atmosphere, preferably in a flow of nitrogen, argon, carbon dioxide, etc., to graphitize the organic compound, thereby producing a composite negative electrode material for a non-aqueous secondary battery including graphite having a graphite substance on at least a portion of its surface.

[0543] The calcination temperature varies depending on the organic compound used to prepare the mixture. In the case of obtaining a non-aqueous secondary battery negative electrode material in which a graphite substance is composited, the temperature at which the organic compound is graphitized or a temperature above it is sufficient. Specifically, it is usually heated to 2000°C or more, preferably heated to 2500°C or more, and more preferably heated to 2700°C or more to fully carbonize it. The upper limit of the heating temperature is the temperature at which the carbonized product of the organic compound does not reach a crystalline structure equivalent to the crystalline structure of the carbon material in the mixture, which is usually 3300°C or less, preferably 3100°C or less, and more preferably 3000°C or less.

[0544] In the sintering treatment conditions, the thermal history temperature conditions, the heating rate, the cooling rate, the heat treatment time, etc. can be suitably set. In addition, after heat treatment in a relatively low temperature region, the temperature can be raised to a given temperature. It should be noted that the reactor used in this process can be a batch type or a continuous type, and can be one or more.

[0545] The furnace used for calcination is not particularly limited as long as it meets the above requirements. For example, a shuttle furnace, a tunnel furnace, a Reedhammer furnace, a rotary kiln, a reaction tank such as an autoclave, a coker (a heat treatment tank for coke production), a Tanman furnace, an Acheson furnace can be used. The heating method can be a high-frequency induction heating furnace, direct resistance heating, indirect resistance heating, direct combustion heating, radiation heating, etc. Stirring can be performed as needed during the treatment.

[0546] The composite carbon material that has undergone the above steps may be subjected to powder processing such as re-crushing, crushing, classification, etc. as necessary to obtain a negative electrode material for a non-aqueous secondary battery.

[0547] The device used for pulverizing and crushing is not particularly limited. For example, as a coarse pulverizer, a shear mill, a jaw crusher, an impact crusher, a cone crusher, etc. can be listed. As an intermediate pulverizer, a roller crusher, a hammer mill, etc. can be listed. As a fine pulverizer, a ball mill, a vibration mill, a pin mill, a stirring mill, a jet mill, etc. can be listed.

[0548] There are no particular restrictions on the device used for the classification process. For example, in the case of dry screening, a rotary screen, a shaking screen, a rotating screen, a vibrating screen, etc. can be used. In the case of dry airflow classification, a gravity classifier, an inertial force classifier, a centrifugal force classifier (granulator, cyclone separator), etc. can be used. In addition, in the case of wet screening, a mechanical wet classifier, a hydraulic classifier, a sedimentation classifier, a centrifugal wet classifier, etc. can be used.

[0549] The mixing ratio of the organic compound when mixing the organic compound in the graphite should be appropriately selected based on the composition of the target composite particles. For the amount of the organic compound relative to the graphite, the weight ratio ([weight of the graphite material] / [graphite with graphite material]]×100) as its carbon residue (graphite) is usually 0.01% or more, preferably 0.1% or more, more preferably 0.5% or more, further preferably 1% or more, particularly preferably 2% or more, and most preferably 3% or more. On the other hand, it is preferably 30% or less, more preferably 20% or less, further preferably 15% or less, and particularly preferably 10% or less. If the weight ratio is within the above range, the battery has a high capacity and Li ions are easily inserted / detached, so the low-temperature input and output characteristics, rapid charge and discharge characteristics, and cycle characteristics are excellent, which is preferred from this point of view.

[0550] <C2-4. Other treatments>

[0551] In order to produce the negative electrode material according to one embodiment of the present invention, the composite particles obtained by the above-mentioned production method may be subjected to a separate pulverization treatment.

[0552] As the coarse pulverizer used for the pulverization treatment, jaw crusher, impact crusher, cone crusher, etc. can be listed, as the intermediate pulverizer, roll crusher, directional mill, hammer mill, etc. can be listed, as the fine pulverization equipment, turbine mill, Cryptron, ball mill, vibration mill, stirring mill, jet mill, etc. can be listed. Among these, turbine mill and Cryptron are preferred from the viewpoint of short pulverization time and processing speed.

[0553] In order to produce the negative electrode material of one embodiment of the present invention, the composite particles obtained by the above-mentioned production method can be subjected to particle size classification. As the classification conditions, the classification can be carried out using an apparatus with an opening of usually 53 μm or less, preferably 45 μm or less, and more preferably 38 μm or less.

[0554] There are no particular restrictions on the device used for the classification process. For example, in the case of dry screening, a rotary screen, a shaking screen, a rotating screen, a vibrating screen, etc. can be used; in the case of dry airflow classification, a gravity classifier, an inertial force classifier, a centrifugal force classifier (granulator, cyclone separator), etc. can be used; in the case of wet screening, a mechanical wet classifier, a hydraulic classifier, a sedimentation classifier, a centrifugal wet classifier, etc. can be used.

[0555] [C3. Negative electrode for non-aqueous secondary battery]

[0556] A negative electrode for a non-aqueous secondary battery according to an embodiment of the present invention (hereinafter sometimes referred to as "the negative electrode of the present invention") comprises: a current collector and an active material layer formed on the current collector, wherein the active material layer contains the negative electrode material according to an embodiment of the present invention described above. The negative electrode for a non-aqueous secondary battery according to this embodiment may be the same as the first embodiment except for the active material layer.

[0557] When the negative electrode is prepared using the negative electrode material, a binder resin is mixed with the negative electrode material in an aqueous or organic medium to prepare a slurry, and a thickener is added thereto as necessary, and then the slurry is applied to a current collector and dried.

[0558] As the binder resin, it is preferred to use a resin that is stable to the non-aqueous electrolyte and non-water-soluble. For example, rubber-like polymers such as styrene-butadiene rubber, isoprene rubber, and ethylene-propylene rubber; synthetic resins such as polyethylene, polypropylene, polyethylene terephthalate, polyimide, polyacrylic acid, and aromatic polyamide; thermoplastic elastomers such as styrene-butadiene-styrene block copolymers or their hydrogenated products, styrene-ethylene-butadiene, styrene copolymers, styrene-isoprene and styrene block copolymers and their hydrogenates; soft resin-like polymers such as syndiotactic-1,2-polybutadiene, ethylene-vinyl acetate copolymers, and copolymers of ethylene and α-olefins with 3 to 12 carbon atoms; fluorinated polymers such as tetrafluoroethylene-ethylene copolymers, polyvinylidene fluoride, polypentafluoropropylene, and polyhexafluoropropylene. As organic media, for example, N-methylpyrrolidone and dimethylformamide can be used.

[0559] Relative to 100 parts by weight of the negative electrode material, 0.1 parts by weight or more, preferably 0.2 parts by weight or more of the binding resin is generally used. By making the amount of the binding resin used 0.1 parts by weight or more relative to 100 parts by weight of the negative electrode material, the binding force between the negative electrode materials and the binding force between the negative electrode materials and the collector become sufficient, and the reduction in battery capacity and the deterioration of cycle characteristics caused by the stripping of the negative electrode material from the negative electrode can be prevented.

[0560] In addition, the amount of the binder resin used is preferably 10 parts by weight or less, more preferably 7 parts by weight or less relative to 100 parts by weight of the negative electrode material. By making the amount of the binder resin used less than 10 parts by weight relative to 100 parts by weight of the negative electrode material, it is possible to prevent the reduction of the negative electrode capacity and to prevent the entry and exit of alkali metal ions such as lithium ions relative to the negative electrode material from being hindered.

[0561] As the thickener added to the slurry, for example, water-soluble celluloses such as carboxymethyl cellulose, methyl cellulose, hydroxyethyl cellulose and hydroxypropyl cellulose, polyvinyl alcohol and polyethylene glycol, etc. are listed. Among these, carboxymethyl cellulose is preferred. The thickener is preferably used in an amount of usually 0.1 to 10 parts by weight, particularly 0.2 to 7 parts by weight, relative to 100 parts by weight of the negative electrode material.

[0562] As the negative electrode current collector, copper, copper alloy, stainless steel, nickel, titanium, carbon, etc., which are currently known to be applicable to this purpose, can be used. The current collector is usually in the form of a sheet, but a material having irregularities on the surface, a mesh, a punched metal, etc. are also preferably used.

[0563] After applying the slurry of the negative electrode material and the binder resin on the collector and drying it, it is preferably pressed to increase the density of the active material layer formed on the collector, thereby increasing the battery capacity per unit volume of the negative electrode active material layer. The density of the active material layer is preferably 1.2 to 1.8 g / cm 3 The range is more preferably 1.3 to 1.6 g / cm 3 By making the density of the active material layer above the above lower limit, it is possible to prevent the battery capacity from decreasing due to an increase in the electrode thickness. In addition, by making the density of the active material layer below the above upper limit, the amount of electrolyte retained in the voids decreases due to a decrease in the voids between particles in the electrode, and it is possible to prevent the mobility of alkali metal ions such as lithium ions from decreasing, thereby preventing the rapid charge and discharge characteristics from decreasing.

[0564] [C3. Non-aqueous secondary battery]

[0565] The non-aqueous secondary battery of one embodiment of the present invention is a non-aqueous secondary battery having a positive electrode, a negative electrode, and an electrolyte, wherein the negative electrode used is the negative electrode of one embodiment of the present invention. In particular, the positive electrode and the negative electrode used in the non-aqueous secondary battery of one embodiment of the present invention are usually preferably positive electrodes and negative electrodes capable of absorbing and releasing Li ions, and the non-aqueous secondary battery of one embodiment of the present invention is preferably a lithium ion secondary battery.

[0566] The non-aqueous secondary battery of one embodiment of the present invention can be manufactured according to a conventional method except that the negative electrode of one embodiment of the present invention is used. In particular, the non-aqueous secondary battery of one embodiment of the present invention is preferably designed to have a value of [capacity of the negative electrode] / [capacity of the positive electrode] of 1.01 to 1.5, and more preferably 1.2 to 1.4.

[0567] [C3-1. Positive electrode]

[0568] As a positive electrode material of a non-aqueous secondary battery as an embodiment of the present invention, for example, lithium transition metal composite oxides such as lithium cobalt composite oxide represented by LiCoO2, lithium nickel composite oxide represented by LiNiO2, lithium manganese composite oxide represented by LiMnO2 and LiMn2O4, transition metal oxides such as manganese dioxide, and mixtures of these composite oxides can be used. Furthermore, TiS2, FeS2, Nb3S4, Mo3S4, CoS2, V2O5, CrO3, V3O3, FeO2, GeO2 and LiNi can be used. 0.33 Mn 0.33 Co 0.33 O2, LiFePO4, etc.

[0569] The positive electrode can be made by slurrying the material with the binding resin in the above-mentioned positive electrode material with an appropriate solvent and coating it on the collector and drying it. It should be noted that in the slurry, it is preferred to contain conductive materials such as acetylene black and Ketjen black. In addition, a thickener may also be contained as needed. It should be noted that as a binding material and a thickener, those known for their use can be used, for example, those exemplified as for the manufacture of the negative electrode can be used.

[0570] The amount of the conductive material is preferably 0.5 to 20 parts by weight, more preferably 1 to 15 parts by weight, relative to 100 parts by weight of the positive electrode material. In addition, the amount of the thickener is preferably 0.2 to 10 parts by weight, more preferably 0.5 to 7 parts by weight, relative to 100 parts by weight of the positive electrode material. In addition, with respect to the amount of the binder resin relative to 100 parts by weight of the positive electrode material, when the binder resin is slurried with water, it is preferably 0.2 to 10 parts by weight, more preferably 0.5 to 7 parts by weight. On the other hand, when the binder resin is slurried with an organic solvent such as N-methylpyrrolidone that dissolves the binder resin, it is preferably 0.5 to 20 parts by weight, more preferably 1 to 15 parts by weight.

[0571] Examples of the positive electrode current collector include aluminum, titanium, zirconium, hafnium, niobium, tantalum, and alloys thereof. Among these, aluminum, titanium, tantalum, and alloys thereof are preferred, and aluminum and alloys thereof are most preferred.

[0572] [C3-2. Electrolyte]

[0573] As the electrolyte solution, a solution prepared by dissolving various lithium salts in a conventionally known non-aqueous solvent can be used.

[0574] As the non-aqueous solvent, cyclic carbonates such as ethylene carbonate, fluoroethylene carbonate, propylene carbonate, butylene carbonate and vinylene carbonate can be used; chain carbonates such as dimethyl carbonate, ethyl methyl carbonate and diethyl carbonate; cyclic esters such as γ-butyrolactone; cyclic ethers such as crown ethers, 2-methyltetrahydrofuran, tetrahydrofuran, 1,2-dimethyltetrahydrofuran and 1,3-dioxolane; chain ethers such as 1,2-dimethoxyethane, etc. can be used. Usually, two or more of these solvents can be mixed and used. Among these, cyclic carbonates and chain carbonates are preferably used, or other solvents are further mixed therein and used.

[0575] Compounds such as vinylene carbonate, vinylethylene carbonate, succinic anhydride, maleic anhydride, propane sultone and diethyl sulfone, difluorophosphates such as lithium difluorophosphate, etc. may be added to the electrolyte. Furthermore, overcharge inhibitors such as diphenyl ether and cyclohexylbenzene may be added.

[0576] Examples of electrolytes dissolved in non-aqueous solvents include LiClO4, LiPF6, LiBF4, LiCF3SO3, LiN(CF3SO2)2, LiN(CF3CF2SO2)2, LiN(CF3SO2)(C4F9SO2), and LiC(CF3SO2)3. The concentration of the electrolyte in the electrolyte solution is usually 0.5 mol / L to 2 mol / L, preferably 0.6 mol / L to 1.5 mol / L.

[0577] [C3-3. Partition]

[0578] In the non-aqueous secondary battery of one embodiment of the present invention, a separator is preferably used, and the separator is interposed between the positive electrode and the negative electrode. As such a separator, a porous sheet or nonwoven fabric of polyolefin such as polyethylene or polypropylene is preferably used.

[0579] Example

[0580] [Experiment A]

[0581] Hereinafter, the content of the present invention will be described in more detail by way of examples, but the present invention is not limited to the following examples as long as it does not exceed its purport. It should be noted that the values ​​of various manufacturing conditions and evaluation results in the following examples have the meaning of preferred values ​​as the upper or lower limits in the embodiments of the present invention, and the preferred range may also be the range specified by combining the values ​​of the aforementioned upper or lower limits with the values ​​of the following examples, or by combining the values ​​of the examples with each other.

[0582] <Production of negative electrode sheet>

[0583] Using the negative electrode material prepared under the conditions described below as the negative electrode active material, a negative electrode layer having an active material layer density of 1.6±0.03 g / cm 3 (Examples and Comparative Examples in Table 1), and 1.5±0.03 g / cm 3 (Examples and Comparative Examples in Table 2) of the active material layer of the electrode plate. Specifically, 50.00±0.02g of 1 wt% carboxymethyl cellulose sodium salt aqueous solution (converted to 0.500g of solid content) and 1.00±0.05g of styrene-butadiene rubber aqueous dispersion with a weight average molecular weight of 270,000 (converted to 0.5g of solid content) were stirred for 5 minutes in a Keyence mixer and degassed for 30 seconds to obtain a slurry.

[0584] The slurry was applied to a copper foil with a thickness of 10 μm as a current collector in a width of 10 cm using a die coater so that the negative electrode material adhered to 10.00±0.2 mg / cm 2 After drying, the mixture was cut into pieces with a width of 5 cm and rolled using a roller with a diameter of 20 cm. The density of the active material layer was adjusted to 1.5 ± 0.03 g / cm 3 and 1.60±0.03g / cm 3 , and obtained their respective electrode sheets.

[0585] <Production of positive electrode sheet>

[0586] The positive electrode was prepared as follows. First, 85 wt% of lithium nickel-manganese-cobalt oxide (LiNiMnCoO2) as the positive electrode active material, 10 wt% of acetylene black as the conductive material, and 5 wt% of polyvinylidene fluoride (PVdF) as the binder were mixed in N-methylpyrrolidone solvent to obtain a slurry. The slurry was coated on a 15 μm thick aluminum foil as the collector using a blade coater so that the positive electrode material adhered to 22.5 ± 0.2 mg / cm 2 The positive electrode was dried at 130°C and rolled to adjust the positive electrode density to 2.60±0.05 g / cm 3 , and an electrode sheet was obtained.

[0587] <Method for producing non-aqueous secondary battery (laminated battery)>

[0588] The 10.0±0.3 mg / cm 2 The density of the negative electrode material and the active material layer is 1.6±0.03g / cm 3 (Examples and Comparative Examples in Table 1), 1.5±0.03 g / cm3 The negative electrode sheet, positive electrode sheet, and polyethylene separator of (Examples and Comparative Examples of Table 2) were stacked in the order of negative electrode, separator, and positive electrode. The battery element obtained above was wrapped in a cylindrical aluminum laminate film, and an electrolyte was injected. The electrolyte was obtained by dissolving LiPF6 at 1 mol / L in a mixed solvent of ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) (volume ratio = 3:3:4), and then vacuum sealed to make sheet-shaped non-aqueous secondary batteries. Furthermore, in order to improve the adhesion between the electrodes, the sheet-shaped battery was clamped with a glass plate and pressurized.

[0589] <Method for producing non-aqueous secondary battery (coin-type battery)>

[0590] The 10.0±0.3 mg / cm 2 The density of the negative electrode material and the active material layer is 1.6±0.03g / cm 3 (Examples and Comparative Examples in Table 1), 1.5±0.03 g / cm 3 The electrode sheet of (Examples and Comparative Examples in Table 2) was punched into a disc with a diameter of 12.5 mm as the negative electrode, and the lithium metal foil was punched into a disc with a diameter of 14 mm as the counter electrode. A separator (made of porous polyethylene film) impregnated with an electrolyte was placed between the two electrodes, and 2016 coin-shaped batteries were made respectively. The electrolyte was obtained by dissolving LiPF6 at 1 mol / L in a mixed solvent of ethylene carbonate and ethyl methyl carbonate (volume ratio = 3:7).

[0591] <Discharge capacity (mAh / g), initial efficiency (%)>

[0592] Using the non-aqueous secondary battery (2016 coin-type battery) produced by the above method, the capacity of the battery during charge and discharge was measured according to the following measurement method.

[0593] The lithium counter electrode was charged to 5 mV at a current density of 0.05 C, and then charged at a constant voltage of 5 mV until the current density reached 0.005 C. After lithium was doped into the negative electrode, the lithium counter electrode was discharged to 1.5 V at a current density of 0.1 C. The discharge capacity at this time was taken as the discharge capacity of this material, and the ratio of the discharge capacity to the charge capacity (discharge capacity / charge capacity × 100) was taken as the initial efficiency (%).

[0594] <Rapid discharge characteristics(%)>

[0595] Using the laminated nonaqueous secondary battery produced by the above-described method for producing a nonaqueous secondary battery, rapid discharge characteristics were measured in accordance with the following measurement method.

[0596] For non-aqueous secondary batteries that have not undergone charge and discharge cycles, initial charge and discharge were performed at 25°C with a voltage range of 4.1V to 3.0V and a current value of 0.2C (the current value for discharging the rated capacity of the 1-hour rate discharge capacity in 1 hour is set to 1C, the same below) for 3 cycles, and with a voltage range of 4.2V to 3.0V and a current value of 0.2C (constant voltage charging was further implemented at 4.2V for 2.5 hours during charging) for 2 cycles. Furthermore, after constant current charging was performed at a current value of 0.2C until 4.2V, constant voltage charging was further implemented at 4.2V for 2.5 hours, and constant current discharge was performed at 3C until 3.0V. The ratio of the discharge capacity during 3C discharge to the discharge capacity during 0.2C discharge (the discharge capacity of the 5th cycle of the above-mentioned initial charge and discharge) (3C / 0.2C×100) was taken as the rapid discharge characteristic (%).

[0597] <Low temperature output characteristics>

[0598] Using the laminated nonaqueous secondary battery produced by the above-described method for producing a nonaqueous secondary battery, the low-temperature output characteristics were measured by the following measurement method.

[0599] For a non-aqueous secondary battery that has not undergone charge and discharge cycles, initial charge and discharge were performed at 25°C with a voltage range of 4.1V to 3.0V and a current value of 0.2C (the current value at which the rated capacity of the discharge capacity at a 1-hour rate is discharged in 1 hour is defined as 1C, the same below) for 3 cycles, and with a voltage range of 4.2V to 3.0V and a current value of 0.2C (constant voltage charging was further performed at 4.2V for 2.5 hours during charging) for 2 cycles. Furthermore, the battery was charged at a current value of 0.2C until SOC 50%, and then discharged at a constant current of 1 / 8C, 1 / 4C, 1 / 2C, 1.5C, and 2C for 2 seconds in a low temperature environment of -30°C. The battery voltage drop value after 2 seconds in the discharge under each condition was measured, and the current value I that could flow for 2 seconds when the upper limit voltage of the charge was 3V was calculated from these measured values. The value calculated by the formula 3×I(W) was used as the low temperature output characteristic of each battery. The low-temperature outputs in Table 1 show values ​​when Comparative Example A1 is taken as 100%, and the low-temperature outputs in Table 2 show values ​​when Comparative Example A4 is taken as 100%.

[0600] <High temperature storage characteristics(%)>

[0601] The high temperature storage characteristics were measured by the following measurement method using the laminated nonaqueous secondary battery produced by the above-mentioned nonaqueous secondary battery method.

[0602] For non-aqueous secondary batteries that have not undergone charge and discharge cycles, initial charge and discharge were performed at 25°C with a voltage range of 4.1V to 3.0V and a current value of 0.2C (the current value for discharging the rated capacity of the 1-hour rate discharge capacity in 1 hour is set to 1C, the same below) for 3 cycles, and with a voltage range of 4.2V to 3.0V and a current value of 0.2C (constant voltage charging was further implemented at 4.2V for 2.5 hours during charging) for 2 cycles. Furthermore, charging was performed at a current value of 0.2C until SOC 80%, and then storage treatment was performed at 60°C for 2 weeks. Then, after discharging at a current value of 0.2C, charging and discharging were further performed at a current value of 0.2C (constant voltage charging was further implemented at 4.2V for 2.5 hours during charging), and the discharge capacity at this time was referred to as the "discharge capacity after storage". Then, the ratio of the discharge capacity after storage to the discharge capacity at the fifth initial charge-discharge cycle (discharge capacity after storage / discharge capacity at the fifth initial charge-discharge cycle×100(%)) was evaluated as high-temperature storage characteristics (%).

[0603] (Example A1)

[0604] Spheroidized natural graphite (average particle size (d50) 16.2 μm, BET specific surface area (SA) 6.9 m) was prepared by spheroidizing flaky natural graphite with an average particle size (d50) of 100 μm. 2 / g, tap density 1.00g / cm 3 ) is filled into a rubber container and sealed, and isotropically pressurized at 200MPa to control the physical properties of the powder. The obtained molded product was crushed and classified. The obtained spheroidized graphite powder was mixed with tar adjusted to ash content <0.01%, metal impurity content 60ppm, and Qi <0.1% as an amorphous carbon precursor, and then decompressed to make the pressure in the furnace below 10torr, and the pressure was restored to atmospheric pressure with nitrogen. Nitrogen was further circulated to make the oxygen concentration in the furnace <100ppm, and a heat treatment of 1300°C was implemented. The obtained calcined product was crushed and classified to obtain a negative electrode material, which is a composite carbon material containing amorphous carbon material on the surface of graphite particles. The calcination yield confirmed that the weight ratio of spheroidized graphite particles and amorphous carbon in the obtained negative electrode material (composite carbon material) (spheroidized graphite particles: amorphous carbon) was 1:0.03. In addition, differential thermal analysis (DTA), Raman R 1 ~R 3The negative electrode material (composite carbon material) has various properties such as the Raman half-peak width (ΔνB), the average particle size (d50), the BET specific surface area (SA), the tap density, the cumulative pore volume, the interplanar spacing (d002), and the crystallite size (Lc). Furthermore, the negative electrode density of 1.6 g / cm was measured using the above-mentioned measurement method. 3 The battery characteristics such as discharge capacity, initial efficiency, rapid discharge characteristics, low temperature output characteristics, and high temperature storage characteristics of the battery are shown in Table 1.

[0605] (Example A2)

[0606] A negative electrode material was obtained in the same manner as in Example A1 except that the weight ratio of spheroidized graphite particles to amorphous carbon (spheroidized graphite particles: amorphous carbon) was 1:0.015. The results of the same measurements as in Example A1 are shown in Table 1.

[0607] (Comparative Example A1)

[0608] Except that isotropic pressurization treatment was not performed, nitrogen was circulated until the oxygen concentration in the furnace was less than

[0609] A negative electrode material was obtained by the same method as in Example A1 except that the concentration of MgO was 1000 ppm and heat treatment was performed at 1300° C. The same measurements as in Example A1 were performed and the results are shown in Table 1.

[0610] (Comparative Example A2)

[0611] A negative electrode material was obtained in the same manner as in Example A1 except that a heat treatment was performed at 900° C. in an inert gas. The same measurements as in Example A1 were performed and the results are shown in Table 1.

[0612] (Comparative Example A3)

[0613] A composite carbon material was obtained in the same manner as in Comparative Example A1 except that the heat treatment was performed at 900°C in an inert gas. The same measurements as in Example A1 were performed and the results are shown in Table 1.

[0614] (Reference Example A1)

[0615] Spheroidized natural graphite (average particle size (d50) 16.2 μm, SA 6.9 μm) prepared by spheroidizing flaky natural graphite with an average particle size (d50) of 100 μm was used as is. 2 / g, tap density 1.00g / cm 3 ), and the same measurements as in Example A1 were carried out, and the results are shown in Table 1.

[0616] (Example A3)

[0617] The flaky natural graphite with an average particle size (d50) of 100 μm was crushed to obtain a flaky natural graphite with a d50 of 8.5 μm. The flaky natural graphite obtained was mixed with 12 parts by weight of liquid oil as a granulating agent, and then spheroidized. The granulating material was removed by heat treatment to obtain a spheroidized natural graphite (average particle size (d50) 12.6 μm, SA 19.1 μm). 2 / g, tap density 0.94g / cm 3 ). The obtained spheroidized graphite was filled into a rubber container and sealed, and isotropically pressurized at 200 MPa to control the physical properties of the powder. The obtained molded product was crushed and classified. The obtained spheroidized graphite powder was mixed with asphalt adjusted to 0.02 wt% ash, 20 wtppm metal impurities, and 1 wt% Qi as an amorphous carbon precursor, and the pressure in the furnace was reduced to less than 10 torr, and the pressure was restored to atmospheric pressure with nitrogen. Nitrogen was further circulated to make the oxygen concentration in the furnace <100 ppm, and a heat treatment of 1300°C was carried out in an inert gas. The obtained calcined product was crushed and classified to obtain a composite carbon material containing amorphous carbon substances on the surface of the graphite particles. The calcination yield confirmed that the weight ratio of spheroidized graphite particles to amorphous carbon in the obtained composite carbon material (spheroidized graphite particles: amorphous carbon) was 1:0.06. In addition to setting the negative electrode density to 1.5 g / cm 3 In addition, the same battery characteristics as in Example A1 were measured. The results are shown in Table 2.

[0618] (Example A4)

[0619] A composite carbon material was obtained in the same manner as in Example A1 except that the weight ratio of spheroidized graphite particles to amorphous carbon (spheroidized graphite particles: amorphous carbon) was set to 1:0.08. The same measurements as in Example A3 were performed, and the results are shown in Table 2.

[0620] (Comparative Example A4)

[0621] The flaky natural graphite with an average particle size (d50) of 100 μm was crushed to obtain a flaky natural graphite with a d50 of 8.5 μm. The pitch as a granulating agent was heated to a liquid state and mixed into the obtained flaky natural graphite, and then spheroidized while being heated in the same manner. After the obtained spheroidized natural graphite with asphalt attached was subjected to a heat treatment at 1300°C in an inert gas, the obtained burnt product was crushed and graded, thereby obtaining a composite carbon material containing amorphous carbon material on the surface of the graphite particles. The weight ratio of spheroidized graphite particles to amorphous carbon in the obtained composite carbon material (spheroidized graphite particles: amorphous carbon) was confirmed to be 1:0.08 by the burning yield. The same measurement as in Example A3 was performed, and the results are shown in Table 2.

[0622] (Comparative Example A5)

[0623] The flaky natural graphite with an average particle size (d50) of 100 μm was crushed to obtain a flaky natural graphite with a d50 of 8.5 μm. The flaky natural graphite obtained was mixed with 12 parts by weight of paraffin oil as a granulating agent, and then spheroidized. The granulating material was removed by heat treatment to obtain a spheroidized natural graphite (average particle size (d50) 12.6 μm, SA 15.3 μm). 2 / g, tap density 0.88g / cm 3 ). The obtained spheroidized graphite powder was mixed with pitch as an amorphous carbon precursor, and after heat treatment at 1300°C in an inert gas, the fired product was crushed and graded to obtain a negative electrode material, which is a composite carbon material containing amorphous carbon material on the surface of graphite particles. The firing yield confirmed that the weight ratio of spheroidized graphite particles to amorphous carbon in the obtained negative electrode material (composite carbon material) (spheroidized graphite particles: amorphous carbon) was 1:0.07. The same measurement as in Example A3 was performed, and the results are shown in Table 2.

[0624] [Table 1]

[0625]

[0626] [Table 2]

[0627]

[0628] Based on the results in Tables 1 and 2, Figure 1 and Figure 2 The relationship between the high temperature storage characteristics and the low temperature output characteristics is shown in the graphs. In these graphs, approximate straight lines are shown based on the results of the examples and the comparative examples. In each graph, the results in the upper right range mean that the balance between the high temperature storage characteristics and the low temperature output characteristics is excellent.

[0629] From Tables 1, 2 and Figure 1 , 2 As clearly shown, Examples A1 to A4 having a specified pore volume and thermal properties in the DTA curve within the specified range have high initial efficiency, excellent rapid discharge characteristics, and show an excellent balance between low-temperature output characteristics and high-temperature storage characteristics. On the other hand, for Comparative Examples A1, A4, and A5 having a pore volume greater than the specified range, Comparative Example A2 having a pore volume greater than the specified range and not having the specified thermal properties, and Comparative Example A3 not having the specified thermal properties, they have low initial efficiency, rapid discharge characteristics, and a poor balance between low-temperature output characteristics and high-temperature storage characteristics. In addition, the surface is not coated with amorphous carbon, and the Raman half-peak width Δν is B (cm- 1 ), the Raman R2 value and the Raman R3 value of the reference example A1 which are smaller than the prescribed ranges have low initial efficiency and a poor balance between low-temperature output characteristics and high-temperature storage characteristics.

[0630] [Experiment B]

[0631] Hereinafter, the content of the present invention will be described in more detail by way of examples, but the present invention is not limited to the following examples as long as it does not exceed its purport. It should be noted that the values ​​of various manufacturing conditions and evaluation results in the following examples have the meaning of preferred values ​​as the upper or lower limits in the embodiments of the present invention, and the preferred range may also be the range specified by combining the values ​​of the aforementioned upper or lower limits with the values ​​of the following examples, or by combining the values ​​of the examples with each other.

[0632] <Production of negative electrode sheet>

[0633] Using the negative electrode material prepared under the conditions described below as the negative electrode active material, a negative electrode layer having an active material layer density of 1.5±0.03 g / cm 3 Specifically, 50.00±0.02g of 1 wt% sodium carboxymethyl cellulose aqueous solution (0.500g in terms of solid content) and 1.00±0.05g of styrene-butadiene rubber aqueous dispersion with a weight average molecular weight of 270,000 (0.5g in terms of solid content) were stirred for 5 minutes in a Keyence mixer and degassed for 30 seconds to obtain a slurry.

[0634] The slurry was applied to a copper foil with a thickness of 10 μm as a current collector in a width of 10 cm using a die coater so that the negative electrode material adhered to 10.00±0.2 mg / cm 2 After drying, the mixture was cut into pieces with a width of 5 cm and rolled using a roller with a diameter of 20 cm. The density of the active material layer was adjusted to 1.5 ± 0.03 g / cm 3, and an electrode sheet was obtained.

[0635] <Production of positive electrode sheet>

[0636] The positive electrode was prepared as follows. First, 85 wt% of lithium nickel-manganese-cobalt oxide (LiNiMnCoO2) as the positive electrode active material, 10 wt% of acetylene black as the conductive material, and 5 wt% of polyvinylidene fluoride (PVdF) as the binder were mixed in N-methylpyrrolidone solvent to obtain a slurry. The slurry was coated on a 15 μm thick aluminum foil as the collector using a blade coater so that the positive electrode material adhered to 22.5 ± 0.2 mg / cm 2 The positive electrode was dried at 130°C and rolled to adjust the positive electrode density to 2.60±0.05 g / cm 3 , and an electrode sheet was obtained.

[0637] <Method for producing non-aqueous secondary battery (laminated battery)>

[0638] The 10.0±0.3 mg / cm 2 The density of the negative electrode material and the active material layer is 1.5±0.03g / cm 3 The negative electrode sheet, positive electrode sheet, and polyethylene separator were stacked in the order of negative electrode, separator, and positive electrode. The battery element obtained above was wrapped in a cylindrical aluminum laminate film, and an electrolyte was injected. The electrolyte was obtained by dissolving LiPF6 at 1 mol / L in a mixed solvent of ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) (volume ratio = 3:3:4), and then vacuum sealed to make sheet-shaped non-aqueous secondary batteries. Furthermore, in order to improve the adhesion between the electrodes, the sheet-shaped battery was clamped with a glass plate and pressurized.

[0639] <Method for producing non-aqueous secondary battery (coin-type battery)>

[0640] The 10.0±0.3 mg / cm 2 The density of the negative electrode material and the active material layer is 1.5±0.03g / cm 3 The electrode sheet was punched into a disc with a diameter of 12.5 mm as the negative electrode, and the lithium metal foil was punched into a disc with a diameter of 14 mm as the counter electrode. A separator (made of porous polyethylene film) impregnated with an electrolyte was placed between the two electrodes, and 2016 coin-shaped batteries were made. The electrolyte was obtained by dissolving LiPF6 at 1 mol / L in a mixed solvent of ethylene carbonate and ethyl methyl carbonate (volume ratio = 3:7).

[0641] <Discharge capacity(mAh / g)>

[0642] Using the non-aqueous secondary battery (2016 coin-type battery) produced by the above method, the capacity of the battery during charge and discharge was measured according to the following measurement method.

[0643] The lithium counter electrode was charged to 5 mV at a current density of 0.05 C, and then charged at a constant voltage of 5 mV until the current density reached 0.005 C. After lithium was doped into the negative electrode, the lithium counter electrode was discharged to 1.5 V at a current density of 0.1 C. The discharge capacity per unit weight of the negative electrode active material at this time was taken as the discharge capacity (mAh / g) of the material.

[0644] <Circulation expansion>

[0645] For non-aqueous secondary batteries that have not undergone charge and discharge cycles, initial charge and discharge were performed at 25°C with a voltage range of 4.1V to 3.0V and a current value of 0.2C (the current value for discharging the rated capacity of the 1-hour rate discharge capacity in 1 hour is set to 1C, the same below), and 2 cycles with a voltage range of 4.2V to 3.0V and a current value of 0.2C (constant voltage charging was further implemented at 4.2V for 2.5 hours during charging). At this point, the glass plate used for temporary fixing was removed, and the thickness of 9 points of one battery was measured using a contact thickness gauge manufactured by Mitutoyo Co., Ltd. of Japan, and the average value was taken as the "thickness before the cycle". Then, the battery was sandwiched with a glass plate again, and then a cycle test was performed in a constant temperature chamber at 45°C with 0.8C-CCCV charging, 0.8CCC discharging, and 1.5V cutoff conditions for 25 charge and discharges. Then, for the battery in the SOC 0% state, 9 points were measured at the same positions as before the cycle, and the average value was calculated as the "thickness after the cycle" and set as: cycle expansion = {(thickness after the cycle) / (thickness before the cycle)-1}×100(%).

[0646] <Quick charging characteristics>

[0647] For coin-type batteries that have not undergone charge and discharge cycles, initial charge and discharge were performed at 25°C with a voltage range of 4.1V to 3.0V and a current value of 0.2C (the current value for discharging the rated capacity of the 1-hour rate discharge capacity in 1 hour is set to 1C, the same below) for 3 cycles, and with a voltage range of 4.2V to 3.0V and a current value of 0.2C (constant voltage charging was further implemented at 4.2V for 2.5 hours during charging) for 2 cycles. Then, CC charging was performed from the state of SOC 0% to SOC 100% at a current value of 3C. The dV / dQ value was calculated by the differential of the obtained voltage (V)-capacity (Q) curve, and the capacity value when dV / dQ=0 when the dV / dQ value reaches the positive region from the negative region was obtained, and it was set as: fast charging characteristics = {capacity value (mAh) when dV / dQ=0} / {capacity value (mAh) at SOC 100%}×100(%).

[0648] (Example B1)

[0649] The flaky natural graphite with an average particle size (d50) of 100 μm was crushed to obtain flaky natural graphite with a d50 of 11.1 μm. 12 parts by weight of liquid oil as a granulating agent were mixed with 100 parts by weight of the obtained flaky natural graphite, and then spheroidized, and the granulating agent was removed by heat treatment to obtain spheroidized natural graphite. The obtained spheroidized graphite was filled into a rubber container, sealed, and isotropically pressurized at 200 MPa to control the amount of mercury removal / mercury injection (B / A). The obtained molded product was crushed and classified, and the various physical properties of the obtained spheroidized graphite powder (negative electrode material raw material) are shown in Table 1. It should be noted that the amount of mercury removal / mercury injection (B / A)×100(%) in the aforementioned mercury porosity method is 61.5%. The spheroidized graphite powder was mixed with asphalt adjusted to 0.02 wt% ash, 20 wtppm metal impurities, and 1 wt% Qi as an amorphous carbon precursor, and the pressure in the furnace was reduced to less than 10 torr, and the pressure was restored to atmospheric pressure with nitrogen. Nitrogen was further circulated to make the oxygen concentration in the furnace <100 ppm, and a heat treatment of 1300°C was implemented in an inert gas. The obtained calcined product was crushed and graded to obtain a composite carbon material containing amorphous carbon material on the surface of the graphite particles. The calcination yield confirmed that the weight ratio of spheroidized graphite particles to amorphous carbon in the obtained composite carbon material (spheroidized graphite particles: amorphous carbon) was 1:0.08. The various physical properties of the negative electrode material obtained in this way are shown in Table 3. In addition, the above-mentioned discharge capacity, cycle expansion, and rapid charging characteristics were measured using the obtained negative electrode material, and the results are shown in Table 3. It should be noted that A and B in Table 3 show values ​​obtained by rounding off the fourth decimal place.

[0650] (Example B2)

[0651] The flaky natural graphite with an average particle size (d50) of 100 μm was crushed to obtain flaky natural graphite with a d50 of 8.5 μm. After mixing 12 parts by weight of liquid oil as a granulating agent into the obtained flaky natural graphite, a spheroidization treatment was performed, and then the granulating agent was removed by heat treatment to obtain spheroidized natural graphite. The obtained spheroidized graphite was filled into a rubber container, sealed, and isotropically pressurized at 200 MPa to control the amount of mercury removal / mercury injection (B / A). The obtained molded product was crushed and classified, and the various physical properties of the obtained spheroidized graphite powder (negative electrode material raw material) are shown in Table 2. It should be noted that the amount of mercury removal / mercury injection (B / A)×100(%) in the aforementioned mercury porosity method is 69.9%. The spheroidized graphite powder was mixed with asphalt adjusted to 0.02 wt% ash, 20 wtppm metal impurities, and 1 wt% Qi as an amorphous carbon precursor, and the pressure in the furnace was reduced to less than 10 torr, and the pressure was restored to atmospheric pressure with nitrogen. Nitrogen was further circulated to make the oxygen concentration in the furnace <100 ppm, and a heat treatment of 1300°C was implemented in an inert gas. The obtained calcined product was crushed and graded to obtain a composite carbon material containing amorphous carbon material on the surface of the graphite particles. The calcination yield confirmed that the weight ratio of spheroidized graphite particles to amorphous carbon in the obtained composite carbon material (spheroidized graphite particles: amorphous carbon) was 1:0.06. The various physical properties of the negative electrode material obtained in this way are shown in Table 3. In addition, the above-mentioned discharge capacity, cycle expansion, and rapid charging characteristics were measured using the obtained negative electrode material, and the results are shown in Table 3.

[0652] (Comparative Example B1)

[0653] The spherical natural graphite with an average particle size (d50) of 100 μm was spheroidized to obtain spherical natural graphite with an average particle size (d50) of 16.2 μm and a BET specific surface area (SA) of 6.9 m 2 / g, tap density 1.00g / cm 3). The mercury removal amount / mercury entry amount (B / A)×100 (%) of the obtained spheroidized graphite powder (raw material of negative electrode material) in the aforementioned mercury porosimetry method is 27.5%. The spheroidized graphite powder is mixed with tar adjusted to an ash content of <0.01%, a metal impurity content of 60 ppm, and Qi <0.1% as an amorphous carbon precursor, and a decompression treatment is performed to make the pressure in the furnace below 10 torr, and the pressure is restored to atmospheric pressure with nitrogen, and nitrogen is further circulated to make the oxygen concentration in the furnace <100 ppm, and a heat treatment at 1300°C is implemented. The obtained calcined product is crushed and classified to obtain a negative electrode material, which is a composite carbon material containing amorphous carbon material on the surface of graphite particles. The weight ratio of spheroidized graphite particles to amorphous carbon (spheroidized graphite particles: amorphous carbon) in the obtained negative electrode material (composite carbon material) is confirmed to be 1:0.03 from the calcination yield. The above-mentioned discharge capacity, cycle expansion, and rapid charge characteristics were measured using the negative electrode material obtained in this way. The results are shown in Table 3.

[0654] (Comparative Example B2)

[0655] The flaky natural graphite with an average particle size (d50) of 100 μm was spheroidized to obtain spheroidized natural graphite (average particle size (d50) 10.9 μm, BET specific surface area (SA) 8.1 m 2 / g, tap density 0.90g / cm 3 ). The mercury removal amount / mercury entry amount (B / A)×100(%) of the obtained spheroidized graphite powder in the aforementioned mercury porosimetry method is 28.3%. The spheroidized graphite powder is mixed with tar adjusted to an ash content of less than 0.01%, a metal impurity content of 60 ppm, and Qi less than 0.1% as an amorphous carbon precursor, and a decompression treatment is performed to make the pressure in the furnace less than 10 torr, and the pressure is restored to atmospheric pressure with nitrogen. Nitrogen is further circulated to make the oxygen concentration in the furnace less than 100 ppm, and a heat treatment at 1300°C is implemented. The obtained calcined product is crushed and classified to obtain a negative electrode material, which is a composite carbon material containing amorphous carbon material on the surface of graphite particles. The weight ratio of spheroidized graphite particles to amorphous carbon (spheroidized graphite particles: amorphous carbon) in the obtained negative electrode material (composite carbon material) is confirmed to be 1:0.04 from the calcination yield. The above-mentioned discharge capacity, cycle expansion, and rapid charge characteristics were measured using the negative electrode material obtained in this way. The results are shown in Table 3.

[0656] (Comparative Example B3)

[0657] The spherical natural graphite with an average particle size (d50) of 100 μm was spheroidized to obtain spherical natural graphite with an average particle size (d50) of 7.2 μm and a BET specific surface area (SA) of 11.1 m2 / g, tap density 0.81g / cm 3 ). The mercury removal amount / mercury entry amount (B / A)×100(%) of the obtained spheroidized graphite powder in the aforementioned mercury porosimetry method is 41.2%. The spheroidized graphite powder is mixed with tar adjusted to an ash content of less than 0.01%, a metal impurity content of 60 ppm, and Qi less than 0.1% as an amorphous carbon precursor, and a decompression treatment is performed to make the pressure in the furnace less than 10 torr, and the pressure is restored to atmospheric pressure with nitrogen. Nitrogen is further circulated to make the oxygen concentration in the furnace less than 100 ppm, and a heat treatment at 1300°C is implemented. The obtained calcined product is crushed and classified to obtain a negative electrode material, which is a composite carbon material containing amorphous carbon material on the surface of graphite particles. The weight ratio of spheroidized graphite particles to amorphous carbon (spheroidized graphite particles: amorphous carbon) in the obtained negative electrode material (composite carbon material) is confirmed to be 1:0.03 from the calcination yield. The above-mentioned discharge capacity, cycle expansion, and rapid charge characteristics were measured using the negative electrode material obtained in this way. The results are shown in Table 3.

[0658] (Comparative Example B4)

[0659] The above-mentioned discharge capacity, cycle expansion, and rapid charge characteristics were measured using artificial graphite containing amorphous carbon on the surface. The results are shown in Table 3.

[0660] [Table 3]

[0661]

[0662] Figure 3 The relationship between the amount of mercury removal / mercury injection (B / A) and the cycle expansion of Examples B1 to B2 and Comparative Examples B1 to B3 is shown. Figure 3 It is found that by using the negative electrode material raw material and the negative electrode material according to the second embodiment of the present invention, a lithium ion secondary battery having high discharge capacity, suppressed cycle expansion, and excellent rapid charge characteristics can be obtained.

[0663] [Experiment C]

[0664] Hereinafter, the content of the present invention will be described in more detail by way of examples, but the present invention is not limited to the following examples as long as it does not exceed its purport. It should be noted that the values ​​of various manufacturing conditions and evaluation results in the following examples have the meaning of preferred values ​​as the upper or lower limits in the embodiments of the present invention, and the preferred range may also be the range specified by combining the values ​​of the aforementioned upper or lower limits with the values ​​of the following examples, or by combining the values ​​of the examples with each other.

[0665] <Production of negative electrode sheet>

[0666] Using the negative electrode material prepared under the conditions described below as the negative electrode active material, a negative electrode layer having an active material layer density of 1.65±0.03 g / cm 3 Specifically, 50.00±0.02g of 1 wt% sodium carboxymethyl cellulose aqueous solution (0.500g in terms of solid content) and 1.00±0.05g of styrene-butadiene rubber aqueous dispersion with a weight average molecular weight of 270,000 (0.5g in terms of solid content) were stirred for 5 minutes in a Keyence mixer and degassed for 30 seconds to obtain a slurry.

[0667] The slurry was applied to a copper foil with a thickness of 10 μm as a current collector in a width of 10 cm using a die coater so that the negative electrode material adhered to 10.00±0.2 mg / cm 2 After drying, the mixture was cut into pieces with a width of 5 cm and rolled using a roller with a diameter of 20 cm. The density of the active material layer was adjusted to 1.5 ± 0.03 g / cm 3 and 1.65±0.03g / cm 3 The density of the active material layer was 1.65 g / cm 3 The peak value of the load applied when the electrode sheet is formed is set as the pressing load [kgf / 5cm] and is shown in Table 4.

[0668] <Production of positive electrode sheet>

[0669] The positive electrode was prepared as follows. First, 85 wt% of lithium nickel-manganese-cobalt oxide (LiNiMnCoO2) as the positive electrode active material, 10 wt% of acetylene black as the conductive material, and 5 wt% of polyvinylidene fluoride (PVdF) as the binder were mixed in N-methylpyrrolidone solvent to obtain a slurry. The slurry was coated on a 15 μm thick aluminum foil as the collector using a blade coater so that the positive electrode material adhered to 22.5 ± 0.2 mg / cm 2 The positive electrode was dried at 130°C and rolled to adjust the positive electrode density to 2.60±0.05 g / cm 3 , and an electrode sheet was obtained.

[0670] <Method for producing non-aqueous secondary battery (laminated battery)>

[0671] The 10.0±0.3 mg / cm 2 The density of the negative electrode material and the active material layer is 1.65±0.03g / cm 3(negative electrode sheet and positive electrode sheet), and polyethylene separator were stacked in the order of negative electrode, separator, and positive electrode. The battery element obtained above was wrapped in a cylindrical aluminum laminate film, and an electrolyte was injected. The electrolyte was obtained by dissolving LiPF6 at 1 mol / L in a mixed solvent of ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) (volume ratio = 3:3:4), and then vacuum sealed to make sheet-shaped non-aqueous secondary batteries. Furthermore, in order to improve the adhesion between the electrodes, the sheet-shaped battery was clamped with a glass plate and pressurized.

[0672] <Expansion measurement>

[0673] For non-aqueous secondary batteries that have not undergone charge and discharge cycles, initial charge and discharge were performed at 25°C with a voltage range of 4.1V to 3.0V and a current value of 0.2C (the current value for discharging the rated capacity of the 1-hour rate discharge capacity in 1 hour is set to 1C, the same below) for 3 cycles, and with a voltage range of 4.2V to 3.0V and a current value of 0.2C (when charging, constant voltage charging was further implemented at 4.2V for 2.5 hours). At this point, the glass plate used for temporary fixing was removed, and the thickness of 9 points of one battery was measured using a contact thickness gauge manufactured by Mitutoyo Co., Ltd. of Japan, and the average value was taken as the thickness before the cycle. Then, the battery was sandwiched with a glass plate again, and then a cycle test was performed in a constant temperature bath at 45°C with 0.8C-CCCV charging, 0.8CCC discharging, and 1.5V cutoff conditions for 25 charge and discharge cycles. Then, for the battery at SOC 0%, nine points were measured at the same positions as before the cycle, and the average value was calculated. The difference between the average value and the thickness before the cycle was taken as the expansion of the electrode plate during the cycle. The difference is shown in Table 4.

[0674] (Example C1)

[0675] The flaky natural graphite with an average particle size (d50) of 100 μm was crushed to obtain a flaky natural graphite with a d50 of 9 μm. The flaky natural graphite obtained was mixed with 12 parts by weight of liquid oil as a granulating agent, and then spheroidized. The granulating material was removed by heat treatment to obtain a spheroidized natural graphite (average particle size (d50) 13 μm, SA 19 μm). 2 / g, tap density 0.94g / cm 3). The obtained spheroidized natural graphite is filled into a rubber container and sealed. After isotropic pressure treatment at 200 MPa, the obtained molded product is crushed and classified. The obtained spheroidized natural graphite powder is mixed with asphalt adjusted to 0.02% by weight of ash, 20% by weight of metal impurities, and 1% by weight of Qi as an amorphous carbon precursor, and the pressure in the furnace is reduced to less than 10 torr. The pressure is restored to atmospheric pressure with nitrogen, and nitrogen is further circulated to make the oxygen concentration in the furnace <100 ppm, and a heat treatment of 1300°C is implemented in an inert gas. The obtained calcined product is crushed and classified to obtain a negative electrode material, which is a composite carbon material containing amorphous carbon material on the surface of graphite particles. The weight ratio of spheroidized graphite particles and amorphous carbonaceous material (spheroidized graphite particles: amorphous carbonaceous material) in the obtained negative electrode material (composite carbon material) is confirmed to be 1:0.06 by the calcination yield. In addition, for the obtained negative electrode material, the tap density, tablet density, true density, and micropore distribution were measured according to the above method, and the results are shown in Table 4. In Table 4, "peak top micropore diameter" is the micropore diameter of the peak top of the peak on the side with a smaller micropore diameter. In addition, the mercury intrusion method measurement results are shown in Figure 6 .

[0676] (Example C2)

[0677] The flaky natural graphite with an average particle size (d50) of 100 μm was crushed to obtain a flaky natural graphite with a d50 of 11 μm. The flaky natural graphite obtained was mixed with 12 parts by weight of liquid oil as a granulating agent, and then spheroidized. The granulating material was removed by heat treatment to obtain a spheroidized natural graphite (average particle size (d50) 16 μm, SA 15 μm). 2 / g, tap density 0.96g / cm 3). The obtained spheroidized graphite was filled into a rubber container and sealed. After isotropic pressure treatment at 200 MPa, the obtained molded product was crushed and classified. The obtained spheroidized graphite powder was mixed with asphalt adjusted to 0.02% by weight ...

Claims

1. A negative electrode material for a non-aqueous secondary battery, comprising graphite having an amorphous carbon material on at least a portion of its surface, The cumulative pore volume of the non-aqueous secondary battery negative electrode material in the range of micropore diameters of 0.01 μm or more and 1 μm or less is less than 0.070 mL / g, and in a DTA curve obtained by differential thermal analysis (DTA) in an air flow, at least one of the following conditions 1) and 2) is satisfied, 1) There is no exothermic peak in the temperature range of 550°C or more and 650°C or less, 2) It has an exothermic peak in a temperature range of 550° C. to 650° C., and the area of ​​the exothermic peak exceeds 0 μV·s / mg and is 90 μV·s / mg or less.

2. A negative electrode material for a non-aqueous secondary battery, wherein the Raman R1 value calculated by the following formula α is 0.15 or more and 1.00 or less, and the Raman half peak width (Δν B ) is 65cm -1 Over 400cm -1 the following, The cumulative pore volume of the non-aqueous secondary battery negative electrode material in the range of micropore diameters of 0.01 μm or more and 1 μm or less is less than 0.070 mL / g, and in a DTA curve obtained by differential thermal analysis (DTA) in an air flow, at least one of the following conditions 1) and 2) is satisfied, 1) There is no exothermic peak in the temperature range of 550°C or more and 650°C or less, 2) having an exothermic peak in a temperature range of 550°C to 650°C, and an area of ​​the exothermic peak exceeding 0 μV·s / mg and being 90 μV·s / mg or less, Formula α: [Raman R1 value] = [1360 cm in Raman spectroscopy analysis -1 Nearby peaks P B Strength I B ] / [1580cm -1 Nearby peaks P A Strength I A ].

3. The negative electrode material for a non-aqueous secondary battery according to claim 1 or 2, wherein: In the DTA curve, the following condition 3) is satisfied, 3) Having an exothermic starting temperature in a temperature range of 550°C to 750°C.

4. The negative electrode material for a non-aqueous secondary battery according to claim 1 or 2, wherein In the DTA curve, the following condition 4) is satisfied, 4) It has an exothermic peak in a temperature range exceeding 650°C and not more than 1000°C.

5. The negative electrode material for a non-aqueous secondary battery according to claim 1 or 2, wherein The nonaqueous secondary battery negative electrode material has a Raman R2 value calculated by the following formula β of 0.03 or more and 0.60 or less, and a Raman R3 value calculated by the following formula γ of 0.10 or more and 1.00 or less. Formula β: [Raman R2 value] = [1580cm in Raman spectroscopy analysis -1 Nearby peaks P A With 1360cm -1 Nearby peaks P B The intensity of the valley (minimum) between C ] / [1580cm -1 Nearby peaks P A Strength I A ] Formula γ: [Raman R3 value] = [1580cm in Raman spectroscopy analysis -1 Nearby peaks P A With 1360cm -1 Nearby peaks P B The intensity of the valley (minimum) between C ] / [1360cm -1 Nearby peaks P B Strength I B ].

6. The negative electrode material for a non-aqueous secondary battery according to claim 1 or 2, wherein the BET specific surface area (SA) is 0.5 m 2 / g or more and 10.0m 2 / g or less.

7. The negative electrode material for a non-aqueous secondary battery according to claim 1 or 2, wherein the tap density is 0.60 g / cm 3 Above and 1.40g / cm 3 the following.

8. The negative electrode material for a non-aqueous secondary battery according to claim 1 or 2, wherein: The non-aqueous secondary battery negative electrode material has a lattice spacing (d002) of 0.340 nm or less as determined by X-ray diffraction, and a crystallite size (Lc) in the c-axis direction of 90 nm or more.

9. A negative electrode for a non-aqueous secondary battery, comprising: Current collector, and An active material layer is formed on the current collector, in, The active material layer contains the negative electrode material according to claim 1 or 2.

10. A non-aqueous secondary battery comprising a positive electrode, a negative electrode and an electrolyte, wherein: The negative electrode is the negative electrode for a non-aqueous secondary battery according to claim 9.

11. A negative electrode material for a non-aqueous secondary battery, comprising graphite having at least one of an amorphous carbon material and a graphite material on at least a portion of its surface, The micropore distribution of the non-aqueous secondary battery negative electrode material measured by mercury intrusion has two or more peaks, and when the cumulative pore volume below the minimum value between the peak with the smallest micropore diameter and the valley of the next peak is set to y [mL / g], and the coverage of the amorphous carbon material and the graphite material on the graphite surface is set to x (%), the following formulas (1) and (2) are satisfied, and the micropore diameter at the peak top of the peak with the smallest micropore diameter is 360 nm or less, Formula (1): y>0.005 Formula (2): y<-0.006x+0.

12.

12. A negative electrode material for a non-aqueous secondary battery, comprising graphite having at least one of an amorphous carbon material and a graphite material on at least a portion of its surface, The non-aqueous secondary battery negative electrode material has a micropore distribution measured by mercury intrusion porosimetry with two or more peaks, and the cumulative pore volume below the minimum value between the peak with the smallest micropore diameter and the valley of the next peak is set as y [mL / g], and the coverage of the amorphous carbon material and the graphite material on the graphite surface is set as x (%), and satisfies the following formulas (1) and (3), Formula (1): y>0.005 Formula (3): y<-0.006x+0.

079.

13. The negative electrode material for a non-aqueous secondary battery according to claim 11 or 12, wherein: The graphite is natural graphite.

14. The negative electrode material for a non-aqueous secondary battery according to claim 11 or 12, wherein the true density is 2.20 g / cm 3 Above and less than 2.262g / cm 3 .

15. The negative electrode material for a non-aqueous secondary battery according to claim 11 or 12, wherein the tap density is 0.85 g / cm 3 above. 16 . The negative electrode material for a non-aqueous secondary battery according to claim 11 , wherein at least a portion of the surface of the negative electrode material is covered with an amorphous carbon material. 17 . The negative electrode material for a non-aqueous secondary battery according to claim 11 , comprising spherical graphite particles, wherein the spherical graphite particles are obtained by granulating flaky graphite, scale-like graphite, and blocky graphite.

18. The negative electrode material for a non-aqueous secondary battery according to claim 17, wherein The granulation treatment is a treatment for imparting at least any of the mechanical energy of impact, compression, friction, and shearing force.

19. The negative electrode material for a non-aqueous secondary battery according to claim 17 or 18, wherein The granulation treatment is a treatment in which a rotating member rotating at high speed is provided in a housing, and a rotor provided with a plurality of blades is provided in the housing, and the rotor is rotated at high speed to impart any of impact, compression, friction, and shearing force to graphite introduced into the interior to perform granulation.

20. A negative electrode for a non-aqueous secondary battery, comprising: Current collector, and An active material layer is formed on the current collector, in, The active material layer contains the negative electrode material according to claim 11 or 12.

21. A non-aqueous secondary battery comprising: a positive electrode, a negative electrode, and an electrolyte, wherein: The negative electrode is the negative electrode for a non-aqueous secondary battery according to claim 20.

22. A method for producing a negative electrode material, wherein the cumulative pore volume of the negative electrode material in the range of micropore diameters of 0.01 μm or more and 1 μm or less is less than 0.070 mL / g, and in a DTA curve obtained by differential thermal analysis (DTA) in an air flow, at least one of the following conditions 1) and 2) is satisfied, 1) There is no exothermic peak in the temperature range of 550°C or more and 650°C or less, 2) having an exothermic peak in a temperature range of 550°C to 650°C, and an area of ​​the exothermic peak exceeding 0 μV·s / mg and being 90 μV·s / mg or less, in, The method for manufacturing the negative electrode material comprises: The graphite is subjected to isotropic pressure treatment.

23. The method for producing a negative electrode material according to claim 22, wherein: The negative electrode material includes graphite having an amorphous carbon material on at least a portion of its surface.

24. The method for producing a negative electrode material according to claim 22, wherein: The negative electrode material has a Raman R1 value calculated by the following formula α of 0.15 or more and 1.00 or less, and a Raman half-peak width (Δν B ) is 65cm -1 Over 400cm -1 the following, Formula α: [Raman R1 value] = [1360 cm in Raman spectroscopy analysis -1 Nearby peaks P B Strength I B ] / [1580cm -1 Nearby peaks P A Strength I A ].

25. A method for producing a raw material for a negative electrode, wherein the raw material for a negative electrode comprises graphite, and when the amount of mercury introduced by mercury injection is A and the amount of mercury removed is B, the following formula (1) is 45% or more, Formula (1) B / A×100(%), in, The value of the above formula (1) is calculated from the amount of mercury introduced A and the amount of mercury removed B measured by the following mercury intrusion method: By using a mercury porosimeter, the negative electrode material raw material is weighed to a value of about 0.2 g, sealed in a powder container, and degassed for 10 minutes at room temperature and a vacuum of less than 50 μmHg to implement pretreatment, then the pressure is reduced to 4 psia, mercury is introduced into the container, the pressure is increased from 4 psia to 40000 psia in a stepwise manner, and then the pressure is reduced to 25 psia, the number of steps during the increase is set to 42 points or more, and the number of steps during the reduction is set to 39 points or more, after maintaining a balance time of 10 seconds in each step, the mercury intrusion amount is measured, and the micropore distribution is calculated from the mercury intrusion curve obtained in this way using the Washburn formula, wherein the surface tension of mercury is 485 dyne / cm and the contact angle is 140° for calculation, Mercury injection amount A = cumulative pore volume above 0.01 μm and below 0.6 μm on the injection side, the unit is mL / g; Mercury withdrawal amount B = mercury withdrawal amount until 25 psia on the withdrawal side, with the unit of mL / g. Wherein, the method for manufacturing the negative electrode material raw material comprises: The graphite is subjected to isotropic pressure treatment.

26. A method for producing a negative electrode material, wherein the micropore distribution of the negative electrode material measured by mercury intrusion has two or more peaks, and when the cumulative pore volume below the minimum value between the peak with the smallest micropore diameter and the valley of the next peak is set to y [mL / g], and the coverage of the amorphous carbon material and the graphite material on the graphite surface is set to x (%), the following formulas (1) and (2) are satisfied, and the micropore diameter at the peak top of the peak with the smallest micropore diameter is 360 nm or less, Formula (1): y>0.005 Formula (2): y<-0.006x+0.12, in, The method for manufacturing the negative electrode material comprises: The graphite is subjected to isotropic pressure treatment.

27. A method for producing a negative electrode material, wherein the micropore distribution of the negative electrode material measured by mercury intrusion has two or more peaks, the cumulative pore volume below the minimum value between the peak with the smallest micropore diameter and the valley of the next peak is set to y [mL / g], and the coverage of the amorphous carbon material and the graphite material on the graphite surface is set to x (%), and the following formulas (1) and (3) are satisfied: Formula (1): y>0.005 Formula (3): y<-0.006x+0.079, in, The method for manufacturing the negative electrode material comprises: The graphite is subjected to isotropic pressure treatment.

28. The method for producing a negative electrode material according to claim 26 or 27, wherein: The negative electrode material includes graphite having at least one of an amorphous carbon material and a graphite material on at least a portion of the surface.

Citation Information

Patent Citations

  • Carbon material and nonaqueous secondary battery

    JP2017037711A

  • Carbon material and nonaqueous secondary battery

    JP2017045574A

  • Negative electrode material for nonaqueous secondary battery, negative electrode for nonaqueous secondary battery, and nonaqueous secondary battery

    JP2018163868A